Scale-resolved water and hydrocarbon accessibility in lacustrine shales revealed using contrast-matched small-angle neutron scattering - Zhouhua Wang; Xintong Zhang; Yun Li; He Cheng; Shuoshi Wang; Jianming Fan; Huang Liu; Hao Wang (Fuel, 2027)

Chalcopyrite mitigates N2O emission in bioretention systems: promoting denitrification and activating nitrous oxide reductase - Huan Xiao; Cheng Cheng; Yunsong Yuan; Wenlin Zhao; Xinyue Wang; Hao Zheng; Haoyu Wang; Qiyuan Li; Hongxiang Chai (Water Research, 2026)

Experimental and numerical analysis on attenuation laws of blast wave propagating in a Z-shaped underground tunnel - Qiu Lu; Yong Peng; Xiangyu Li; Xiaoguang Xue; Hao Cheng; Ziguo Wang (Tunnelling and Underground Space Technology, 2026)

Plastic film mulching enhances crop productivity by improving physiological and ecological characteristics in arid irrigation areas - Cheng Li; Mengtian Li; Jingui Wang; Lihua Liu; Junye Zhou; Yiteng Wang; Hao Feng; Yunxin Zhang; Lishu Wang; Wenxin Zhang (Soil and Tillage Research, 2026)

Characteristics and constitutive model of segmented damage and fracture in granite under thermo-hydro-mechanical (THM) condition - Luping Cheng; Chun Wang; Yi Tan; Hao Li; Zonghong Zhou; Yumeng Ren; Juanjuan Li; Taihao Cui (Geothermics, 2026)

A process of microwave pyrolysis treatment of amidoxime functionalized fiber and enrichment of uranium for uranium extraction from seawater - Shen Zhang; Wencai Cheng; Junwen Tan; Benyao Yu; Tianjun Li; Congcong Ding; Xirui Lu; Jun Wen; Hao Li (Desalination, 2026)

Anaerobic co-digestion of model lignocellulosic components and sludge under pH adjustment: Component interactions and methanogenic performance - Pengfei Li; Qiwen Hu; Hao Zhao; Chongbo Cheng; Gang Li; Chao He; Xiaoman He; Caiyou Zeng; Dekui Shen; Youzhou Jiao (Biomass and Bioenergy, 2026)

Single-cell transcriptomic profiling identifies TIMP1 as a diagnostic marker linked to macrophage ferroptosis in ulcerative colitis - Wen-Hao Xiong; Shuo Huang; Yan-Hong Liu; Guo-Shan Chen; Dan-Zhou Li; Yong-Cheng Di; Wen-Bin Song; Yong-Chao Zhang; Yi-Fan Wang; Feng Qi (Tissue and Cell, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Mechanism of water and nutrient competition between shelterbelts and farmland under different irrigation patterns in the Hexi Corridor oasis area, China - Yulian Hao; Haiyang Xi; Wenju Cheng; Tengfei Yu; Baofeng Li; Tuo Han; Yuqing Chen; Linbo Qu; Zhehui Wang (Soil and Tillage Research, 2026)

ZmP5CS3 positively regulates drought tolerance by regulating proline biosynthesis and ROS homeostasis in maize seedlings - Shuai Zhao; Fashuai Li; Kuan Cheng; Hao Qi; Mingli Song; Xuehui Qian; Yanan Tian; Xinlei Feng; HaoYue Xu; Qian Liu; Jinhua Hu; Wei Chen; et al. (Plant Science, 2026)

Role of residual carbon in the fusion temperature regulation of ash-iron mixtures under entrained-flow gasification conditions - Hao Cheng; Guoqiang Cao; Zhongren Ba; Donghai Hu; Yongbin Wang; Chunyu Li; Jiantao Zhao; Yitian Fang (Fuel, 2026)

Association of combined exposure to polycyclic aromatic hydrocarbons, BTX and metals with metabolic syndrome risk - Xiaoyu Hao; Xiangkai Zhao; Zhiguang Gu; Bin Yang; Di Zhang; Rui Zhao; Xu Guo; Zhe Cheng; Gang Wang; Xiaohui Li; Junfeng Zhao; Zhiheng Li; et al. (Environmental Pollution, 2026)

A dual mechanical tuning framework for rigid pillared elastic metamaterials: Geometric reconfiguration and controllable prestress - Zu Shao; Tong Cheng; Yi Zhang; Wei Zhong Jiang; Zhu Kun Mi; Xiang Jie Wei; Xin Guo; Wang Lin Xiong; Kai Hao Lin; Chuang Li; Shu Hao Song; Cheng Shen; et al. (Engineering Structures, 2026)

Microalgae-based bioremediation of reverse osmosis concentrate (ROC): Mechanisms, techno-economic bottlenecks, and circular bioeconomy perspectives - Na-Hui Hao; Jun Li; Ya-Rong Qi; Zhuo Chen; Yu-Ming Wang; Yu-Jia Gao; Xu-Cheng Cai; Yu Hong; Hong-Ying Hu; Yin-Hu Wu (Desalination, 2026)

A Neoproterozoic arc-backarc system in the northern Yangtze Block: Implications for crustal growth and Rodinia reconstructions - Chao Chen; Hao Deng; Jin-Ling Yuan; Timothy Kusky; Qiang Chen; Zhen-Bing She; Ling-Yao Kong; Jiang Zhu; Hong-Mei Li; Jing-Meng Huang; Guo-Hu Wang; Cheng Yang; et al. (Earth-Science Reviews, 2026)

Gold and REE pre-enrichment in metasomatized Archean lithospheric mantle aided the genesis of Mesozoic giant ore deposits, eastern North China Craton - Shan-Shan Li; Kun-Feng Qiu; Timothy Kusky; Lu Wang; Hartwig E. Frimmel; Yi-Xue Gao; Tong Zhou; Deng-Yang He; Hao-Cheng Yu; Zheng-Yu Long; Tian-Shuo Liang; Ying-Jiu Wang; et al. (Earth-Science Reviews, 2026)

High efficiency water evaporation and purification performance of three-dimensional porous graphene oxide based photothermal evaporators - Qiao Wu; Saihong Ru; Mengxin Wang; Xiaoyu Zheng; Hao Cheng; Maoqing Fan; Wang Li (Chemical Engineering Journal, 2026)

Interface chemical bonding triggered rapid charge transfer for efficient photocatalytic H2 evolution on indium proximal to sulfur vacancy - Hui Chang; Cheng Luo; Pengrong Gu; Xiaojun Zheng; Wenjuan Fan; Hao Fu; Yufeng Li; Hu Li; Zhiqiang Jiang (Chemical Engineering Journal, 2026)

Nanoarchitectonics with synergistic optimization among various structural types in walnut green peel derived carbon materials for high-performance symmetric supercapacitors - Xiaoxue Liu; Hao Wu; Jun Zhang; Jinfeng Zheng; Duoliang Shan; Xiaoyang Cheng; Lingyan Li; Yilei Jing (Biomass and Bioenergy, 2026)

Machine learning-integrated multi-objective application and optimization framework for sulfur-based reactive filler towards nutrient removal - Jia-Min Xu; Jia-Qiang Lv; Wen-Ke He; Hong-Cheng Wang; Xiang-Li Zeng; Yu-Qi Wang; Wan-Xin Yin; Fang Huang; Gui-Jiao Zhang; Heng Dong; Yanchen Liu; Aijie Wang; et al. (Water Research, 2026)

Comparison between microscale sealed vessel pyrolysis (MSSV) and gold tube pyrolysis for the simulation of oil cracking - Shufen Liu; Pufan Wang; Xinyan Fang; Hao Li; Wenmin Jiang; Bin Cheng; Yun Li; Liangliang Wu (Organic Geochemistry, 2026)

The arrival of green transportation — Are our major cities ready with charging infrastructures? - Yingjie Liang; Hao Chen; Lelin Li; Shuang Cheng; Min Wang (Journal of Transport Geography, 2026)

A review of the mechanism, modification strategies and recent advances of piezocatalysis - Ying Cheng; Yue Cheng; Sa Li; Weichang Hao; Rui Guo (Journal of Environmental Chemical Engineering, 2026)

Chemical-free closed-loop conversion of nitrate into struvite fertilizer via exsolved high-entropy perovskite electrocatalyst - Li-Hui Yang; Yi-Heng Liu; Si-Hao Lv; Man-Ting Liao; Hui Lin; Wei Li; Cao Yang; An-Qi Wang; Hao-Yi Cheng (Journal of Environmental Chemical Engineering, 2026)

A food-derived small-molecule cocktail for serum-free expansion of bovine muscle stem cells identified via high-throughput screening - Xinpei Cheng; Yu Zheng; Hao Lu; Yuxuan Jiang; Shijie Ding; Chunbao Li; Guanghong Zhou; Renpeng Guo (Food Research International, 2026)

The impact of component interactions on fried flour products: synergistic regulation through dough mixing, resting and frying stages - Mengyue Li; Guifang Huang; Hao Cheng; David Julian McClements; Jianwei Zhao; Qing Hong; Zhenmin Liu; Zhengyu Jin; Long Chen (Food Hydrocolloids, 2026)

High-speed quantum junction photodetector enabled by oxygen-plasma interfacial capacitance modification - Hao Li; Can Yang; Yinglin Wang; Jiabao Lu; Song Yang; Xiaochen Guo; Yong Li; Zihan Wang; Yanlong Lu; Zhixiang Gui; Hancheng Zhu; Cheng Zhou; et al. (Chemical Engineering Journal, 2026)

A programmed magnetic resonance tuning probe for tumor miRNA-21 imaging and drug release monitoring - Minghui Chen; Xueqi Li; Zhen Zhang; Hao Zhang; Xingyu Chen; Jiali Wang; Kai Xu; Guohui Cheng (Chemical Engineering Journal, 2026)

Atomic-scale Cu in situ confined in ZIF-8 as a chemical-biomolecular bridge for visible-light-activated therapy of Staphylococcus aureus biofilm-associated skin infections - Xuehua Chen; Tai-Cheng Zhou; Hao Wang; Xilun Wang; Zhiguo Zhu; Changle Wen; Xiaoxiao Shi; Hanglin Li; Yang Tang; Jia Wei (Chemical Engineering Journal, 2026)

Flower-like PtCuTe nanozymes for synergistic photothermal and Fenton-like antibacterial therapy in infected wound healing - Ding Luo; Ji Cheng; Hao Zhang; Rui Liu; Hanjing Lu; Xudong Liu; Yuji Weng; Yunjun Zhang; Jianli Liu; Xiangyan Meng; Jinghua Li; Qi Lv; et al. (Chemical Engineering Journal, 2026)

Unveiling dynamic membrane functions in a high-rate anaerobic mesophilic co-digestion system treating cow manure and food waste: Performance, digestate characteristics, and microbial community - Hao-Cheng Zhang; Liguo Wan; Yule Han; Xiaochang C. Wang; Rong Chen; Yu-You Li; Bao-Shan Xing (Bioresource Technology, 2026)

Strigolactones constrain rice drought acclimation by suppressing ROS scavenging through the D53–OsWRKY31–ZFP36 module - Qianqian Li; Yi Wang; Jijun Yan; Liquan Kou; Hao Zhang; Jinhua Yang; Qingliang Hu; Yanshuo Guo; Xinwei Ban; Nan Luo; Peiyong Xin; Yanhui Jing; et al. (Molecular Plant, 2026)

Making Waves: Emerging Risks as Regulatory Mismatch Meets Automation in LLM-Agents like OpenClaw for Water Treatment and Environmental Infrastructure - Yu-Qi Wang; Boyan Xu; Hao-Lin Yang; Jia-Ji Chen; He-Wen Li; Wen-Zhe Wang; Hong-Cheng Wang (Water Research, 2026)

Ecological risk assessment of 1,4-thioxane and its remediation by a synthetic microbiome based on a sulfur transformation system: From multi-omics to water application - Xu Yang; Ai-de Peng; Yong-han Huang; Jia-hao Cheng; Hao-tian Zhong; Hai-tang Zhou; Pei-qi Liu; Xiao-hui Ji; Chen Li; Sheng-rui Zhang; Jin-long Lai; Xue-gang Luo (Water Research, 2026)

Annual energy use and economic performance of rice-based cropping systems: A three-year field study in Southwest China - Chuanhai Shu; Qingyue Cheng; Binbin Liu; Hongkun Xie; Yuanqing Shi; Mingming Hu; Hao Fu; Peng Ma; Na Li; Zhonglin Wang; Zongkui Chen; Yongjian Sun; et al. (Journal of Cleaner Production, 2026)

Quantifying interprovincial NO₂ transport over the Yangtze River Delta: Dynamics and drivers - Zhenda Sun; Zhongfeng Pan; Nan Zhang; Chongyang Li; Hao Yin; Ke Liu; Youwen Sun; Cheng Liu (Journal of Environmental Sciences, 2026)

Toxin partitioning and sxtA4 expression in Alexandrium catenella under excess nitrogen supply - Ziru Lian; Chang Xu; Lin Guo; Jingxuan Li; Hao Huang; Ren-Cheng Yu (Harmful Algae, 2026)

Low-frequency deficit irrigation in a semi-arid vineyard of Xinjiang's Manas region: Effects on grape and wine aroma composition across three vintages - Ning Shi; Meng-Bo Tian; Hao-Cheng Lu; Yi-Fan Zhao; Ming-Yu Li; Jia-Yi Deng; Chi-Fang Cheng; Shu-De Li; Zhen-Zhen Zhang; Keji Yu; Yi-Bin Lan; Fei He; et al. (Food Research International, 2026)

Orchestrating immunity and beyond: polysaccharides as multi-target regulators of inflammatory networks via gut microbiota and structure-dependent pathways - Hao Cheng; Jing Wen; Qingyao Jia; Lijun Luo; Yong Li; Xing Wang; Shiyu Yang; Xingyue Su; Yijun Zhang; Shenglan Li; Wuwen Feng; Cheng Peng (Food Research International, 2026)

Residential greenness and incident type 2 diabetes: A large prospective cohort study in China integrating evidence from 17 global cohorts - Jian-Cheng Jiang; Chuan-Jiang He; Ai-Min Xu; Lu Wang; Xiao-Qi Zhu; Bei-Bei Li; Wen Liu; Ya Qiu; Jing-Ran Xu; Min-Hui Li; Zhuo-Hao Wang; Xiao-Guang Zou; et al. (Environmental Research, 2026)

An integrated sensing, adsorption, and recovery platform using engineered Escherichia coli for mercury remediation - Mingzhu Huang; Li Kong; Yanzi Huang; Shuo Gao; Hao Cheng; Xuelan Chen (Environmental Research, 2026)

Generative diffusion model for environmental diffusion problems - Yuxun He; Bo Jiang; Yun Cheng; Xiangyu Chi; Meicheng Liao; Chenliang Tao; Peng Li; Hao Qiu; Zhen Cheng (Environmental Modelling & Software, 2026)

Study on the mechanism of synergistic adsorption of CO2 and Hg0 by Mg-MOF-74-derived modified composites based on experiment and density functional theory - Peng Cheng; Li Jia; Jia-hao Zhao; Ya-wen Wu; Yue Yu; Xiao-fang Gao; Qing Meng; Yan Jin (Chemical Engineering Journal, 2026)

Environment-responsive multi-enzymed Cu/Cu2O@NC nanorhombic nanoplatform for infected wound antimicrobial treatment - Ji Cheng; Hao Zhang; Yueting Jiang; Zuojia guo; Rui Liu; Xiantao Lin; Hanjin Lu; Yunjun zhang; Wenxuan Fan; Ding Luo; Jinghua Li (Chemical Engineering Journal, 2026)

Ultrahigh energy storage in BNBT-ST ceramics enabled by multiscale heterogeneous structures - Zhifei Zhang; Juntao Huang; Yuxin Xu; Saifei Wang; Guangyao Li; Chengchao Hu; Haihua Huang; Jigong Hao; Wei Li; Zhenxiang Cheng; Mahesh Kumar Joshi; Peng Fu (Chemical Engineering Journal, 2026)

Photocatalytic degradation of diclofenac using iron-doped hydrothermal carbonation carbon coupled with peroxydisulfate: Insights into reactive species contributions and degradation pathways via density functional theory - Chao Zhang; Yutong Zhang; Yueyao Cheng; Meifang Li; Yuanhao Peng; Hao Xu; Siwei Kang; Yuan Ouyang; Zhihang Yuan; Shan Xie; Chuansheng Chen (Bioresource Technology, 2026)

Lacticaseibacillus rhamnosus GR-1 Alleviates Escherichia coli-induced Autophagy-dependent Ferroptosis in Bovine Endometrial Epithelial Cells via FOXO1 Signaling - Xiangfu Wen; Mengsen Wang; Deyuan Song; Xiaohan Li; Meiyi Ren; Jinshang Song; Guowei Liang; Jing Chang; Ziyan Wang; Hao Li; Jia Cheng; Mingchao Liu (Probiotics and Antimicrobial Proteins, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Early Fibroblast Remodeling Associated with Lung Tissue Preservation After FLASH Irradiation - Caihui Li; Luhao Tan; Qixiang Liu; Zhihui Li; Menghua Li; Xuefeng Yang; Guofu Dong; Cheng Quan; Jie Ping; Changzhen Wang; Hao Lu (Phenomics, 2026)

Marine phycotoxins repurposed as bioresource: their antiviral potentials and molecular mechanisms in aquatic organism - Cheng Cao; Baofu Ma; Pau Loke Show; Huu Hao Ngo; Xiaozhe Fu; Ningqiu Li; Jin Zhou (Marine Life Science & Technology, 2026)

RSF-YOLOv8: a re-parameterized multi-branch feature augmentation network for polarization-guided underwater object detection - Hao Cuan; Shucheng Li; Weifeng Jing; Yiming Wang; Ruiqi Cheng; Xing Peng (Frontiers in Marine Science, 2026)
Underwater object detection techniques for marine resource exploration, underwater engineering inspection, and AUV intelligent operations face three major demands: high precision, low latency, and embeddable deployment. In natural underwater environments, complex interferences such as water scattering, wavelength-selective attenuation, illumination distortion, and target occlusion commonly exist. As a result, traditional optical imaging methods often suffer from inherent drawbacks, including image blurring, low contrast, and edge degradation. Polarization imaging can separate scattered stray light and preserve the intrinsic polarization texture of targets. Therefore, it exhibits significant advantages in highly turbid and low-light underwater scenes. However, existing lightweight detection models are not structurally adapted to the unique features of polarization images, leading to weak multi-scale modeling capacity, suppression of weak target features, and high miss rates for small targets. To address these issues, a novel underwater object detection model termed RSF-YOLOv8 is proposed based on the YOLOv8n baseline. Three core innovative modules are designed to optimize the model: 1) An EfficientRep re-parameterized multi-branch convolution module is constructed. By combining multi-scale parallel convolutions with structural reparameterization, the multi-scale feature extraction capability is enhanced without increasing inference cost, thereby adapting to the large-scale span and irregular morphology of underwater targets. 2) An EfficientSE dual-pooling channel attention module is designed. Global average pooling and max pooling are fused to replace the traditional single-pooling SE structure so that target feature channels are adaptively enhanced while redundant background channels are suppressed, improving the recognition capability for low-contrast polarized targets. 3) A FASFF4 (Four-scale Adaptive Spatial Feature Fusion) module is established. Unlike the original PAN-FPN which only performs simple lateral connections across three scales(1/32, 1/16, 1/8) and lacks fine-grained 1/4 detail preservation, our FASFF4 introduces a dedicated 1/4-scale branch and a bidirectional cross-scale interaction pathway that explicitly transmits high-level semantics downward while compensating detailed edge cues upward through an additional bottom-up path. This four-scale bidirectional design alleviates feature dilution and localization offset for very small underwater target, which are inherently prone to vanishing in conventional three-scale fusion. Systematic experiments are conducted on a self-constructed polarized underwater organism dataset(PUOD) and four public/self-constructed generalization datasets(UDD, DUO, URPC2020, BMPD). The results show that, compared with the baseline YOLOv8n, the proposed RSF-YOLOv8 achieves a precision of 0.9394(from 0.9299), an mAP@0.5 of 0.9939(from 0.9839), and a mAP@[0.5:0.95] of 0.7125(from 0.6792) on the PUOD dataset. Although the 1.02% gains in precision and mAP@0.5 appear marginal in absolute terms, they represent a relative reduction of 13.4% and 6.2% in false positives and misclassifications, respectively, given that the baseline already operates in a high-accuracy regime(>0.98). More critically, the 4.90% improvement in mAP@[0.5:0.95] reflects a substantial enhancement in strict localization accuracy, which directly translates to fewer missed small targets in real AUV operations. Ablation studies validate the effectiveness and synergistic effects of each module, while generalization experiments demonstrate strong robustness across different underwater scenarios. This research provides a high-precision and real-time detection solution for AUVs equipped with polarization cameras, achieving an inference speed of 62.3FPS and 16.0ms single-image latency on RTX4060 GPU, as well as 18.2FPS on Intel i9-13900HX CPU after structural reparameterization. With only 3.1M parameters and 8.1 GFLOPs at inference, the model provides a computationally efficient architectural foundation that is well-suited for resource-constrained underwater platforms.

A legacy pollutant deciphered by multiomics toxicology and targeted remediation by a synthetic microbial consortium: a case study of 2-chloroacetophenone from abandoned chemical weapons - Xu Yang; Ai-De Peng; Jia-Hao Cheng; Yong-Han Huang; Hao-Tian Zhong; Hai-Tang Zhou; Pei-Qi Liu; Xiao-Hui Ji; Chen Li; Sheng-Rui Zhang; Jin-Long Lai; Xue-Gang Luo; et al. (Water Research, 2026)

A risk assessment of the environmental and clinical implications of aquaculture-associated, multidrug-resistant Aeromonas veronii - Baili Zheng; Jian Qi; Lan Ma; Cuilan Hao; Xiaofeng Zheng; Yongchao Li; Yaling Cheng; Cheng Yue; Yingyu Liu (Water Research, 2026)

Integrated biological sulfidogenic process: Synergizing sulfate and elemental sulfur reduction for metal-laden wastewater treatment - Jiahua Guo; Junjie Han; Chenxin Zhang; Hao Li; Cheng Li; Shuting Chen; Yibo Wang; Yu Li; Feng Jiang (Water Research, 2026)

Nitrous oxide mitigation in biochar–pyrite-based bioretention systems via zonal microenvironment regulation - Wenlin Zhao; Cheng Cheng; Huan Xiao; Hao Zheng; Yuhao Ding; Haoyu Wang; Qiyuan Li; Hongxiang Chai (Water Research, 2026)

Retraction notice to “Size distribution and chemical composition of primary particles emitted during open biomass burning processes: Impacts on cloud condensation nuclei activation” [Sci. Total Environ. 674 (2019) 179–188] - Li Chen; Qing Li; Di Wu; Hao Sun; Yaqi Wei; Xiang Ding; Hui Chen; Tiantao Cheng; Jianmin Chen (Science of The Total Environment, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Pyrrolic-N-directed Fe single-atom seeding tunes O2 dipole moments for boosted oxygen reduction - Zheng Li; Yafeng Ma; Quzhi Song; Shuqin Li; Qiyou Wang; Hao Cheng; Zhongliang Tian; Mengran Wang; Wei Zhang; Zhao Fang; Jianhui Yan; Dong Luo (Science Bulletin, 2026)

Fungal community succession drives the decay of jujube fruit (Ziziphus jujuba Mill. cv. Jingcang 1) during ambient storage - Jian-Yu Wang; Ke-Xin Jiao; Min-Xin Mao; Cheng-Gang Li; Jian-Ping Qu; Bo Zhou; Qian Zhang; Qing Hao (Postharvest Biology and Technology, 2026)

Formation and detection of marine algal toxins and their distribution in Chinese coastal waters - Fangyuan Cheng; Junfeng Zhang; Qianqian Li; Bo Hu; Hao-Bing Yu; Shengying Li; Xingwang Zhang (Marine Environmental Research, 2026)

SlCOMT1-dependent melatonin biosynthesis is required for auxin-mediated alleviation of cadmium toxicity in tomato - Zi-Qi Pei; Cheng Ma; Peng Xing; Liang-Hao Li; Xin-Xin Mou; Tong Guo; Lu Wang; Juan Wang; Sheng Zheng; Teng-Guo Zhang (Journal of Plant Physiology, 2026)

Phytohormonal orchestration of plant phosphate starvation responses - Kai-Kai Lu; Ru-Feng Song; Yu-Pu Fan; Ling-Yu Xu; Bo-Hao Chen; Shu-Xian Li; Meng-Tian Sun; Guo-Mao Liu; Xiao-Li Huang; Lin Li; Xin-Ru Guo; Feng Ren; et al. (Journal of Plant Physiology, 2026)

Identifying driving factors of lacustrine groundwater discharge in Lake Taihu with integrated surface-subsurface numerical modeling - Hao Zhou; Yadong Shi; Yue Zou; Ya Jiang; Na Zheng; Subin Cheng; Donghao Wu; Xin Luo; Chaomeng Dai; Juntao Zheng; Zhi Li (Journal of Hydrology, 2026)

Structure-guided tuning of the SiO2/Al2O3 mass ratio enables low-temperature fiberization of red mud slags - Lei Xing; Pei-pei Du; Yue Long; Hao Liang; Ruo-cheng Liao; Li Wang (Journal of Cleaner Production, 2026)

Decolorization of synthetic dyes by Stropharia rugosoannulata producing laccases as the main ligninolytic enzyme and their application - Shuxue Zhao; Xiaohang Li; Hao Yu; Fansheng Cheng; Xianhao Cheng; Lizhong Guo; Weihuan Li; Chunhui Hu (Journal of Environmental Sciences, 2026)

Screening and identification of soybean antioxidant peptides using Fe3O4-Modified carbon fibers - Xiao-Feng Chen; Xiang-Yu Huang; Hao-Ran Liu; Li Ding; Li Wen; Xu-Feng Wang; Zhou Xu; Yun-Hui Cheng; Mao-Long Chen (Food Bioscience, 2026)

Denitrogenation of aqueous organic nitrogen by vacuum ultraviolet in tandem with chlorine - Baiyang Chen; Hao-Lin Yang; Longjie Cheng; Yuheng Chen; Xiao Li; Qiaoxia Han (Chemical Engineering Journal, 2026)

Soybean MYB transcription factors GmMYB73 and GmMYB85 regulate lipid biosynthesis through lncRNA-mediated mechanisms - Jiaxin Wang; Xingyu Guo; Yanqiu Li; Xinchao Luan; Yushan Bai; Lianjie Li; Peiwu Wang; Jian Wei; Wenge Cheng; Wenyuan Hao; Dan Yao (Theoretical and Applied Genetics, 2026)

Analysis of Arbuscular Mycorrhizal Fungal Community in Soil of Sugarcane at Different Tillage Depths - Qun-Qing Huang; Sheng Wang; Ying-Jie Nong; Kai-Mao Zhong; Yi-Cheng Su; Xiao-Juan Qin; Jin-Lian Zhang; Yi-Hao Kang; Ting-Su Chen; Shi-Yuan Zeng; Xi-Chao Deng; Ming-Guo Jiang; et al. (Sugar Tech, 2026)

Proteomic comparison of human neural cell-derived extracellular vesicles and parental cells from Alzheimer’s disease and cognitively normal individuals - Jia-Yan Xin; Jie Liu; Hao-Min Dong; Hai-Lun Yu; Zhong-Song Xiao; Jian-Ni Hu; Qiu Jiang; Yu-Peng Zhu; Lin Feng; Yun Feng; Yu-Juan Jia; Zi-Yu Yuan; et al. (Science China Life Sciences, 2026)

Interdecadal winter temperature variability driven by the East China Sea Mode: A global perspective - Keyan Fang; Hao Wu; Shuheng Lin; Jun Cheng; Jane Liu; Deliang Chen; Jinbao Li; Cesar Azorin-Molina; Zheng Zhao; Frode Stordal; Shuo Hao; Nicole Davi; et al. (Science China Earth Sciences, 2026)

Seawater mixing as a mechanism to enrich gold ore: Insights from the Ludousou gold deposit (China) - Hao-Cheng Yu; Jun Deng; Kun-Feng Qiu; A. E. Williams-Jones; Ya-Qi Huang; Lian Zhang; Lei Wang; Ke Geng; Xiao-Fei Yu; Deng-Yang He; Jia-Dong Ma; Yong-Sheng Li (Mineralium Deposita, 2026)

Egg Disease in Spodoptera litura (Fabricius) Caused by Aspergillus ochraceus and Its Metabolic Phenotype - Wen-Jie Lei; Yan Zhao; Qin-Ye Zhang; Hao-Jun Wang; Xiang-Li Dong; Jian-Yu Meng; Liu-Ti Cai; Hui-Zi Wu; Han-Cheng Wang (Current Microbiology, 2026)

The maternal gut microbiota influences myocardial maturation and diastolic function of offspring in mice - Shanshan Li; Yiqiong Zhang; Yang Li; Yuyang Lei; Hao Wu; Peining Liu; Wen Xi; Xiaozhen Zhuo; Pu Huang; Ting Yang; Ting Bai; Juanli Li; et al. (Science China Life Sciences, 2026)

Transcriptomic analysis reveals organ-specific adaptations in the gut-liver axis during diet domestication of mandarin fish (Siniperca chuatsi) - Hao-Yu Li; Zhi-Guang Hou; Yi-Huan Xu; Cheng-Bin Wu; Zun-Li Qi; Xiao-Wei Gao; Chun‑Long Zhao; Xin Zhao; Li-Han Zhang (Aquaculture International, 2026)

Enhanced dimethylsulfide emissions following eutrophication remediation in a coastal bay: biogeochemical and hydrological controls - Xiao-Ran Li; Jin-Wei Wu; Xiao-Song Zhong; Hao Qiao; Shi-Bo Yan; Feng Xu; Yu-Cheng Jiang; Rui-Te Zhang; Yu-Hao Qiu; Hong-Hai Zhang (Progress in Oceanography, 2026)

n-butanol treatment alleviates chilling injury of mango fruit by regulating membrane lipid metabolism - Hao Dong; Ping Yi; Lihong Xie; Qi Wei; Yuhan Long; Min Huang; Ting Gan; Qiuyu Cheng; Lan Zhang; Li Li; Jian Sun (Postharvest Biology and Technology, 2026)

H3K18 lactylation-regulated ATG10 is involved in the acute respiratory distress syndrome induced by acute exposure to hydrogen sulfide through activation of autophagy in lung epithelial cells - Bingyu Ling; Ping Geng; Bowen Fan; Xiaolong Wu; Yi Yang; Jiaheng Lin; Wenjie Li; Qizhan Liu; Cheng Cheng; Jinsong Zhang; Hao Wu (Journal of Hazardous Materials, 2026)

Activity identification and proteomics analysis of water-soluble proteins in cocoon coat from different silkworm varieties - Hao Tian; Wei Chen; Jiayi Li; Yuli Zhang; Tingcai Cheng; Wenjin Zhang; Chun Liu (Insect Biochemistry and Molecular Biology, 2026)

Numerical and experimental study on the soot formation in methane multi-jet flames under microgravity - Wen-Jiao Wang; Kai-Ru Jin; Zhi-Hao Zheng; Hong-Qing Shi; Du Wang; Ling-Nan Wu; Ya-Wen Liu; Longfei Li; Jiayu Sun; Yu Cheng Liu; Zhen-Yu Tian (Fuel, 2026)

Fiber influence on local and global responses of UHPC slabs under explosions: Mesoscale analysis - Ming Li; Hao Wu; Yuehua Cheng; Yan Li; Kunkun Fu (Engineering Structures, 2026)

A multi-functional passive fixation lead for diagnosis and treatment of cardiac diseases - Xuandi Deng; Yiran Hu; Puqing Yao; Chunhong Yu; Juwei Yang; Ruizeng Luo; Sijing Cheng; Hao Huang; Peng Cheng; Lei Jia; Xingyao Lv; Menghan Li; et al. (Chemical Engineering Journal, 2026)

Fe/FeF2 Mott-Schottky heterojunction with the spontaneous charge transfer boosting the bifunctional oxygen electrocatalysis performance - Nanping Deng; Jinyu Han; Hao Chi; Yewen Shui; Xinyi Li; Chengwei Liu; Gang Wang; Weimin Kang; Bowen Cheng (Chemical Engineering Journal, 2026)

The AT-HOOK MOTIF CONTAINING NUCLEAR LOCALIZED gene promotes somatic embryogenesis and polyploidy formation in Liriodendron hybrids - Yao Tang; Qi Zhao; Jinshu Li; Dingjie Yang; Lu Lu; Zhaodong Hao; Liming Yang; Tielong Cheng; Jisen Shi; Ying Chen; Jinhui Chen (Plant Cell Reports, 2026)

Independent and joint effects of ambient temperature and relative humidity on fetal distress: effect modification by air pollutants - Hua Xiao; Yi Wang; Zongli Qi; Ziwei Ye; Liping Li; Li Mao; Peng Hu; Yuefei Li; Haoyun Zhang; Yao Cheng; Hao Wang; Ping Chen; et al. (International Journal of Biometeorology, 2026)

REE source, fractionation and enrichment behavior in the Tuguanzhai-Maliping ion-adsorption REE deposit, Tengchong Block (SW China) - Zhong Tang; Congfa Bao; Tianxue Ming; Hanjie Wen; Xiaohu He; Hao Cheng; Jiaxin Liu; Zewei Pan; Liang Li; Jiasheng Wang; BeiBei Chen; Kunfeng Qiu (Acta Geochimica, 2026)

Research on Collaborative Microseismic Phase Picking for Single-Component Arrays Based on Time-Frequency Two-Dimensional Cross-Correlation - Gui-wu Chen; Yan Li; Shu-xun Zhang; Hao Wang; Shao-lei Song; Peng-Cheng Huang (Applied Geophysics, 2026)

Integrated NGS-MassARRAY Screening Reveals Hidden Wilson Disease Burden - Jia Tang; Hao Geng; Haihong Shi; Ting Yu; Jinping Qiao; Qingjiang Guo; Kun Wang; Jingjing Jiang; Qing Zhao; Na Nian; Yun Cheng; Shijing Wang; et al. (Phenomics, 2026)

Mechanism of Pre-tensioned Bolt for Strainburst Mitigation: Insights from the Regulation of Stress/Energy Fields and Fracture Pattern - Ruyi Cheng; Minghe Ju; Liyuan Yu; Yang Zou; Hao Ji; Bo Zhang; Minjie Ding; Xiaofeng Li (Rock Mechanics and Rock Engineering, 2026)

Closed-loop graphite recycling from the manufacturing scrap graphite by sulfuric acid leaching combined with low-temperature oxidation - Guoxuan Li; Chao Chen; Zibo Chen; Jiebin Zheng; Zhengwei Kang; Hao Cheng; Xinyi Li; Hailin Yu; Zhongliang Tian; Yanqing Lai (Waste Management, 2026)

Urban forest canopies are both source and sink for Pb and Hg deposition in subtropical southern China - Cheng Li; Dongqing Ji; Jin Wang; Heng Jiang; Xinyu Jiang; Cao Hao; Xiaodong Liu; Xiangdong Li; Jiong Cheng (Urban Forestry & Urban Greening, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Seven undescribed metabolites from Ganoderma lucidum-derived endophytic Talaromyces sp. GLQ04 and their anti-DLBCL (diffuse large B-cell lymphoma) activities - Shan Liu; Hao Sun; Pei-Ting Li; Pei-Shan Li; Xia Cheng; Feng Wang; Qi Luo (Phytochemistry, 2026)

Influence of ground pressure on grounding performance of deep-sea mining vehicle tracks - Junlin Zhao; Manhong Li; Hao Zheng; Yangrui Cheng; Zhou Li; Cong Ding; Andi Yu; Gen Li (Ocean Engineering, 2026)

Earliest centripetal flaking system in eastern Eurasia reveals human behavioral complexity in late Middle Pleistocene China - Yu-chao Zhao; Zhan-yang Li; Hai-wei Zhang; Xin-ya Shao; Hao-hong Cai; Ying Cui; Ya-Nan Li; Hai Cheng; Zhe Hou; Christopher J. Bae; Brian A. Stewart (Journal of Human Evolution, 2026)

Removal of Microcystis aeruginosa by Fe-doped biochar via persulfate activation: Catalytic performance and mechanistic exploration - Tiantian Li; Zhiwen Cheng; Lili Yan; Guofeng Shang; Zongdi Hao; Guoqing Shen; Pinhua Rao; Runkai Wang; Guanghui Li; Zhaoziyue Zhang; Benjiao Huo (Journal of Environmental Chemical Engineering, 2026)

Programming interfacial electron transfer at Shewanella oneidensis – Magnetic biochar hybrids for selective tetracycline–ciprofloxacin co-removal - Lei Wang; Yudong Li; Dongle Cheng; Jian Zhang; Huu Hao Ngo; Wenshan Guo; Jie Li; Huaqing Liu; Yanlong Wang; Aiyun Guo (Journal of Environmental Chemical Engineering, 2026)

Carbonate-associated fluorescent dissolved organic matter (CAFDOM): Establishing a new proxy for dissolved organic matter in ancient oceans - Wei Wang; Chao Li; Matthew S. Dodd; Hao Xu; Meng Cheng; Zihu Zhang; Chunxia Yang; Jun Hu; Haiyang Wang; Xinyang Chen; Adrian Immenhauser (Geochimica et Cosmochimica Acta, 2026)

Mg–K isotopic compositions deciphering mantle heterogeneity beneath southeast Tibet - Qiong Chen; Hao Cheng; Guo-Chun Zhao; Mei-Fu Zhou; Ping-Ping Liu; Wen-Jun Li; Min Sun (Geochimica et Cosmochimica Acta, 2026)

Multifunctional Cu2O@Ag probe for ultra-sensitive SERS detection and inhibition of Escherichia coli O157: H7 - Hao Jiang; Yu-Qing Wang; Huan Cheng; Shi-Ying Fu; Hongmei Li; Jia-Sheng Lin; Yue-Jiao Zhang; Jian-Feng Li (Food Chemistry, 2026)

Piperazine-based bis-benzoxazine-derived self-crosslinked AEMs with suppressed swelling for low-resistance electrodialysis desalination - Lan Yang; Xinrui Lu; Hao Xu; Yafei Cheng; Qiuhua Li; Haiyang Yan; Xiaocheng Lin (Desalination, 2026)

Ultrafast and selective removal of Sr2+ by a chain-structured aluminophosphate for nuclear waste remediation - Yucheng Hao; Cheng Hou; Changlin Chen; Mingyang Cao; Shihan Zhang; Xinnan Li; Guangyu Zhang; Fengshan Yu; Hongping Bian (Desalination, 2026)

Corrigendum to "Engineering atomic Mn-N4 sites in g-C3N4 for promoting the photocatalytic oxidation of glucose to glucaric acid" [Chem. Eng. J., 534 (2026) 175244] - Mingfu Li; Pingjun Zhang; Jiannan Qin; Hao Cheng; Qiang Yu; Liqun Jiang (Chemical Engineering Journal, 2026)

Pt decorated core-shell ZnS:Cu doped epoxy composites: Achieving enhanced breakdown strength and defect visualization - Zhi-Hao Xing; Ming-Xiao Zhu; Jian-Yi Xue; Jia Cheng; Guang Li; Bing Xia; Chongzi Cao; Yanbing Ji; Rui Liu (Chemical Engineering Journal, 2026)

Molecular pillar engineering of terephthalate-intercalated vanadium oxide cathodes for ultra-stable high-power aqueous zinc-ion batteries - Haoyan Cheng; Tianwen He; Junqi Liu; Yuhao Li; Bo Zhao; Hao Hu (Chemical Engineering Journal, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Synergistic enhancement of energy recovery during co-pyrolysis of excavated waste and municipal solid waste - Yunan Sun; Mingya Zhu; Hao Li; Jian Li; Junyu Tao; Zhanjun Cheng; Beibei Yan; Guanyi Chen (Biomass and Bioenergy, 2026)

Retrieval of water cloud droplet size distribution based on FY-3G PMAI data - Cheng Dai; Haifeng Xu; Qiushi Yu; Dongdong Li; Hao Chen; Jinji Ma; Xiuqing Hu; Haofei Wang; Zhengqiang Li (Atmospheric Research, 2026)

Engineering Ru–Co sites for promoted hydrogen spillover in ammonia synthesis - Shengxuan Luo; Guorun Dai; Annan Hu; Jun Cheng; Yuxiang Mao; Hao Li; Zhefeng Li; Weixin Liu; Rongxin Xia (Waste Disposal & Sustainable Energy, 2026)

Polyprenylated acylphloroglucinols from Hypericum monogynum and their reversal of multidrug resistance in MCF-7/ADR cells - Yan-Rong Zeng; Peng Zhao; Jing-Yi Yin; Hong-Jin Ban; Zhan Feng; Yu-Xiang Li; Min Yang; Jing Tan; Cheng-Jian Tan; Jue Yang; Xiao-Jiang Hao; Chun-Mao Yuan (Molecular Diversity, 2026)

Dynamic water delay time estimation using dispatch data for improved inflow forecasting in cascade hydropower reservoirs - Xiong Cheng; Junwen Yang; Bin Luo; Miriam R. Aczel; Wenwu Li; Hao Zhong; Xianshan Li; Shumian Miao (Journal of Hydrology, 2026)

Integrated process analysis of hydrogen-carbon complementarity between the coke dust high-temperature gasification and coke oven gas to methanol - Hao Cheng; Yuheng Chen; Tao Wang; Zhongren Ba; Jiantao Zhao; Yitian Fang; Chunyu Li (Journal of Cleaner Production, 2026)

Tracking high-field-strength-element enrichment pathways in alkaline granites: Insights from potassium and barium isotopes - Hao-Cheng Yu; Zheng-Yu Long; A.E. Williams-Jones; Ralf Halama; Frédéric Moynier; Shan-Shan Li; Ming-Qian Wu; Hao-Ran Duan; Jia-Dong Ma; Nan Ju; Ze-Zhou Wang; Kun-Feng Qiu (Geochimica et Cosmochimica Acta, 2026)

Elucidating the pyrolytic mechanisms of clean and safe gas generator 5-amino-1H-tetrazole/SiO2: A comprehensive kinetic and theoretical investigation - Si-Yuan Zhou; Xuan Li; Yuan-Hui Liu; Hao-Tian Zhou; Peng-Cheng Xi; Dan Zhang; Mi Li; Li-Feng Xie (Fuel, 2026)

Nanostructured electrospun nitrocellulose: Stabilization mechanisms and degradation kinetics of organic stabilizers - Wen-Jie Xu; Xue-Ning Cheng; Zhong-Xuan Han; Zhan-Jun Yang; Shu-Na Zhao; Hao Liu; Mi Li; Lin Jiang (Fuel, 2026)

A high-performance LaSA-Co MAs catalyst derived implantable flexible electrochemical sensor for endogenous dopamine detection - Binqi He; Jiawei Li; Qianzuo Liu; Xinyue Xiang; Sifan Sun; Haoran Yang; Guosheng Cheng; Maiyong Zhu; Ying Hao; Ting Zhang; Tie Li (Chemical Engineering Journal, 2026)

A glucose-triggered self-reinforcing hydrogel based on carboxymethyl chitosan/oxidized hyaluronic acid/borax for delivering nano-selenium and dynamic diabetic wound management - Wei-Xiong Li; Shanshan Li; Hao Cheng; Yu Chen; Han-Jian Hu; Shipeng Tang; Jian Sun; Xiao-Ping Liao; Gang-Biao Jiang; Hongyan Zhang (Carbohydrate Polymers, 2026)

Protein foundation models: a comprehensive survey - Hao Xu; Liangjie Li; Sangyu Pan; Peng Cheng; Yuxiang Wang; Zhen Rong; Feng Liu; Xingxu Huang; Shengqi Wang; Wenjie Shu (Science China Life Sciences, 2026)

Isoliquiritigenin combined with gemcitabine inhibited lung cancer by suppressing JAK2/STAT3 signaling via lncRNA-p21/miRNA-4534 axis - Chenyue Xu; Cancan Gong; Cheng Wang; Meiping Xie; Mianhua Wu; Dengfeng Ge; Hao Ren; Bin Zhang; Zequn Jiang; Wenting Li (Journal of Natural Medicines, 2026)

Herbiconiux dendrobii sp. nov., a Novel Bacterium Isolated from Dendrobium devonianum Sawdust Substrate - Hao Liang; Fang Zhao; Hong-Bo Zha; Zhang-Gui Ding; Le-Le Li; Jiang-Yuan Zhao; Zhi-Ran Zhao; Min Zheng; Jian-Sheng Cheng; Hui-Cheng Deng; Shu-Kun Tang; Ming-Gang Li (Current Microbiology, 2026)

Biosynthesis of active small molecule prenylsalidroside a and its anti-inflammatory activity - Jia-Hao Xue; Hua-Jin Yu; Long-Jun Li; Gui-Hu Lu; Pei-Shan Li; Xia Cheng; Qi Luo; Wei Wu; Zhong-Sheng Bi (Natural Product Research, 2026)

Imiquimod enhances anti-tumor effects of CD47 targeting in oral squamous cell carcinoma - Hongzhi He; Yu Hao; Jing Chen; Biao Ren; Xin Zheng; Xu Cao; Bolei Li; Lei Cheng (Inflammation Research, 2026)

Beyond crown volume: UAV-LiDAR-derived foliated crown volume (FCV) enhances coniferous tree attribute estimation - Shoumin Cheng; Yuanshuo Hao; Jingzhe Liu; Xin Liu; Lihu Dong; Yinghui Zhao; Fengri Li (Computers and Electronics in Agriculture, 2026)

Quantifying the counteracting impacts of climate change on large-scale pavement infrastructure serviceability - Jin Li; Wentao He; He Zhang; Hao Shi; Huailei Cheng; Lijun Sun (Transportation Research Part D: Transport and Environment, 2026)

Aldometanib attenuates OGD/R-induced cardiomyocyte injury via mitigation of mitochondrial dysfunction - Mian Xie; Jiajia Hao; Chen Chao; Xi Chen; Qiuling Chen; Yao-wang Lin; Jiang-hua Li; Qi-yun Liu; Cheng Liu (Tissue and Cell, 2026)

Strongly spatial-confined self-assembled monolayers for high-performance perovskite photovoltaics - Dongyang Li; Qiming Yin; Zhiwei Ren; Guihua Zhang; Jie Li; Qianyi Li; Yu Han; Sibo Li; Lihan Pang; Hao Xia; Guang Yang; Longbin Qiu; et al. (Science Bulletin, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Sparteine-type alkaloids with anti-tomato spotted wilt virus from the seeds of Lupinus angustifolius L. - Jian-Guo Tan; Cheng-Feng Liu; Li Wang; Xing-Ya Wu; Li-Hua Zhao; Xiao-Jiang Hao; Zhan-Xing Hu (Pesticide Biochemistry and Physiology, 2026)

Ailancoumaquinone A and ailancoumarins M-T, undescribed terpenylated coumarins from Ailanthus altissima and their anti-inflammatory activity - Da-Le Guo; Li Huang; Hui-Min Zhang; Yu-Ting Mu; Hao-Ran Lei; Li-Lian Zhao; Su Hu; Yun-Jie Hu; Cong-Cong Li; Meng-Dan Liu; Yu-Cheng Gu; Guan-Kui Yang; et al. (Phytochemistry, 2026)

Early Cretaceous radiolarian assemblages in mélange of Yarlung-Tsangpo suture zone in the Saga area, southern Xizang - Zhi-Hao He; Xin Li; Ya-Lin Li; Atsushi Matsuoka; Hui Luo; Xiao-Hui Cui; Jian-Bo Cheng (Palaeoworld, 2026)

Opisoma menchikoffi Dubar, 1948: New occurrences from the Lower Jurassic of the High Atlas, Morocco and Tethyan Himalaya, southern Xizang (Tibet), China - Fu-Lin Li; Kai Ye; Xin Rao; Zhong Han; Cheng-Gang Wang; Xiong-Wei Zeng; Long Wang; Hao Liu; Zong-Xin Wang; Fa-Fu Wu; Kun Liang; Wen-Kun Qie (Palaeoworld, 2026)

Functional divergence of two ethylene receptor subfamilies in calcium permeability - Chenliang Pan; Junyuan Cheng; Zining Lin; Dongdong Hao; Zhina Xiao; Yuhang Ming; Peng You; Hongtao Yu; Wei Yan; Wen Song; Li Liu; Hongwei Guo (Molecular Plant, 2026)

Deciphering the molecular pathways underlying di(2-ethylhexyl) phthalate degradation and metabolic adaptation in Alexandrium pacificum - Hong-Jia Huang; Dan Huang; Jiang-Bing Qiu; Si-Ying Li; Qing Han; Cai-Qin Cheng; Hao-Yun Zhang; Zong-Di Wang; Yi-Tong Huang; Li-Gong Zou; Ce-Hui Mo; Hong-Ye Li; et al. (Journal of Hazardous Materials, 2026)

Multidimensional evidence of the positive effects of land use on plant biodiversity in the Hengduan Mountains - Yu Huang; Peng Luo; Honglin Li; Hao Yang; Wenwen Xie; Chuan Luo; Honghong Jia; Yue Cheng; Ming Ni; Zhixiang Sun; Zhouyu Luo; Jiang He (Journal of Environmental Management, 2026)

Removal performance and mechanisms of microplastics by superhydrophobic medium - Zhang Tingting; Cheng Wenqing; Wang Xiaojuan; Yan Yaping; Song Xichen; Zhou Jianqiang; Liu Xiuyun; Gao Suxia; Li Hao; Liu Jianlin; Cao Lianbao; Li Wei; et al. (Journal of Environmental Chemical Engineering, 2026)

Effect of atmosphere on the ash fusion temperature and precipitation kinetic of metallic iron of iron-containing coal ash - Hao Cheng; Guoqiang Cao; Zhongren Ba; Donghai Hu; Yongbin Wang; Chunyu Li; Jiantao Zhao; Yitian Fang (Fuel, 2026)

Sequential double crosslinking enables pea protein-κ-carrageenan emulsion gel with enhanced mechanical strength: Mechanism and structure-dependent properties - Xiaojiao Li; Hao Cheng; Li Liang (Food Hydrocolloids, 2026)

Engineering atomic MnN4 sites in g-C3N4 for promoting the photocatalytic oxidation of glucose to glucaric acid - Mingfu Li; Pingjun Zhang; Jiannan Qin; Hao Cheng; Qian Yu; Liqun Jiang (Chemical Engineering Journal, 2026)

Combined hydrothermal carbonization and pelletization for high-quality biofuel production - Geng Li; Hao Song; Wei Cheng; Jianfeng Chen; Hao Jiang; Jing'ai Shao; Haiping Yang; Hanping Chen (Biomass and Bioenergy, 2026)

Cell type-specific contribution of low-density lipoprotein receptor to atherosclerosis - Wei-Hui Li; Yu-Liang Zhang; Ya-Fen Zhang; Zhenyang Yu; Liang Chen; Hao-Yu Fang; Liang Cheng; Bao-Liang Song; Jie Luo (Science China Life Sciences, 2026)

Copper-loaded halloysite nanotube-coated chitosan sutures: Enhanced antibacterial activity, mechanical strength, and reduced burst-release toxicity - Renzheng Guan; Xinyan Hao; Chuyang Chen; Guangqi Cheng; Qianchen Huang; Shuang Wang; Fang Wang; Jiwei Li; Aihua Cui; Shaohua Zhang (Applied Clay Science, 2026)

Pyroptosis as a double-edged sword in colorectal cancer: Molecular mechanisms and therapeutic opportunities - Han-Xi Zhang; Wen-Jing Xu; Yi-Xin Jiang; Lu Li; Bai-Yu Chen; Meng-Yao Cheng; Meng-Yuan Hao; Hang-Shen Han; Hong-Jie Li; Yan-Ge Li; Dong-Dong Wu (Apoptosis, 2026)

Discovery of notoprenylate F from Notopterygium incisum (Qianghuo) as a PPARγ agonist with potent anti-inflammatory activity through HTS2 - Meng-Dan Liu; Li-Jun Huang; Hao-Ran Lei; Yong-Jiang Wang; Yun-Jie Hu; Xue-Yan Huo; Cong-Cong Li; Li Huang; Li-Lian Zhao; Ming-Zhi Zhang; Yu-Cheng Gu; Melody Shyy; et al. (Marine Life Science & Technology, 2026)

Microenvironment-directed chondrogenesis of adipose-derived mesenchymal stem cells in hyaline, elastic, and fibrocartilage in vivo - Yi Han; Hao Ma; Jingyi Chen; Liuhanghang Cheng; Ke Li; Baolin Zhang; Peiru Min (Cell and Tissue Banking, 2026)

Mechanisms of phosphorus release from coastal sediments driven by organic matter enrichment at high nitrogen concentrations - Chun-Pu Zhao; An-Hao Wang; Ying Zeng; Wen-Hao Yin; Cheng Luo; Shi-Xia Liu; Miao Liu; Hai-Jun Wang; Xiao-Wen Li; Ji-Lin Xu; Shuo-Nan Ma (Marine Pollution Bulletin, 2026)

Physicochemical strategies for antibiotic removal in aquaculture wastewater: Mechanistic insights, technological challenges, and sustainable development pathways - Tai-Yue Wang; Yan-Ping Qiao; Kai-Jun Yue; Ming Cheng; Li-Ting Hao; Nan Zhang; Ran-Bin Liu; Chen Shi (Aquaculture, 2026)

The role of artificial intelligence in advancing population-based cancer registration - Shuai Ding; Mingyuan Liu; Hao Wang; Cheng Song; Luyue Zhao; Zhihao Yang; Yue Wang; Yifan Wang; Haitao Cui; Zihao Liu; Dongrun Liu; Tomohiro Matsuda; et al. (Science Bulletin, 2026)

Task-path integrated planning with 3D region decomposition for underwater coverage in heterogeneous AUVs - Shaomin Meng; Liang Cheng; Hao Liu; Jianbo Wu; Jiangxiong Li; Yinglin Ke (Ocean Engineering, 2026)

BR-C promotes lipid synthesis through the nuclear receptor HR96 during metamorphosis in insects - Xing Zhang; Peixin Li; Xuechuan He; Dongqin Yuan; Hao Li; Qiaoling Sun; Daojun Cheng; Wenliang Qian (Journal of Insect Physiology, 2026)

Exposure to 2-chlorohydroquinone induces systemic vascular disorders and increases the risk of cerebral hemorrhage in zebrafish larvae - Jian Li; Hao Cheng; Yulian Li; Shanshan Zhu; Wenyan Liu; Baochun Wang; Xiaowen Shi (Journal of Hazardous Materials, 2026)

Fair scheduling efficiency benchmarking for sustainability in heterogeneous hydropower systems - Xiong Cheng; Xiaotao Zeng; Qingshe Meng; Mian Wang; Lei Wang; Miriam R. Aczel; Wenwu Li; Xianshan Li; Hao Zhong (Journal of Cleaner Production, 2026)

The research of a novelty bio-based flame retardant derived from the synthetic combination of alkaline-extracted polymer substances from wastewater sludge with phytic acid - Congcong Li; Ming Cheng; Ruiqin Chen; Ruofei Wang; Xiangyang Wang; Liang Zhao; Xiaodi Hao; Chen Shi; Wei Zhang (Journal of Environmental Management, 2026)

Calcium mediated modulation of Maillard reaction kinetics and product formation in model dairy systems: Implications for heat-processed calcium-fortified foods - Shiqi Hao; Yi Li; Yongqiang Cheng; Ning Tang (International Dairy Journal, 2026)

Study on temperature/oxygen dependence of ammonia-alcohol laminar premixed flame characteristics and N2O generation by highspeed photography and laser Raman spectroscopy - Changyou Yu; Degang Li; Wanchen Sun; Hao Zhang; Peng Cheng; Liang Guo; Yuying Yan; Miao Yang; Yanan Guo; Xiaotian Wang; Yanbin Shi; Changcheng Liu (Fuel, 2026)

Dynamic light exposure from afternoon shading reveals aromatic plasticity in grapes and wines from a semi-arid region - Meng-Bo Tian; Ning Shi; Hao-Cheng Lu; Ming-Yu Li; Jia-Yan Wei; Jia-Yi Deng; Chi-Fang Cheng; Shu-De Li; Fei He; Yi-Bin Lan; Chang-Qing Duan; Keji Yu; et al. (Food Chemistry, 2026)

Effects of wheat starch and gluten protein interaction on fried flour products during processing - Mengyue Li; Guifang Huang; Hao Cheng; David Julian McClements; Jianwei Zhao; Yun Ma; Zhengyu Jin; Long Chen (Food Hydrocolloids, 2026)

Optimized one-step pyrolysis synthesis of zinc-modified sludge biochar for enhanced perfluorooctane sulfonate removal from water - Muzi Li; Ranbin Liu; Xiaodi Hao; Dongye Zhao; Xi Cheng; Jian Pan; Tianyuan Xu; Shuting Tian; Yangmo Zhu (Environmental Research, 2026)

Percussion-based method for detecting wall tie presence in masonry walls using deep learning technique - Haosheng Zhou; Cheng Yuan; Jun Li; Hong Hao; Wensu Chen (Engineering Structures, 2026)

Molten salt upcycling of waste PET into high-performance lithium-ion battery anodes - Hao Zhang; Junjie Jiang; Mengge Xing; Liangyuan Cheng; Qi Zhang; Shidong Li; Yihan Qian; Xiong Qian; Chi Sun Poon; Jiashen Meng (Chemical Engineering Journal, 2026)

Promoting the ionic conductivity and self-healing ability of micro-Si anode via a versatile crosslinker of Al(H2PO4)3 - Yang-Ning You; Shu-Hao Guo; Tao Li; Yu-Jun Bai; Xi-Cheng Ma (Chemical Engineering Journal, 2026)

Synergistic co-preintercalation of nickel and aluminum ions into vanadium oxide hydrate as positive electrode material in ultrahigh-rate and high-capacity aqueous zinc-ion batteries - Hung-Lin Chen; Tsung-Yi Chen; En-Hao Li; Yen-Lin Chen; Wen-Hsuan Lu; Hsu-Chen Cheng; Shu-Yu Chen; Jue-Hua Pan; Hsiang-Jung Chen; Syuan-Cen Lin; Ruey-An Doong; Sanna Gull; et al. (Chemical Engineering Journal, 2026)

Naringin-loaded metal-organic framework biomimetic hydrogel system mitigates wear particle-induced periprosthetic osteolysis by suppressing aseptic inflammation and osteoblast apoptosis - Chenhao Qiu; Zhenjia Che; Hao Cheng; Huabin Liu; Yuhao Zhang; Jingtao Wu; Chen Li; Jianyou Li; Xiongfeng Li; Xiao Sheng; Hongliang Gao (Chemical Engineering Journal, 2026)

Fire emissions modulate wildfire spread through aerosol-meteorology feedbacks: Insights from a novel WRF-Chem/Fire coupled model - Zhonghua He; Jie Luo; Congcong Li; Gaofeng Fan; Bin Xu; Lingxiang Wang; Zhao-Cheng Zeng; Dongmei Huang; Yuping Sun; Hao He (Atmospheric Environment, 2026)

Genome-wide characterization of soybean alcohol dehydrogenase (ADH) genes identifies GmADH13 as a positive regulator of the salt stress response - Sihui Wang; Zhiyuan Xu; Peng Cheng; Jun Yang; Qiang Hao; Jinfang Wang; Ziqian Cheng; Lingshi Xia; Zhenbang Hu; Xin Li; Anyu Su (Theoretical and Applied Genetics, 2026)

Visualizing application of RUBY-MAT system in maize genetic transformation and gene expression pattern detection - Tengfei Jia; Shuai Zhao; Xiangyu Zhang; Yingxue Li; Kuan Cheng; Xuehui Qian; Mingli Song; Wenjing Ge; Qian Liu; Haoyue Xu; Fashuai Li; Jinhua Hu; et al. (Plant Cell Reports, 2026)

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

Breaking the antimicrobial resistance dilemma: marine natural products, a treasure trove for the development of new anti-Staphylococcus aureus drugs - Peng-Jie Li; Liu-Xia Lv; Xi-Zhen Cao; Jian-Yu Liu; Ji-Xiu Gao; Hao-Ran Li; Gulab Said; Dan Chen; Bo Yao; Xin Liu; Mei-Yan Wei; Xiao-Ping Yang; et al. (Marine Life Science & Technology, 2026)
Antimicrobial resistance (AMR) affects multiple fields, including medicine, pharmacy, food safety, and animal husbandry, and poses a major threat to public health and economic development. Staphylococcus aureus has emerged as one of the most critical bacterial pathogens due to its widespread prevalence and significant genetic plasticity. This review outlines currently approved small-molecule drugs for clinical use and their mechanisms in controlling bacterial infections and antimicrobial resistance, highlighting the development of novel agents as an effective strategy to combat AMR. Special emphasis is placed on the antibacterial activity of marine-derived natural products (MNPs) against S. aureus , and a systematic analysis is presented for the first time on the structures, origins, activities, and structure–activity relationships of 1,192 compounds reported in 468 publications from 1977 to 2025. Among these, 36 MNPs exhibited significant activity against both methicillin-sensitive S. aureus and methicillin-resistant S. aureus (MIC ≤ 1 µg/mL). Macrolides and peptides represented the most prevalent structural classes, with compounds displaying potent activity accounting for 24% and 27% of the total active compounds, respectively. Further drug-likeness analysis shows that MNPs have promising therapeutic potential. Among the 160 highly active MNPs, over 80% have suitable lipid-water partition coefficients, and 41% fully meet Lipinski's Rule of Five. Structural analysis reveals tetrahydrofuran, tetrahydropyran, and sugar units as the most common motifs, present in 20, 16, and 14 compounds, respectively. Technologies and strategies to accelerate the development of marine-derived antibacterial drugs are also proposed. This will serve stakeholders across diverse sectors by supporting cross-sectoral coordination to address AMR.

Microseismic source localization in tunnels under seepage conditions: an optimized approach using NFBG sensors and the GWO-SA hybrid algorithm - Qinliang Sun; Shuai Cheng; Liping Li; Hao Wang; Xiaoyu Liu; Song Zhao (Tunnelling and Underground Space Technology, 2026)

Corrigendum to “Cattle manure hydrochar posed a higher efficiency in elevating tomato productivity and decreasing greenhouse gas emissions than plant straw hydrochar in a coastal soil” [Sci. Total Environ. 912 (2024), 168749] - Xiao Wang; Qingxian Kong; Yadong Cheng; Hao Zheng; Xueyang Yu; Yue Quan; Xiangwei You; Yiqiang Li (Science of The Total Environment, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Anti-inflammatory constituents from Murraya paniculata var. omphalocarpa - Kun-Ching Cheng; Chia-Hung Wu; Hao-Ze Li; Tsong-Long Hwang; Ping-Chung Kuo; Tian-Shung Wu (Phytochemistry Letters, 2026)

Two unprecedented 2-(2-phenylethyl)chromone dimers from the Cambodian agarwood of Aquilaria crassna - Yan Huang; Hao Wang; Wen-Li Mei; Hui-Qin Chen; Fei Wu; Yan-Mei Wei; Wen-Ming Cheng; Hao-Fu Dai (Phytochemistry Letters, 2026)

Suspensaditerpenes A–Q, anti-inflammatory labdane and nor-labdane diterpenoids from the seeds of Forsythia suspensa - Hui-Ying Li; Meng-Yu Bao; Hao-Ming Xiong; Can-Can Wang; Li-Ping Bai; Wei Zhang; Cheng-Yu Chen; Zhi-Hong Jiang; Guo-Yuan Zhu (Phytochemistry, 2026)

Species delimitation within a taxonomically complex group: An example from the genus Apodemus (Rodentia: Muridae) - Xuan Pan; Buqing Peng; Xuming Wang; Zhongzheng Chen; Hao Cheng; Rui Liao; Chia-Lung Huang; Jiatang Li; Shaoying Liu (Molecular Phylogenetics and Evolution, 2026)

A multi-processes phase-field model for CO2 phase change fracturing - ZiHan Zhang; Hao Yu; Bo Li; Wei Cheng; JiaPing Tao; SiWei Meng; He Liu; HengAn Wu (International Journal of Rock Mechanics and Mining Sciences, 2026)

Self-igniting flame of high-pressure methane-hydrogen mixture released into the air - Hao Qi; Zhenmin Luo; Shangyong Zhou; Tao Wang; Bin Su; Ruikang Li; Fangming Cheng (Fuel, 2026)

Study on the influence mechanism of lead carbonate salt compounds on the combustion behaviors of 5AT/Sr(NO3)2 solid propellant - Yuan-Hui Liu; Jiu Chen; Zhan-Jun Yang; Guang-Ling Chen; Peng-Cheng Xi; Hao-Tian Zhou; Mi Li; Li-Feng Xie; Dan Zhang (Fuel, 2026)

Multifunctional electrospun nanofiber films towards efficient deodorization and preservation of crayfish meat (Procambarus clarkii) via a triple-synergistic strategy - Cheng Wang; ZiHan Wang; MengHuan Liu; Ning Jiang; Jia Kan; LiFang Liu; MingZhu Li; ZeFeng Yue; Hao Yu (Food Chemistry, 2026)

Unraveling novel pancreatic lipase and cholesterol esterase inhibitory peptides in Oryza Sativa L. and their mechanism by peptidomics, molecular dynamics simulations, and cell study - Liuyi Wei; Taoying Wu; Hao Wu; Li Wen; Bo Cui; Yunhui Cheng (Food Bioscience, 2026)

Toward ceramifiable thermal barriers: A multiscale organic-inorganic aerogel coating with integrated fireproofing and insulation - Yuanlong Xiang; Longlong Li; Yueyue Xiao; Zhongxin Zhang; Hui Yang; Hao Wu; Heping Zhang; Xudong Cheng; Yuelei Pan (Chemical Engineering Journal, 2026)

Unveiling Mo doping effects in hydrated vanadium oxide cathodes for high-energy zinc-ion batteries: Evidence from operando synchrotron X-ray and DFT analysis - Sanna Gull; Hsu-Chen Cheng; En-Hao Li; Tsung-Yi Chen; Chung-Sheng Ni; Wan-Ju Yu; Hao-Hsiang Chang; Ai-Yin Wang; Ruey-An Doong; Chin-Lung Kuo; Yu-Chun Chuang; Bo-Hao Chen; et al. (Chemical Engineering Journal, 2026)

Lattice anchoring via Ni doping empowers a robust H2TiO3 adsorbent for lithium extraction in strongly alkaline solutions - Xinyi Li; Hao Cheng; Guoxuan Li; Zibo Chen; Hailin Yu; Jiebin Zheng; Zhengwei Kang; Zhongliang Tian (Chemical Engineering Journal, 2026)

Microbial mechanisms of arbuscular mycorrhizal fungi in mitigating nitrous oxide emissions via regulating nitrogen metabolism in constructed wetlands - Xiang-Long He; Liang-Cheng Lin; Yi-Hao Li; Yu-Quan Zhong; Hao Xu; Jing-Wen Li; Can Liu; Jun-Feng Wang (Chemical Engineering Journal, 2026)

Hydroxybutyl chitosan-based thermosensitive hydrogel enhanced osteoporotic bone regeneration through sustained release of alendronate and BMP-2 - Mingyuan Lei; Haibing Liu; Qiang Zhong; Libo Zhao; Jingwen Liu; Huaming Mai; Yuheng Zhang; Hongyu Wang; Yourong Chen; Rong Chen; Yixin Xu; Hao Li; et al. (Carbohydrate Polymers, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

In-situ sulfur isotope and microscopic analyses reveal multiple pyrite genesis mechanisms in the early Ediacaran Doushantuo Formation, South China - Shiqi Cheng; Lianjun Feng; Guoqiang Tang; Yan Liu; Hao Qiu; Qiuli Li; Xuelei Chu; Xingliang Zhang; Jinhua Li (Chemical Geology, 2026)

An integrated engineered microbial system for copper biosorption, real-time monitoring, and magnetic recovery in water remediation - Mingzhu Huang; Yanzi Huang; Xindong Yang; Wenxin Liu; Li Kong; Shuo Gao; Hao Cheng; Xuelan Chen (Bioresource Technology, 2026)

CSSL-based GWAS identifies SNPs and candidate genes associated with Verticillium wilt resistance in cotton - Youzhong Li; Xiaohui Jiang; Hongyu Cao; Xinyu Zhang; Zhongxu Lin; Qian-Hao Zhu; Yanjun Li; Fei Xue; Shuaishuai Cheng; Feng Liu; Jie Sun (Theoretical and Applied Genetics, 2026)

Integrated analysis identifies conserved transcription factors TCF12, E2F1, and TEAD4 with diagnostic and therapeutic value in osteoarthritis subchondral bone - Jingyang Cheng; Rulong Cai; Wei Lu; Zhilin Zhang; Hao Liang; Hao Chen; Hui Zheng; Jianli Fang; Youhui Liu; Runguang Li; Weidong Chen; Hang Fang; et al. (Genes & Genomics, 2026)

Impacts of mat and pile foundations on floor response spectra of SMR structures considering soil–structure interaction - Bo Li; Hao Liu; Cheng Peng (Annals of Nuclear Energy, 2026)

Carbon tax, renewable portfolio Standards, or both? Evaluating policy effectiveness in promoting renewable energy and reducing emissions - Dandan Wu; Hao Ding; Yang Cheng; Hongyan Jenny Li; Wei Wang; Qi Sun (Environment, Development and Sustainability, 2026)
The transition to a low-carbon economy is a critical global challenge. However, the relative effectiveness of renewable portfolio standards (RPS) and carbon tax policies, particularly their potential synergistic effects, remains insufficiently understood. Clarifying this relationship is essential for designing effective policies that enhance renewable energy investment and reduce carbon emissions. We develop an optimization framework in which a monopolistic electricity supplier in China invests in a hybrid energy system of conventional and renewable power. We compare profit-maximizing strategies under four policy scenarios: no policy, a carbon tax, an RPS, and a mixed policy (carbon tax + RPS). The analysis examines how these policies shape production and pricing decisions, investment, emissions, consumer surplus, and social welfare. Three main findings emerge. First, both carbon tax and RPS policies significantly encourage renewable energy investment and reduce carbon emissions. Second, mixed policies consistently outperform single policies, demonstrating the highest potential for renewable energy development and carbon emission reduction. Third, social welfare effects under mixed policies vary depending on the carbon tax and renewable energy quota level, with the highest social welfare achieved under low and medium quotas. Importantly, renewable intermittency does not alter the relative ranking of policies, though consumer environmental awareness shifts investment thresholds. Based on these findings, three recommendations emerge: integrating carbon tax with RPS accelerates renewable deployment, phased emission reduction balances neutrality targets with electricity demand, and incentives linking green electricity with consumer awareness strengthen adoption. These results provide actionable policy guidance for China and offer broader insights for economies pursuing a sustainable low-carbon transition.

Microbial degradation of short-chain chlorinated paraffins in marine environment: bacterial community responses, functional genes, transformation products, and metabolic mechanisms - Lina Lyu; Li Zhang; Cheng Yang; Yanqun Li; Hao Yin; Lin Wang; Zhimao Mai; Si Zhang (Water Research, 2026)

Geniposide activates the NLRP3 inflammasome pathway to induce nephrotoxicity by regulating FXR/PERK/TXNIP pathways - Shenghui Cheng; Baoyue Liu; Zhinan Jin; Mingzhu Shi; Xuliang Hao; Huifang Li (Toxicon, 2026)

Overexpression of peroxiredoxin 6 in bone marrow-derived mesenchymal stem cells amplifies their in vivo effect on bronchopulmonary dysplasia by increasing mesencephalic astrocyte-derived neurotrophic factor secretion - Huanqing Song; Qingfei Hao; Jingjing Li; Yuanyuan Liu; Zhifang Huo; Ranran Si; Xiaoxia Feng; Chuan Zhou; Xiuyong Cheng (Toxicology and Applied Pharmacology, 2026)

Long-term air pollution exposure and cognitive impairment risk in Chinese middle-aged and older adults - Shengqiang Xie; Shichao Su; Wenxuan Li; Yanteng Li; Fangbin Hao; Gang Cheng; Jianning Zhang (NeuroToxicology, 2026)

A “six-point S-shaped” sampling strategy based on micro-Raman spectroscopy enabling the rapid and accurate detection of small-sized microplastics in soil - Huibing Hu; Liyuan Qiang; Song Wei; Jinping Cheng; Hao Pan; Zhihang Sun; Qiang Li; Ruoyu Zhang (Journal of Hazardous Materials, 2026)

Acid and alkali jointly promote the co-doping of N, B and O atoms in wheat straw derived carbon materials for high-performance symmetrical supercapacitors - Xiaoxue Liu; Qi Gao; Xiaoyang Cheng; Lingyan Li; Lihua Zhang; Hao Wu; Lingjuan Zhang; Jinfeng Zheng; Jingwei Li; Haojie Gao (Fuel, 2026)

Emerging roles of lactic acid bacteria in health management: Insights from fermented foods to microbiota - Xuan Shi; Yiping Li; Yi Cheng; Weichi Liu; Zelong Li; Hao Jin; Lai-yu Kwok; Zhihong Sun (Food Bioscience, 2026)

Simultaneous removal of nitrogen and manganese via autotrophic denitrification driven by iron-carbon micro-electrolysis in an upflow anaerobic sludge blanket (UASB) reactor - Hao-Nan Xiao; Jun-Cheng Han; Tong Cai; Qian-Dong Qin; Bing-Bing Li; Hou-Yun Yang; Kan Wang (Environmental Research, 2026)

Effect of freeze-thaw cycles on nitrogen retention in an alpine topsoil amended with peanut shell hydrochar - Yuxi Wu; Jiawen Zhang; Yadi Ai; Weici Quan; Yiwei Gong; Kaiming Yang; Jin Gao; Lu Li; Caiwei Hao; Wenbo Li; Wenjie Ai; Kai Yang; et al. (Environmental Research, 2026)

Facile molten salt synthesis of Co@N-C catalysts enables highly efficient HMF-to-FDCA conversion under mild conditions - Hao-Yue Ma; Jun-Fei Gu; Xing-Chuan Li; Zhan Chen; Qi-Yu Fu; Francis Verpoort; Wen-Jie Mo; Zheng Liu; Cheng Chen; Soon Hyeok Hong; Zongkui Kou (Chemical Engineering Journal, 2026)

Direct/indirect strategies on engineering extracellular electron transfer of anode electrodes in microbial electrolysis for hydrogen production and pollutants removal: A review - Seyed Masoud Parsa; Huu Hao Ngo; Bing-Jie Ni; Xinbo Zhang; Ying Liu; Li Luo; Hui Cheng; Wenshan Guo (Chemical Engineering Journal, 2026)

Nanoscale steric-engineering enables synergistic ion confinement and transport for large-strain electrochemical actuation - Yang Li; Hao Li; Cheng Yang; Zheng Zhang; Bo Zhao; Yueting Pu; Zhixiang Guo; Xiaoyan Li; Bonan Hao; Haoran Li; Fangju Tao; Shuangyi Li; et al. (Chemical Engineering Journal, 2026)

Machine learning-assisted sensor array based on enhanced dual enzyme-like activities of Fe SAzymes modulated via Pluronic surfactant for multi-category perfluoroalkyl intelligent recognition and quantification - Wen-Cai Jiang; Xiao-Mei Li; Jia-Hao Cheng; Li-Yao Xu; Ri-Za He; Gui-Lin Zou; Zhi-Bo Hou; Yan Zhao; Guo-Qi Zhang (Chemical Engineering Journal, 2026)

Chitosan‑selenium nanoparticles alleviate fluoride-induced hippocampal neurotoxicity by targeting the DUSP5-ERK-CREB-BDNF signaling axis - Haojie Li; Fangyu Yan; Cheng Huang; Weijiang Chu; Rongze Wang; Tianyu Wang; Hui Zhao; Yuanyuan Li; Jiarong Yang; Zijun Hao; Yufeng Gao; Jie Ren; et al. (Chemical Engineering Journal, 2026)

Multiscale simulation of SiO2 nanoparticle evolution in coaxial premixed combustion reactors - Jie Ju; Lingli Luo; Yingjie Wu; Qilin Cheng; Hao Jiang; Yanjie Hu; Chunzhong Li (Chemical Engineering Journal, 2026)

Bacteria-derived carbonic anhydrases enhance the soil shear strength of biocrusts - Zhimao Mai; Lin Wang; Qiqi Chen; Si Zhang; Jing Zhang; Hao Cheng; Jian Zhang; Xiaobing Zhou; Jie Li (CATENA, 2026)

Comprehensive virome analysis of soybean agroecosystems in China reveals geographic patterns and interfacial virus spillovers - Mengjia Xu; Ruixiang Cheng; Rong Yan; Hao Ai; Sijing Qiao; Pengbo Li; Jin Zhang; Tianyu Hu; Xiaoli Chang; Huawei Yang; Wenwu Ye; Ming Ding; et al. (Science China Life Sciences, 2026)

Melatonin Ameliorates Neuropathic Pain in Mice by Regulating Pyroptosis Through Gut Microbiota-Mediated Linoleic Acid - Yan Wang; Bin Yuan; Yunzi Li; Yan Sun; Yi Xie; Hao Cheng; Yao Zhang; Qi Wu; Jun Tang (Molecular Neurobiology, 2026)

miR-124 Ameliorates Spatial Memory Deficits in Rats Exposed to Single-Prolonged Stress by Downregulating IQGAP1 to Regulate Actin-Binding Proteins and Apoptosis in Hippocampal Neurons - Qi An; Miao Li; Xin-Yu Ji; Cheng-Hao Piao; Shu-Ting Yang; Lei Tong; Li-Li Ji (Molecular Neurobiology, 2026)

Inhibition of the Microglial cGAS-STING Pathway Improves Neurological Deficits and Long-Term Hydrocephalus Symptoms in Mice with Intraventricular Hemorrhage - Hao-Xiang Wang; Hua-Jiang Deng; Kun-Hong Zhong; Zi-Ang Deng; Bao-Cheng Gao; Xin Tang; Yuan-You Li; Ke-Ru Huang; Ai-Ping Tong; Da-Xiong Feng; Liang-Xue Zhou (Molecular Neurobiology, 2026)

Single-Cell RNA Sequencing Reveals Impaired CHIP-Mediated Heat Stress Response in SCA3 Pathogenesis - Mi-bo Tang; Shi-feng Sheng; Zheng-wei Hu; Hai-yang Luo; Meng-jie Li; Shuo Zhang; Xiao-yan Hao; Cheng-yuan Mao; Shao-hua Li; Hui-fang Sun; Zhi-hua Yang; Yi Song; et al. (Molecular Neurobiology, 2026)

The Role of Thyroid Hormones in Neurodegenerative Disorders: Opportunities and Challenges - Yi Zhang; Miao Hao; Yuchuan Li; Kewen Cheng; Chunhai Zhang (Molecular Neurobiology, 2026)

Association between low daily average temperature and epilepsy outpatient visits: a hospital-based study in Chongqing, China - Pei Jiang; Jing Yang; Yumeng Zhou; Jinchi Gu; Fengxia Liu; Chunlei Tan; Yao Cheng; Hao Wang; Li Mao; Peng Hu; Ping Chen; Ding Liu; et al. (International Journal of Biometeorology, 2026)

Microbial drivers of N₂O mitigation in soils: Role of nosZ II subclades under conservation tillage and stover mulching - Da-Cheng Hao; Yaoxuan Wang; Yuanyuan Luan; Fangbo Deng; Hongtu Xie; Yongxin Lin; Xuanqi Li; Zhongjun Jia; Lianfeng Wang (Applied Soil Ecology, 2026)

Spatial phylogenetics and biocultural conservation of medicinal plants in ethnic minority communities of china: implications for environmental sustainability - Da-Cheng Hao; Yaoxuan Wang; Zhi-Duan Chen; Li-Min Lu; Pei-Gen Xiao (Biodiversity and Conservation, 2026)

Dual-promoter systems drive plasmid loss via non-translational burden in geraniol-producing E. coli - Jia Zhou; Mengqi Cheng; Shengyang Su; Ziyi Li; Mengxin Lv; Die Hu; Xiaodie Zhang; Yilong Zhou; Hao Shi; Zhongbiao Tan; Ya Xin; Dianlong Wang; et al. (Archives of Microbiology, 2026)

Programmed cell death in osteoarthritis - Haolin Li; Ping Chen; Weigang Cheng; Zhimin Zhang; Juanjuan Yang; Hao Zhang; Fangmei Jin; Lili Kan; Lei Chen; Haidong Wang (Apoptosis, 2026)

The groundwater mixing mechanism and hydrogeochemical processes driven by coal mining in the typical area, Northern Ordos, China - Yang Meng; Zhaoji Zhang; Qichen Hao; Zhixiu Wang; Chunxiao Cheng; Fengran Zhang; Yan Dong; Pengfei Han; Yasong Li (Environmental Monitoring and Assessment, 2025)

Dominant factors of individual tree mortality at stand scale: analyzing crown structure and neighbourhood competition via UAV laser scanning - Xin Liu; Yuanshuo Hao; Xinyang Zou; Shoumin Cheng; Lihu Dong; Fengri Li (Computers and Electronics in Agriculture, 2025)

The potential impact of glacier volume changes on biome dynamics in the southeastern margin of the Tibetan Plateau since the last deglaciation - Pengyu Li; Ziru Hao; Yang Yang; Xiao Zhang; Mengna Liao; Lina Liu; Kai Cui; Yongbo Wang; Haiyan Li; Jun Cheng; Kai Li; Jian Ni (Quaternary Science Reviews, 2025)

Dynamic performance of trains in submerged floating tunnels under wave loading - Linzhong Han; Bo Huang; Wenlong Luo; Cheng Cui; Jie Hou; Hao Ding; Ke Li; Liang Cheng; Dan Zhong; Jiawei Zhou (Ocean Engineering, 2025)

Bio-inspired intermittent locomotion: A novel energy-saving strategy for manta ray-inspired underwater vehicles - Ao Liu; Cheng Xing; Wei Cao; Bojun Liu; Shuai Wang; Jiale Jin; Wenze Zhang; Kangkang Li; Yang Lu; Yiwei Hao; Yonghui Cao; Yong Cao (Ocean Engineering, 2025)

The study of stiffness design of tube, cable, and joint in submerged floating tunnel by segmentation analysis method under static and dynamic loads - Jie Hou; Bo Huang; Linzhong Han; Peng Chen; Hao Ding; Jianting Zhou; Ke Li; Liang Cheng; Dan Zhong; Jiawei Zhou (Ocean Engineering, 2025)

Recognition of a phytocytokine by the DEPR1–SERK2 receptor complex confers multi-pathogen resistance in wheat - Lijun Wang; Jun Zhao; Chuanchun Yin; Hongxu Li; Yanan Xiao; Cuicui Du; Zhaoxi Lu; Yongjian Zhang; Fangshuai Jia; Jiaxin Hao; Jinghui Yan; Yi Zhang; et al. (Molecular Plant, 2025)

Large variations in zircon hafnium isotopes due to preferential dissolution of high-U zircon: A case study of the Lincang Batholith in SW China - Jia-Hao Fan; Jin-Cheng Xie; Li Liu; Qing Wang; Di-Cheng Zhu (Lithos, 2025)

Evaluating the impact of “source-sink" landscape composition and configuration changes on sediment yield in watersheds using a coupled multi-model framework - Hao Yang; Zixuan Qi; Wei Huang; Bo Li; Guanhui Cheng; Yanpeng Cai (Journal of Cleaner Production, 2025)

Machine learning-driven advances in water treatment - Zhen Qiu; Zechao Zhuang; Xue Jia; Hao Li; Cheng Chen; Jinchao Shen; Bing Yu (Journal of Environmental Chemical Engineering, 2025)

Combined toxicity of microplastics and heavy metals to terrestrial plants: A global meta-analysis integrating machine learning predictions - Ye-Qian Zhen; Tian-Hao Che; Yu-Xuan Song; Ya-Ming Wan; Hai-Han Jiang; Zuo-Zhou Yu; Miao Yu; Shi-Qi Xu; Cheng-Yong Li; Jing-Ya Zhou (Journal of Environmental Chemical Engineering, 2025)

Application of microbial electrolysis cells in enrichment of anammox bacteria - Qi Gao; Liang Fu; Jing Wei; Xiao-Chun Wang; Xiang Xiao; Yang-Yang Yu; Liang Cheng; Yu-Hao Qiu; Shan-Wei Li (Journal of Environmental Chemical Engineering, 2025)

Dual-functional carbon materials for sustainable Cr(VI)-organic co-decontamination: Structure activity relationship analysis of defect and oxygen content - Ming Zhang; Qingkai Shi; Jing Tong; Min Cheng; Hao Ge; Sai Li; Guangfu Wang; Li Du; Hongda Liu; Ao Chen; Zhongwu Li (Journal of Environmental Chemical Engineering, 2025)

Experimental study of hydrogen release self-ignition at different CH4 ratios - Hao Qi; Zhenmin Luo; Shangyong Zhou; Kai Wang; Tao Wang; Bin Su; Ruikang Li; Fangming Cheng (Fuel, 2025)

A novel BWBN-integrated physics-informed neural network for advanced hysteretic modeling of RC structures under cyclic loads - Cheng Yuan; Xiaojun Fang; Zhejian Li; Qingzhao Kong; Wensu Chen; Hong Hao (Engineering Structures, 2025)

Corrigendum to “Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration” [Chem. Eng. J. Volume 523 (2025) 168846] - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Negative-pressure induced controllable foaming reaction for ultralight and flame-retardant phenyl-containing silicone rubber foam nanocomposites modified with low content of graphene oxide - Shuai-Chi Liu; Yun-Hao Qu; Dun-Peng Bao; De-Mei Kong; Zhi-Hao Xu; Zuan-Yu Chen; Yang Li; Jie-Feng Gao; Yong-Qian Shi; Pingan Song; Guo-Dong Zhang; Long-Cheng Tang (Chemical Engineering Journal, 2025)

Copper sulfide catalysts facilitating zinc sulfide electro-oxidation in aqueous zinc–sulfur batteries - Peng Hei; Guangxu Hu; Lin Yu; Yulai Lin; Xueying Ning; Bo Li; Yuqing Wang; Zhaohui Chen; He Chong; Hao Cheng; Jing Wang; Weibin Cui; et al. (Chemical Engineering Journal, 2025)

Cascade pH-responsive multi-drug delivery nanosystem actuates PANoptosis of triple-negative breast cancer - Zhechen Fan; Junqiu Ye; Sijia Yao; Zhongsheng Ji; Weisong Li; Jianping Zhou; Hao Cheng; Yang Ding (Chemical Engineering Journal, 2025)

A study on soil erodibility and the applicability of estimation methods in Robinia pseudoacacia L. mixed forests on the Loess Plateau, China - Jin-long Ma; Bing Wang; Run-hao Yu; Yan-fen Yang; Guo-bin Liu; Jing Wang; Cheng-fang Li (CATENA, 2025)

Role of mitochondrial metabolism in ischemic stroke and natural products intervention - Xuan-Hao Zhang; Ying Li; Cheng-Yu Jin; Jia-Le Zhang; Yang-Peng Yan; Jia-Xiu Guo; Xin Lu; Han-Qing Pang; Yong-Juan Zhao (Molecular Biology Reports, 2025)

Serum amyloid A: multifaceted roles in inflammation and cellular interactions - Shouzheng Cheng; Dingyu Duan; Hao Cui; Yingying Lian; Fan Jiang; Qianming Chen; Taiwen Li; Lei Zhao (Immunologic Research, 2025)

Prediction of the natural fracture linear density in Block B of the Sichuan Basin: insights from conditional probability binning ensemble methods - Mengchu Xiao; Yuntao Li; Mengyang Zhang; Xiaoyun Cheng; Xiang He; Hao Jian (Carbonates and Evaporites, 2025)

Partially empirical model-based water depth retrieval in shallow sea using GF5-AHSI hyperspectral remote sensing data: a case study on Meizhou Bay in Fujian Province, China - Xiaoai Dai; Yunfeng Shan; Cheng Li; Hao Chen; Tangrui Dai; Ge Qu; Tianyi Xie; Chengbo Tong; Htun Naing; Min Zhang (Frontiers of Earth Science, 2025)

Characterization of pyrolytic properties of pyrite in the terahertz frequency band - Tong Zhang; Cheng Song; Zhi-Yuan Zheng; Si-Qi Zhang; Hao-Chong Huang; Jun-Feng Shen; Xiao-Wei Li (Applied Geophysics, 2025)

Dispersal, Climate Anomaly and Contemporary Climate Shape the Latitudinal Patterns of β‐Diversity of Angiosperm Trees - Liqi Lu; Jie Li; Fushan Cheng; Jingyuan He; Minhui Hao; Chunyu Fan; Chunyu Zhang; Klaus von Gadow; Xiuhai Zhao (Global Ecology and Biogeography, 2025)
Aim The underlying drivers of latitudinal gradients in multifaceted β‐diversity remain debated. The primary focus on abiotic drivers of β‐diversity has left dispersal processes insufficiently explored. This study presents a multiscale analysis of how dispersal, Quaternary climate and contemporary environmental conditions influence multifaceted β‐diversity and its decomposition components in a large temperate forest. Location Northeast China. Time Period 2017. Major Taxa Studied Angiosperm trees. Methods We constructed metacommunities by aggregating multiple sets of local plots to assess taxonomic, functional and phylogenetic β‐diversity across spatial scales. β‐diversity was then partitioned into species replacement and richness difference. Using a community dispersal capacity metric (DCMc), we first evaluated its abiotic drivers and then applied variance partitioning to disentangle the relative contributions of dispersal and environmental filtering to latitudinal patterns of β‐diversity. Spatial simultaneous autoregressive models and structural equation models were then employed to estimate the direct and indirect effects of DCMc and abiotic factors on β‐diversity and its components. Results Environmental filtering emerged as the dominant mechanism of community assembly across scales, whereas dispersal gained importance at broader scales, primarily through spatial and historical structures. We found that DCMc itself represents a legacy of Quaternary climate change. After accounting for abiotic factors, high DCMc values decreased richness differences but increased replacement, while contemporary climate continued to dominate across scales. Interestingly, DCMc had no significant effect on total β‐diversity, whereas temperature anomaly indirectly shaped β‐diversity by influencing DCMc. Main Conclusions Dispersal plays a secondary but significant role relative to environmental filtering in shaping the three facets of β‐diversity, particularly through its mediation of Quaternary climate legacies. Our findings highlight the importance of contemporary climate and reveal distinct pathways by which historical climate shapes different facets of β‐diversity, underscoring the complex interplay between dispersal and environmental filtering in community assembly across scales.

Neuroprotective Effects of Glucosamine in Huntington’s Disease Through NLRP3 Inflammasome Inhibition - Lichieh Julie Chu; Yi-ting Hsu; Yu Aoh; Chih-Yuan Cheng; Hui-Hsuan Wang; Ming-Tse Wu; Hao-Hsuan Li; Xiu-Yuan Lai; Kuo-Feng Hua; Chiung-Mei Chen; Tz-Chuen Ju (Journal of Neuroimmune Pharmacology, 2025)

Per- and polyfluoroalkyl substances in tissues of intermediate egrets (Ardea intermedia) from the South China Sea - Ling Mo; Jun Xiang; Ming-Yang Wang; Yu-Quan Zhang; Qin-Wei Hao; Qi-Fei Peng; Yong-Fu Chen; Yu-Feng Hu; Jing Zheng; Qiao Xing; Bin Tang; Li-Cheng Wang (Marine Pollution Bulletin, 2025)

Geniposide induces hepatotoxicity via the bile acid-induced activation of NLRP3 inflammasome and regulation of the FXR/PERK/TXNIP pathway - Zhinan Jin; Shenghui Cheng; Baoyue Liu; Yixuan Liu; Yanming Wei; Xuliang Hao; Huifang Li (Toxicology Letters, 2025)

Asthenospheric upwelling-induced seismic activity in the eastern North China Craton: Evidence from viscosity obtained from an MT study - Baochun Li; Gaofeng Ye; Sheng Jin; Wenbo Wei; Letian Zhang; Hao Dong; Chengliang Xie; Yaotian Yin; Shaohuai Sun; Zhaoyuan Kang; Peng Ding; Yiwu Zhang; et al. (Tectonophysics, 2025)

Green manure species synergize with organic fertilization to enhance soil nutrient–microbial interactions and wheat productivity in oasis drip–irrigated systems - Liyang Cheng; Hao He; Shuai Li; Mengmeng Yu; Tingting Wan; Jie Qin; Chunyan Li; Junhua Li (Field Crops Research, 2025)

Long-term exposure to ambient benzene and incident type 2 diabetes mellitus in a national cohort: The modifying effect of genetic susceptibility - Zhi-Hao Xiao; Qian Li; Xinwei Guo; Guangfeng Long; Zitong Meng; Cheng Xu (Environmental Research, 2025)

Regulation of cell migration through cross-sectional morphology design to facilitate implant-to-ureter regeneration - Baiyang Song; Zonghuan Wang; Junjun Huang; Yiwei Hu; Fang Yang; Zewen Shi; Yuhao Cao; Li Fang; Hao Rong; Zejun Yan; Junhui Jiang; Ruoyu Zhang; et al. (Chemical Engineering Journal, 2025)

Sugar-based block copolymer/carbon nanotube nanocomposites for thermoelectric applications - Yen-Yu Chen; Hong Li; Chih-Jung Lin; Koshin Tanaka; Meng-Hao Lin; Shao-Huan Hong; Min-Chi Fu; Jian-Fa Ding; Yu-Jane Sheng; Redouane Borsali; Tsuyohiko Fujigaya; Cheng-Liang Liu (Chemical Engineering Journal, 2025)

Flexible piezoresistive sensing device with integrated design and fabrication for health monitoring - Wen Zhao; Lufang Geng; Jian Li; Hao Zhang; Shu Zhang; Yanling Guo; Shunxin Cheng; Wei Zhao (Chemical Engineering Journal, 2025)

Formoterol, a clinically approved drug, inhibits ferroptosis by suppressing lipid peroxidation and attenuates APAP-induced acute liver injury - Lin-Song Teng; Zhen-Dong Ying; Xiao-Han Sun; Hao-Cheng Hou; Shi-Dong Qiu; Peng Liu; Ke-Jing Li; Lei Zhang; Xie-Huang Sheng (Chemico-Biological Interactions, 2025)

Novel strategy for recovering phosphorus from sulfate-rich wastewater combined with phosphogypsum recycling - Yan Cheng; Haibo Li; Wenjie He; Hao Dong; Linfeng Wang; Gang Guo; Guanghao Chen; Jie Ma (Bioresource Technology, 2025)

Characterization of particle number size distribution and new particle formation in a highly-humid megacity Wuhan, central China - Haoqian Wang; Xiaoxiao Li; Jin Wu; Hao Wu; Yiran Li; Chong Liu; Ning Ma; Ping Zeng; Xuehui He; Jiapeng Ran; Huaying Song; Dandan Huang; et al. (Atmospheric Environment, 2025)

From growth to decline: The dynamic effects of maize-based cropping systems on soil organic carbon storage in Northeast China - Jin-Sai Chen; Zhuo Shi; Yu-Gang Tian; Hao-Ran Li; Hong-Xuan Duan; Zhi-Heng Qin; Jia Cheng; Yash Pal Dang; Bai-Jian Lin; Xin Zhao; Hai-Lin Zhang (Agriculture, Ecosystems & Environment, 2025)

Human adenovirus in Taiwan, 2019–2023 - Su-Lin Yang; Wan-Ju Tsai; Chung-Hao Li; Yu-Hsin Cheng; Shu-Wei Lin; Ming-Tsan Liu; Fang-Tzy Wu (Archives of Virology, 2025)

Discovery and profiling of efficient microbial strains for struvite biomineralization in high-salinity wastewater - Bing-bing Liu; Rong-ji Zhao; Nimaichand Salam; Shu-hong Xu; Rong Shi; Jiang-hao Zhu; Zi-qing Chen; Cheng-yin Liu; Bing Li; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Research on the Meso-mechanism of the Evolution of Wet Expansion Cracks in Expansive Soil Based on Discrete Element Method - Xue-lei Cheng; Xiao-fan Xing; Sheng-hui Feng; Shuo-shuo Guo; Qi-qi Li; Lu-yun Guo; Zhong-hao Zhu (Applied Geophysics, 2025)

Research on the oxidative decomposition of 1,2-bis(2,4,6-tribromophenoxy)ethane induced by •OH, SO4-•, and O3: Transformation mechanism, kinetics, and toxicity assessment - Yang Long; Liming Tai; Shi Yan; Jinbao Huang; Hong Wang; Xinsheng Li; Hao Cheng; Li Jin (Journal of Environmental Chemical Engineering, 2025)

Manipulating internal catalytic microenvironment of dynamic Cu/SSZ-13 catalysts by in situ Ce incorporation for efficient NH3-SCR - Yan Wang; Tiantian Zhang; Xinya Wu; Yuanjiang Wang; Hao Qu; Cheng Zhang; Jianguo Cui; Cailing Xu; Zhaoqiang Li; Yongquan Qu; Shanghong Zeng (Journal of Environmental Chemical Engineering, 2025)

Integrated machine learning model for prediction of nutrients contents and maturity in rural organic solid wastes aerobic composting - Hao Peng; Lan Mu; Yingjin Song; Hong Su; Yadong Ge; Zhanjun Cheng; Rundong Li; Guanyi Chen (Journal of Environmental Chemical Engineering, 2025)

Synergistic engineering of four-pointed star-like layered stacking and oxygen vacancies toward high-efficiency Bi2O2-xSe photocatalysts for the degradation of tetracycline and Congo red - Yao Yang Liu; Zhong Li; Yi Liang; Jing Hao Zhuang; Wen Ji Zhang; Tao Tang; Yin Fen Cheng; Rui Ou; Bao Yue Zhang; Jian Zhen Ou (Journal of Environmental Chemical Engineering, 2025)

A real-time intelligent lithology identification based on an optimized Kalman filtering K-nearest neighbors algorithm - Youpeng Diao; Longlong Li; Jian Li; Cheng Jiang; Zhiyong Hao; Hairui Jiang (Journal of Applied Geophysics, 2025)

Flavoromics analysis and sensory evaluation of wines produced from nine red grape cultivars in Manas region, Xinjiang, China: Implications for terroir adaptation - Ning Shi; Yi-Fan Zhao; Hao-Cheng Lu; Meng-Bo Tian; Ming-Yu Li; Jia-Yi Deng; Jia-Yan Wei; Ai-Sai Chen; Chi-Fang Cheng; Shu-De Li; Fei He; Keji Yu; et al. (Food Chemistry, 2025)

Identifying gelatin source by mass spectrometry: A review - Xiao-Mei Sha; Le-Ying Yang; Hui Wang; Jie Cheng; Hao-Sheng Luo; Li-Jun Zhang; Zi-Zi Hu; Zong-Cai Tu (Food Chemistry, 2025)

Real-time geological hazard detection ahead of tunnel face using blast-induced seismic signals: A case study in Tashan Tunnel, China - Xingang Zhang; Shuai Cheng; Jiquan Zi; Liping Li; Qinliang Sun; Chao Jia; Hao Wang (Engineering Geology, 2025)

Fracture evolution and anchoring mechanisms in discontinuous rock masses with irregular joints: Discrete element study using a novel damage constitutive model - Yin-Ge Zhu; Yue Wu; Cheng-Hao Han; Wei-Guo Qiao; Feng Jiang; Ji-Xian Dong; Shuai Zhang; Yan-Zhi Li (Computers and Geotechnics, 2025)

High-efficiency enrichment process of uranium from amidoxime-functionalized fibers after treated by alkaline elution system - Shen Zhang; Wencai Cheng; Congcong Ding; Ze Qiu; Junwen Tan; Xirui Lu; Jun Wen; Hao Li (Chemical Engineering Journal, 2025)

Superwetting aqueous electrolyte for highly stable zinc anodes - Yurou Wu; Huijian Wang; Meilan Xie; Kai Fu; Zhendong Li; Xingyuan Dai; Jiarui Zhang; Lihan Wang; Xiaoshu He; Yidan Luo; Sheng Ouyang; Wen He; et al. (Chemical Engineering Journal, 2025)

Biphasic continuously composite electrolyte design for high-performance solid-state Li–CO2 batteries - Qian-Cheng Zhu; Shu-Jian Li; Zi-Yuan Wang; Fu-Li Zhang; Jin-Hao Xie; De-Yu Mao (Chemical Engineering Journal, 2025)

Bamboo-inspired self-descaling tubular evaporators with a Janus-confined water layer for rapid and durable hypersaline brine desalination - Yi-Zhou Chen; Ting Shen; Jia-Hui Xin; Yu Zhang; Kai Li; Ling-Shu Wan; Hao-Cheng Yang; Zhi-Kang Xu (Chemical Engineering Journal, 2025)

Local collaboration between oxygen vacancy, palladium and platinum trimer triggers exceptional performance in the alkaline fuel cell - Dinesh Bhalothia; Che Yan; Yawei Wu; Jui-Cheng Kao; Yu-Chieh Lo; Haolin Li; Nozomu Hiraoka; Hirofumi Ishii; Yen-Fa Liao; Sheng Dai; Chen-Hao Wang; Alice Hu; et al. (Chemical Engineering Journal, 2025)

A customized immunomodulator reinforces the T cell-mediated immunological cascade for cancer therapy - Guowang Cheng; Jiaxin Wu; Wei Liu; Yumiao Yang; Hao Cui; Xiuxiu Dai; Bowen Li; Zhen Tian; Xiaojia Chen; Xiaohui Li; Zhenfeng Wu; Guochao Liao; et al. (Chemical Engineering Journal, 2025)

Retrieval of water cloud droplet size from multi-angle satellite imagery - Wenhui Luo; Haifeng Xu; Shijie Liu; Cheng Dai; Hao Chen; Jinji Ma; Zhengqiang Li (Atmospheric Environment, 2025)

Organic nitrates in coastal aerosols: Seasonal dynamics, influencing factors, and formation pathways - Mengke Tian; Zhijian Ding; Jia Chen; Juntao Huo; Guochen Wang; Jian Xu; Hao Li; Ziwei Liu; Yunkai Wang; Nan Ye; Xiaofei Qin; Yanfen Lin; et al. (Atmospheric Environment, 2025)

HMGA2 Attenuates Tendon Stem/Progenitor Cell Senescence Via PI3K/AKT-Mediated Mitophagy Activation and SASP Suppression - Hao Wang; Guang-Chun Dai; Yu-Cheng Gao; Xiao-Yu Liu; Pan-Pan Lu; Mu-Min Cao; Ren-Wang Sheng; Liu Shi; Zhang Cheng; Ying-Juan Li; Yun-Feng Rui (Stem Cell Reviews and Reports, 2025)

Multi-omic-based classification for identifying optimal neoadjuvant treatment strategies for high-risk early-stage breast cancer - Fei Ji; Xianzhe Chen; Ciqiu Yang; Liulu Zhang; Mei Yang; Jieqing Li; Hongfei Gao; Teng Zhu; Minyi Cheng; Yitian Chen; Hao Peng; Jin Wang; et al. (Science China Life Sciences, 2025)

Comparative Transcriptomic Analysis Reveals Key Growth-Related Genes and Alternative Splicing Events in Siniperca scherzeri - Hao Xu; Jian Jin; Yang Li; Yannian Wu; Zhiqiang Cheng; Maoyuan Wang; Xiaojun Ye; Mingyong Lai; Dongling Zhang (Marine Biotechnology, 2025)

Populus Euphratica extraction based on deep learning of spatiotemporal Information using Sentinel data - Hao Li; Qinyu Zhao; Jiacong Hu; Jiawei Zou; Chao Ding; Luyan Ji; Suhong Liu; Weiming Cheng (International Journal of Remote Sensing, 2025)

A novel dynamic membrane-equipped element sulfur-based denitrification reactor for efficient and easily maintainable treatment of high-nitrate wastewater - Na Zhang; Xiang-Li Zeng; Wen-Wei Liao; Meng-Yi Chen; Guijiao Zhang; Da-Heng Ren; Xu-Chen Ba; Min-Kun Zhang; Hao-Ran Xu; Aijie Wang; Hao-Yi Cheng (Water Research, 2025)

A holistic seismic performance evaluation of irregular curved bridges with precast segmental piers considering SSI and depth-varying spatial motion inputs - Yu-Cheng Diao; Chao Li; Hong-Nan Li; Hui-Hui Dong; Er-Tong Hao (Soil Dynamics and Earthquake Engineering, 2025)

Study on optimization of prediction models for small-scale oil spill area: Impacts of wind and waves - Hao Yan; Xueyan Cheng; Mei Liu; Qian Li; Kecun Ma; Zhi Chen; Qingguo Chen (Process Safety and Environmental Protection, 2025)

Analysis of spontaneous failure of lithium-ion battery under micromechanical deformation - Chuang Qi; Hongtao Yan; Hao Cheng; Yuemeng Zhang; Chunjing Lin; Siqi Chen; Xi Liu; Li Lao; Yazhou Sun; Qiang Wang (Process Safety and Environmental Protection, 2025)

Changes in cell wall characteristics and expression of MiERF12, MiERF109-like, and MiERF113 during mango softening - Yuhan Long; Lihong Xie; Ping Yi; Fang Huang; Min Huang; Ting Gan; Jian Sun; Li Li; Hao Dong; Qi Wei; Zhenmei Fan; Qiuyu Cheng (Postharvest Biology and Technology, 2025)

Study of cable layout selection for oval cross-section submerged floating tunnel under wave-current coupling action - Chong Ji; Mengqi Tian; Xiantao Zhang; Xin Li; Ke Li; Dan Zhong; Liang Cheng; Hao Ding (Ocean Engineering, 2025)

Analysis of the influence of key structural parameters on the dynamic response of oval cross-section SFT under wave-current action - Hao Ding; Chong Ji; Mengqi Tian; Ke Li; Liang Cheng; Dan Zhong; Xiantao Zhang; Xin Li (Ocean Engineering, 2025)

Acetamiprid mediates cognitive dysfunction through the gut-brain axis: Synaptic damage and immune-mediated blood-brain barrier dysfunction - Bing Wu; Xue-yan Tian; Wen-si Ni; Hao-Xuan Gao; Yu-wen Wang; Ling-he Zhang; Yu-bin Li; Yan-ling Lv; Ya-nan Song; Yu-cheng Yan; Xiao-zhe Geng; Yi-man Li; et al. (Journal of Hazardous Materials, 2025)

Causal links between long-term exposure to the chemical constituents of PM2.5 and lung cancer mortality in southern China - Shimin Chen; Peiwen Ye; Jing Wei; Huanhuan Cheng; Yuqin Zhang; Yujiao Ma; Shirui Chen; Wenjing Wu; Tong Guo; Zhiqiang Li; Jie Jiang; Yujie Ma; et al. (Journal of Hazardous Materials, 2025)

Using ventilation hood during cooking reduced household air pollution exposure and brought cardiometabolic and pulmonary health benefits: A community-based, cluster-randomized controlled intervention study - Yueru Yang; Kuai Yu; Wending Li; Xuedan Xu; Chengyong Jia; Qi Yan; Xingxing Li; Hao Cai; Denghuan Hu; Hui Gao; Xuanwen Mu; Yuhui Lin; et al. (Journal of Hazardous Materials, 2025)

Interfacial electric field steering S-scheme charge transfer in MIL-88A(Fe)/polydopamine Heterojunctions: Dual-redox pathways for efficient pollutant mineralization - Bo Shen; Hao Du; Aoxiang Liu; Ningyi Li; Cheng Chen; Liguo Shen; Yuxin Hui; Rubin Huo; Zhe Zhang; Qi Wang (Journal of Cleaner Production, 2025)

Holographic, traceable, and switchable anti-counterfeiting using temperature-tolerant relief gratings on polyimide substrate - Chengwei Xiao; Haixian Shi; Hao Zhong; Chengbin Zou; Yiyong Chen; Jinru Li; Weien Liang; Wanying Zhang; Dezhi Zhan; Shilong Zhong; Rui Chen; Zhaoxiang Zhu; et al. (Chemical Engineering Journal, 2025)

Recent progress in two-dimensional materials: From emerging structures and synthesis approaches to electronic and sensing applications - Jing Hao Zhuang; Zhong Li; Yi Liang; Tao Tang; Xin Yi Hu; Rui Ou; Qi Jie Ma; Bao Yue Zhang; Yin Fen Cheng; Wen Lin Feng; Jian Zhen Ou (Chemical Engineering Journal, 2025)

A-site vacancy engineering and electron density optimization in layered perovskite anodes for high-performance lithium-ion batteries - Jiahui Chen; Haoyan Cheng; Yuhao Li; Chang Lu; Tianwen He; Hao Hu (Chemical Engineering Journal, 2025)

Electrostatic interaction strategy stabilizes the crystal structure in ultra-high Ni cathode - Jianlong Wang; Honglin Yan; Cheng Wei; Yuan Ha; Weidong Zhu; Lu Li; Chaoyi Zhou; Qianxin Xiang; Zhimin Li; Yue Hao (Chemical Engineering Journal, 2025)

Comparative analysis of rural organic waste treatment: greenhouse gas emissions, economics, and energy flow - Hao Peng; Lan Mu; Yingjin Song; Dan Zeng; Hong Su; Zhanjun Cheng; Rundong Li; Guanyi Chen (Biomass and Bioenergy, 2025)

Effects of Commercial Organic Fertilizers and Soybean Green Manure on Wheat Growth and Soil Microbial Communities in Oasis Farmlands - Liyang Cheng; Hao He; Xiangjie Chang; Xiaojuan Yang; Shuai Li; Mengmeng Yu; Junhua Li (Journal of Soil Science and Plant Nutrition, 2025)

MTGGF: A Metabolism Type-Aware Graph Generative Model for Molecular Metabolite Prediction - Peng-Cheng Zhao; Xue-Xin Wei; Qiong Wang; Hao-Yang Wang; Bing-Xue Du; Jia-Ning Li; Bei Zhu; Hui Yu; Jian-Yu Shi (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Probabilistic failure mode-based prediction method for flexural design capacities of precast reinforced concrete and prestressed concrete beams - Yukun Hu; Jitao Yao; Kaikai Cheng; Luyang Zhang; Meng Ran; Hao Li; Jiewei Xu (Bulletin of Earthquake Engineering, 2025)

Establishment and characterization of a new Chinese extrahepatic cholangiocarcinoma cell line, EBC-X1 - Yuanhui Su; Huan Tang; Xin Miao; Cheng Yu; Changpeng Chai; Wei Huang; Lu Li; Jieyu Zheng; Tao Xu; Fa Jin; Zhipeng Ye; Zhao Hu; et al. (Human Cell, 2025)

Bucking and free vibration characteristics of smart hybrid sandwich plate via spatial state-space approach - Hao Li; Cheng Zhang; Yudong Han (Wave Motion, 2025)

Coupling effect of phytic acid and chlorite on uranium removal by Shewanella putrefaciens under simulated natural environment - Qingrong Li; Yang-Yang Zhang; Guo-Hao Zhang; Yilin Qin; Wencai Cheng; Xinyu Wang; Liuyuan Fu; Nan Wang; Xiaoan Li; Faqin Dong; Jun Li; Xiaoqin Nie (Water Research, 2025)

Iron pipe corrosion enhanced the transformation of iopamidol, a precursor of iodinated disinfection byproducts: The role of sulfate-reducing bacteria - Jun Hu; Zilong Zhang; Xinyuan Wu; Hao Zheng; Zhuce Cheng; Li Gong; Zhimin Qiang; Jianming Yu (Journal of Hazardous Materials, 2025)

Synergistic catalytic degradation of benzene and toluene on spinel MMn2O4 (M Co, Ni, Cu) catalysts - Xin Xing; Zhe Li; Yixin Wang; Zonghao Tian; Dandan Liu; Jie Cheng; Zhengping Hao (Journal of Environmental Sciences, 2025)

Chemical and cell toxicity properties of particulate matter emitted from a diesel engine fueled with biodiesel and ethanol blends - Pak Kin Wong; Shou Hao Chen; Meisam Ahmadi Ghadikolaei; Kar Wei Ng; Simon Ming Yuen Lee; Jin Cheng Xu; Zhen Dong Lian; Lin Li; Shuli Li; Zhi Ning; Nirmal Kumar Gali; Adebayo Afolabi Fadairo (Environmental Pollution, 2025)

Wake-induced vibrations of tandem main cables: Insights from flexible and rigid models in wind tunnel tests - Jun Xu; Hao-Yang Li; Tai-Ke Zhang; Cun-Ming Ma; Cheng Pei; Qing-Song Duan (Engineering Structures, 2025)

Mechanistic insights into the combustion behaviors of 5AT/Sr(NO3)2 solid propellant induced by additives (Cu2(OH)2CO3 and Cu(OH)2)) - Jiu Chen; Guang-Ling Chen; Yuan-Hui Liu; Peng-Cheng Xi; Hao-Tian Zhou; Mi Li; Guang-Cheng Yang; Li-Feng Xie; Dan Zhang (Chemical Engineering Journal, 2025)

Interfacial engineering electron-rich Cuδ−-Ov-Zn oxygen vacancy via Mn Cu alloy in LDH structure for selective CO2 conversion to methanol - Zhefeng Li; Wentao Du; Zhuo Chen; Yongbin Zhong; Tongyun Zhang; Jingwen Xu; Yuanfa Zhuang; Weixin Liu; Hao Li; Shengxuan Luo; Jun Cheng (Chemical Engineering Journal, 2025)

Corrigendum to “Active and intelligent gellan gum-based packaging films for controlling anthocyanins release and monitoring food freshness” [Carbohydrate Polymers 254 (2021) 117410] - Li-Ting Wu; I-Lin Tsai; Yi-Cheng Ho; Yu-Hao Hang; Chi Lin; Min-Lang Tsai; Fwu-Long Mi (Carbohydrate Polymers, 2025)

Unveiling interactions between anammox and denitrification from long-term steady-state scale and transient kinetic scale in a granular sludge system - Hao Tan; Fengjun Yin; Jinjin Zheng; Xuehai Yue; Ying Zhao; Sha Wang; Cheng Song; Yongzhi Li; Hong Liu (Bioresource Technology, 2025)

Chemical constituents from Dictamnus dasycarpus Turcz. and their chemotaxonomy value - Yan Liu; Guangzhi Li; Ye Sun; Jiatong Wu; Shiqi Xu; Juan Pan; Junnan Li; Luxin Li; Zhichao Hao; Wei Guan; Yuanyuan Zhou; Qi Shi; et al. (Biochemical Systematics and Ecology, 2025)

CCN1 Is a Therapeutic Target for Reperfused Ischemic Brain Injury - Gilbert Aaron Lee; Yu-Wei Chang; Jing-Huei Lai; Tzu-Hao Chang; Shiu-Wen Huang; Chih‑Hao Yang; Ting-An Shen; Wan-Li Lin; Ying-Chieh Wu; Li-Wen Tseng; Sung-Hui Tseng; Yung-Chieh Chen; et al. (Translational Stroke Research, 2025)

Integration of bulked segregant analysis and transcriptome sequencing reveals an interaction network associated with cluster buds trait in Brassica napus - Libin Zhang; Xin Cheng; Dengyan Chen; Lina Zhang; Weiguo Zhao; Hongbo Chao; Yongtai Yin; Hao Wang; Maoteng Li (Theoretical and Applied Genetics, 2025)

Effect of rootstocks on growth potential, soil properties and rhizosphere microbiome of Vitis vinifera L. cv. Cabernet Sauvignon - Ning Shi; Xiao Han; Hao-Cheng Lu; Meng-Bo Tian; Ming-Yu Li; Fei He; Chang-Qing Duan; Ke-Ji Yu; Jun Wang (Plant and Soil, 2025)

Improvement in soil organic carbon turnover and microbial community niche differentiation with the addition of commercial organic fertilizers in wheat–green manure systems - Liyang Cheng; Hao He; Tao Min; Tong Luo; Junhua Li (Plant and Soil, 2025)

Research progress on electrochemiluminescence nanomaterials and their applications in biosensors - A review - Ming-Zhu Deng; Ming-Yu Zhong; Meng-Li Li; Gui-Qun Huang; Hao He; Xiao Xiao; Ruo-Bing Bai; Ruchika Hansanie Ukwatta; Li Mi; Ting-Ting Zhang; Yong-Hong Hu; Hui-Cheng Shi; et al. (Analytica Chimica Acta, 2025)

Eremothecium species from Cardiospermum halicacabum and Koelreuteria henryi, and their associated soapberry bugs - Cheng-Hsuan Li; Jie-Hao Ou; Chi-Yu Chen (Mycological Progress, 2025)

Intercropping enhances the reciprocal facilitation of N and P uptake through complementarity - Hao-Yue Qin; Cheng-Bao Wang; Ping Wang; Si-Cun Yang; Xiao-Fei Li; Long Li (Plant and Soil, 2025)

Modulation of SUMO1-TOP1 DNA damage repair by TOPORS following ovalbumin-induced oxidative stress in macrophages - Xulong Cai; Qiaolan Xu; Tongjin Yin; Xia Li; Yan Cheng; Xiangning Li; Chuangli Hao (Toxicology Letters, 2025)

A bionic yeast for the colon-targeted delivery of curcumin in the treatment of inflammatory bowel disease - Dunsheng Liang; Xiao-Fan Shen; Ting-Ting Li; Yao Deng; Hong-Liang Xiao; Zhi-Peng Li; Shuan-Cheng Bai; Xiao-Yu Ma; Xiao-ping Liao; Dong-Hao Zhao; Hao Ren; Chaoqun Zhang; et al. (Chemical Engineering Journal, 2025)

A versatile and double cross-linked hydrogel with potent antibacterial and immunomodulatory Zn@Met nanocomplexes for enhanced diabetic-infected wound healing - Tinglong Chen; Xueliang Zhang; Shengzhe Zhou; Dong Fang; Dinghao Luo; Zhaoyang Ran; Yingchun Liu; Cheng Xu; Jinhao Cao; Xiaodong Li; Yongqiaong Hao; Xiaoqing Wang; et al. (Chemical Engineering Journal, 2025)

Combinative dual-nanoparticle assembly improves oxygen-autarky PDT efficacy in hypoxic tumors - Shengyu Liu; Yi Wang; Sijia Yao; Qian Li; Chenkai Sun; Yishan Chen; Junqiu Ye; Weisong Li; Dong Wu; Jianping Zhou; Hao Cheng; Yang Ding (Chemical Engineering Journal, 2025)

Hierarchically amorphous cellulose acetate porous membranes with spectral selectivity for all-weather radiative cooling - Heyi Li; Chang Liu; Xinxin Yuan; Yue Ma; Chenbo Zhi; Hao Li; Yinghe Hu; Luyun Xue; Guang Yang; Xupin Zhuang; Bowen Cheng (Carbohydrate Polymers, 2025)

Terracing stabilizes and enhances soil organic carbon sequestration benefits of revegetation on the Loess Plateau, China - Hui Cheng; Hao Feng; Xiaoping Zhang; Zhiguang Li; Kaiyang Yu; Hongbin Ma; Jia Xu (CATENA, 2025)

Source characteristics and gas-particle partitioning of alkylated polycyclic aromatic hydrocarbons in coal combustion emissions - Cheng Yang; Fang Yin; Hao Wang; Xianbin Li; Penghao Su; Daolun Feng (Atmospheric Environment, 2025)

Unveiling Impact of Polyamide Microplastics on Ceftiofur Sodium Migration in Porous Media: Experimental and Modeling Insights - Yanna Chen; Ming Wu; Zhou Cheng; Yanru Hao; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu (Water, Air, & Soil Pollution, 2025)

Role of Dorsolateral Prefrontal Cortex During Motor Preparation on Anticipatory Postural Adjustments - Jiajia Yang; Guifang Zhang; Xiaoyu Gao; Xue Cheng; Zengming Hao; Jinjin Ma; Nanhe Lin; Ruochen Fu; Wai Leung; Ambrose Lo; Yan Li; Hao Xie; et al. (Brain Topography, 2025)

Glycerol monolaurate reduces lipid deposition and promotes the health of liver and intestine in grass carp fed with high-fat diet - Chi Wang; Pengju Li; Haibo Yu; Yunhe Li; Cheng Zhang; Xiaotian Zhang; Hao Li; Tian Li; Hong Ji (Animal Feed Science and Technology, 2025)

Hydrological connectivity creates additional cooling effects for urban wetland complexes - Wenwen Xie; Hao Yang; Peng Luo; Honglin Li; Shijun Zhang; Yu Huang; Yue Cheng; Ming Ni; Sujuan Wu; Haoyu Yang (Urban Climate, 2025)

UV-B stress reshapes root-associated microbial communities and networks, driven by host plant resistance - Chuanji Zhang; Na Gao; Xiaofan Na; Kaile Li; Meiyun Pu; Hao Sun; Yanfang Song; Tong Peng; Panshuai Fei; Junjie Li; Zhenyu Cheng; Xiaoqi He; et al. (Soil Biology and Biochemistry, 2025)

Optimized feeding schemes of heterotrophic anodic denitrification coupled with cathodic phosphate recovery from wastewater using a microbial fuel cell - Yuanyao Ye; Xueyi Yan; Yuanshou Jiang; Songlin Wang; Dongqi Liu; Yongzheng Ren; Daosheng Li; Huu Hao Ngo; Wenshan Guo; Dongle Cheng; Wei Jiang (Science of The Total Environment, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Structural response analysis of different submerged floating tunnel route selection conditions in the complex strait under the action of typhoon Sepat - Cheng Cui; Bo Huang; Minglin Chen; Wenlong Luo; Jianting Zhou; Hao Ding; Ke Li; Liang Cheng; Dan Zhong; Jiawei Zhou (Ocean Engineering, 2025)

In-situ geotechnical properties of abyssal sediments and implications for environmental impacts of polymetallic nodule mining - Zhenggang Li; Zhou Li; James R. Hein; Yangrui Cheng; Yuwei Liu; Shiquan Lin; Hao Wang; Xibin Han; Yanhui Dong; Fengyou Chu; Xiaohu Li (Marine Geology, 2025)

Suppression of NRF2 by photodynamic action to enhance bortezomib-triggered DNA damage for synergistic colorectal cancer therapy - Liu-Gen Li; Hao Chen; Ting-Ting Yu; Rui-Lin Liu; Cunqing Kong; Fan Leng; Rong-Cheng Xiao; Yao-Hua Lu; Ning Han; Jun Hu; Yuan-Jian Hui; Tong-Fei Li (Journal of Photochemistry and Photobiology B: Biology, 2025)

Physiological responses and adaptive mechanisms of the harmful algal bloom species Heterosigma akashiwo to naphthalene exposure - Dan Huang; Hao-Yun Zhang; Hua-Jun Wang; Hong-Jia Huang; Shuang Liu; Chu-Yi Qiu; Cai-Qin Cheng; Yun Huang; Zhaohe Luo; Wei-Dong Yang; Hong-Ye Li; Xiao-Fei Zheng; et al. (Journal of Hazardous Materials, 2025)

Phenol-driven ammonium recovery from coal chemical wastewater in a bioelectrochemical system (BES) - Ran Zeng; Li-Hui Yang; Si-Yuan Zhai; Cheng-Yan Liu; Na Lin; Qing-Hua Ou-Yang; Yan-Hua Xu; Ai-Jie Wang; Hao-Yi Cheng (Journal of Hazardous Materials, 2025)

Sensitive lateral flow immunoassay enabled by signal amplification strategy with high active oxidase-like nanozymes - Jie Zhu; Yunhui Cheng; Xufeng Wang; Hao Wu; Ye Jiao; Keyu Xing; Li Yao; Pei Jia; Zhou Xu (Food Bioscience, 2025)

Fate of myofibrillar protein-bound Nε-(carboxymethyl)lysine in the presence of the human colonic microbiota after gastrointestinal digestion - Shuqi Hao; Zeyu Lu; Mengyu Ye; Na Li; Jiayi Hu; Wei Quan; Jiwen Cheng; Huaide Xu; Mei Li (Food Bioscience, 2025)

Parametric study on hysteretic performance of separately-anchored self-centering concrete connections - Lu-Xi Li; Chao Li; Jin-Cheng Wu; Hong Hao (Engineering Structures, 2025)

Key role of recycled terrigenous sediments in generating continental arc magmatism in the West Qinling orogen, China - Li-Tao Ma; Li-Qun Dai; Hao Liang; Ye-Dan Hu; Qing-Cheng Yang; Zi-Fu Zhao; Guo-Chao Sun (Chemical Geology, 2025)

Abundant antecedent rainfall incubated a group-occurring debris flow event in the Dadu River Basin, Southwest China - Hao Li; Kaiheng Hu; Shuang Liu; Haiguang Cheng; Zhan Wen; Xiaopeng Zhang; Chao Ma; Manish Raj Gouli; Li Wei; Hongjuan Yang (Landslides, 2025)

ARHGAP17 Inhibits Hepatocellular Carcinoma Progression by Inactivation of Wnt/β-Catenin Signaling Pathway - Sirui Fan; Hongqing Zhao; Cheng Li; Xing Chen; Mingjie Sun; Fengyang Chen; Chao Long; Yinghui Zhou; Boyuan Nan; Hao Zhao; Wei Zhang (Biochemical Genetics, 2025)

Transcriptomic insights into methanol utilization in Pichia pastoris lacking AOX genes under co-feeding conditions - Xueyun Zheng; Zhifang Ye; Jiao Gao; Yuechuo Hao; Cheng Li; Hongsen Xie; Ying Lin; Shuli Liang (Archives of Microbiology, 2025)

Neutrophils: a new target for postoperative cognitive dysfunction - Jianxin Cheng; Jin Gao; Jianjun Li; Hao Tian (Apoptosis, 2025)

Recognition and classification techniques of marine mammal calls based on LSTM and expanded causal convolution - Wanlu Cheng; Hao Chen; Jiaming Jiang; Shuang Li; Jingjing Wang; Yanping Zhou (Frontiers in Marine Science, 2025)
Marine mammal calls play a vital role in navigation, localization, and communication. Effectively classifying these calls is essential for ecological monitoring, species conservation, and military biomimetic applications. However, traditional machine learning methods struggle to capture complex acoustic patterns, while most existing deep learning approaches rely solely on frequency-domain features and require large datasets, which limits their performance on small-scale marine mammal datasets. To address these challenges, we propose a hybrid architecture combining a time-attention Long Short-Term Memory (LSTM) network and a multi-scale dilated causal convolutional network. The model comprises three modules: (1) a frequency-domain feature extraction module employing dilated causal convolutions at multiple scales to capture multi-resolution spectral information from Mel spectrograms; (2) a time-domain feature extraction module that inputs Mel-frequency cepstral coefficients (MFCCs) into an LSTM enhanced with a time-attention mechanism to highlight key temporal features; and (3) a classification module leveraging transfer learning, where a pre-trained neural network is fine-tuned on real marine mammal call data to improve performance. Extensive experiments were conducted on vocalizations from four marine mammal species. Our proposed method outperformed existing baseline models across four evaluation metrics: accuracy, precision, recall, and F1 score, with improvements of 3%, 7%, 2%, and 4%, respectively. The results confirm the effectiveness of combining frequency- and time-domain features along with attention mechanisms and transfer learning. This hybrid approach enhances the accuracy and robustness of marine mammal call classification, especially under limited data conditions.

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Natural variations in the promoter of ZmDeSI2 encoding a deSUMOylating isopeptidase controls kernel methionine content in maize - Xin Lu; Yuhong Lei; Zhennan Xu; Zixiang Cheng; Meng Liu; Yuxin Tai; Xiaohua Han; Zhuanfang Hao; Mingshun Li; Degui Zhang; Hongjun Yong; Jienan Han; et al. (Molecular Plant, 2025)

Enhancing antibiotic removal in constructed wetlands: A MgFe-LDHs-based strategy for optimizing microbial communities and metabolic functions - Yu-Quan Zhong; Xiang-Long He; Yi-Hao Li; Hui Zhu; Jing-Wen Li; Hao Xu; Can Liu; Liang-Cheng Lin; Jun-Feng Wang (Journal of Hazardous Materials, 2025)

Improving XCO2 retrieval under high aerosol loads with fused satellite aerosol Data: Advancing understanding of anthropogenic emissions - Hao Zhu; Tianhai Cheng; Xingyu Li; Xiaotong Ye; Donghao Fan; Tao Tang; Haoran Tong; Lili Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Occurrence and enrichment mechanisms of helium in geothermal systems in continental China - Yinlei Hao; Yingchun Wang; Xingxing Kuang; Zhonghe Pang; Yiman Li; Yuqing Feng; Hui Zhou; Nianqing Li; Yuanzhi Cheng; Liwu Li; Lantian Xing; Qinghua Gong (Gondwana Research, 2025)

Relationship between starch granule-associated proteins and in vitro digestibility of buckwheat starches: From the perspective of gelatinization degree - Jin Du; Zhen Lu; Kai Cheng; Changfeng Li; Hao Wu; Bin Xu; Jian-Ya Qian (Food Chemistry, 2025)

The application of marine bioactive composite materials in environmental remediation - Yanan Huang; Hao Li; Ronglian Xing; Xiaorui Chen; Yuxin Sun; Meichen Tian; Ran Zhang; Xin Wang; Xinxin Wang; Rui Li; Lihong Chen; Hongxia Zhang; et al. (Desalination, 2025)

A lithium-poor tantalum oxychloride solid electrolyte for all-solid-state lithium batteries - Hao Cheng; Kangzhe Yu; Deli Xu; Guoxian Wu; Minghua Li; Sheng Wang; Baolong Shen; Jinyong Zhang; Xiao Huang; Bingbing Tian (Chemical Engineering Journal, 2025)

Lithospheric deformation and corresponding deep geodynamic process of the SE Tibetan Plateau - Zhangjun Li; Yang Wang; Lijun Liu; Zhigang Shao; Feng Cheng; Jinjiang Zhang; Weijun Gan; Ming Hao (Science China Earth Sciences, 2025)

A Highly Selective and Sensitive Turn-on Fluorescent Probe for Al3+ Detection: Properties and Applications - Xiao-Yu Li; Hang-Yu Xie; Neng Wan; Xiao-Dong Ning; Hao-Tong Li; Qing-Zhong Li; Yu-Guang Fan; Xin Qiao; Cheng-Zhi Xie (Journal of Fluorescence, 2025)

A Survey on the Design and Mechanical Analysis of Cryogenic Hoses for Offshore Liquid CO2 Ship-to-Ship Transfer - Hao Cheng; Fangqiu Li; Yufeng Bu; Yuanchao Yin; Hailong Lu; Houbin Mao; Xun Zhou; Zhaokuan Lu; Jun Yan (Journal of Marine Science and Engineering, 2025)
With the increasing severity of climate change, Carbon Capture, Utilization, and Storage (CCUS) technology has become essential for reducing atmospheric CO2. Marine carbon sequestration, which stores CO2 in seabed geological structures, offers advantages such as large storage capacity and high stability. Cryogenic hoses are critical for the ship-to-ship transfer of liquid CO2 from transportation vessels to offshore carbon sequestration platforms, but their design methods and mechanical analysis remain inadequately understood. This study reviews existing cryogenic hose designs, including reinforced corrugated hoses, vacuum-insulated hoses, and composite hoses, to assess their suitability for liquid CO2 transfer. Based on CO2’s physicochemical properties, a conceptual composite hose structure is proposed, featuring a double-spring-supported internal composite hose, thermal insulation layer, and outer sheath. Practical recommendations for material selection, corrosion prevention, and monitoring strategies are provided to improve flexibility, pressure resistance, and thermal insulation, enabling reliable long-distance tandem transfer. A mechanical analysis framework is developed to evaluate structural performance under conditions including mechanical loads, thermal stress, and dynamic responses. This manuscript includes an introduction to the background, the methodology for data collection, a review of existing designs, an analysis of CO2 characteristics, the proposed design methods, the mechanical analysis framework, a discussion of challenges, and the conclusions.

Mycoplasma ovipnuemoniae impairs the immune response of sheep and suppresses neutrophil function by inhibiting S100A9 - Chenbo Yan; Tianning Dong; Yiyi Shan; Bingru Zhao; Hua Yang; Yu Cai; Shanglai Li; Qiuyue Liu; Yuefeng Chu; Huafang Hao; Zilong Cheng; Maojun Liu; et al. (Veterinary Microbiology, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Mantle metasomatism by subducted Indian continental crust: Evidence from post-collisional basaltic ultrapotassic rocks in southern Tibetan plateau - Miao-Yan Zhang; Lu-Lu Hao; Yue Qi; Qiang Wang; Andrew C. Kerr; Lin Ma; Cheng-Cheng Huang; Gang-Jian Wei; Jie Li; Jin-Long Ma; Qi-Wei Li; Zi-Long Wang; et al. (Lithos, 2025)

Polarity and fluorescent fractions of manure dissolved organic matter could affect differently the adsorption and desorption of antibiotics in soils - Jin-Sheng Hu; Hui-Yun Xiao; Xiang-Yu Tang; Hao Yan; Zhuo Chen; Jian-Hua Cheng; Xiao-Yu Li (Journal of Environmental Management, 2025)

Quantitative analysis of β-carotene and unsaturated fatty acids in blended olive oil via Raman spectroscopy combined with model prediction - Yulong Chen; Zhihan Yang; Shan Zeng; Hui Tian; QingZhou Cheng; Site Lv; Hao Li (Food Chemistry, 2025)

A remotely triggered phase change hydrogel dressing for controlled release and promoting healing of infected wounds - Xiaolong Hu; Hongyan Zhang; Zuan-Tao Lin; Yu Chen; Hao Cheng; Bi-Huan Zhong; Yongli Li; Xiao-Ping Liao; Jian Sun; Mei X. Wu; Gang-Biao Jiang (Chemical Engineering Journal, 2025)

2-Mercapto-1,3,4-thiadiazole-functionalized gold nanoclusters as a comparable bactericidal nanoantibiotic to vancomycin in treating methicillin-resistant Staphylococcus aureus infections - Quan-Quan Zhuang; Jia-Xin Ma; Yi-Ming Zheng; Lin-Yan Lu; Jia-Lin Yang; Qing-Qing Chen; Xiao-Li Yan; Yan-Cheng Jiang; Hao-Hua Deng; Wei Chen; Gang Liu (Chemical Engineering Journal, 2025)

Dextran from human feces-derived Weissella cibaria facilitates intestinal mucosal barrier function by modulating gut bacteria and propionate levels - Huan Zhao; Sakandar Abbas; Jing Ren; Haibin Huang; Ying Song; Xiaoning Su; Qiuyang Wu; Yane Ma; Hao Tang; Yi-Zhou Gao; Yuanzhe Li; Xiaoming Gu; et al. (Carbohydrate Polymers, 2025)

Identification of elite alleles associated with glume-opening angle in rice natural population - Yingying Zhao; Hui Jiang; Chunyu Jing; Tianhu Li; Yanan Zhang; Zhengbo Liu; Yinping Chang; Mingyu Du; Hao Sun; Jinghan Sun; Yang Ang; Xianping Cheng; et al. (Euphytica, 2025)

Pharmacologically activating BDNF/TrkB signaling exerted rapid-acting antidepressant-like effects through improving synaptic plasticity and neuroinflammation - Si-Rui Sun; Jia-Ning Zhao; Peng-Wei Bi; Hui-Ying Zhang; Guang-Xiang Li; Jiao-Zhao Yan; Yun-Feng Li; Yong-Yu Yin; Hao Cheng (Metabolic Brain Disease, 2025)

Regional abnormalities of white and gray matter in youths with conduct problems - Man Dong; Xiaodong Cheng; Yage Li; Shanling Ji; Hao Yu; Liangliang Ping; Chuanxin Liu; Cong Zhou (Brain Imaging and Behavior, 2025)

Corrigendum to Impact of satellite AOD data on top-down estimation of biomass burning particulate matter emission [Sci. Total Environ. 864 (2023)/161055] - Xiaotong Ye; Tianhai Cheng; Xiaoyang Li; Hao Zhu (Science of The Total Environment, 2025)

Age constraints on the Ediacaran carbonate carbon isotope excursions in the Tarim Block: Evidence from in situ U–Pb dating of dolostone - Wen-Wu Huang; Liang-Liang Zhang; Di-Cheng Zhu; Li Liu; Xiao-Wei Li; Jin-Cheng Xie; Qing Wang; Hao-Yin Chi (Precambrian Research, 2025)

Sex-specific effects of triphenyltin on gut microbiota and intergenerational effects in marine medaka (Oryzias melastigma) - Ping Li; Bian-Hao Zeng; Shu-Wen He; Bin Liu; Cheng-Zhuang Chen; Jian-Xue Feng; Ling Liu; Zhi-Hua Li (Journal of Hazardous Materials, 2025)

Implications of China's foreign waste ban on the global waste paper trade networks for circular economy and sustainability - Xinfei Li; Chang Yu; Zhaohua Wang; Chenlu Tao; Hao Li; Gang Diao; Baodong Cheng (Forest Policy and Economics, 2025)

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

Core-shell hydrogel microspheres with sequential delivery of cerium oxide nanoparticles and spinal white matter extracellular matrix for improved functional recovery in spinal cord injury - Yixiang Ai; Chunping Hu; Yifan Wang; Youjun Liu; Renfeng Liu; Hailiang Xu; Hui Li; Yuqi Zhao; Yuhao Wang; Ruojie Ning; Cheng Ju; Weidong Wu; et al. (Chemical Engineering Journal, 2025)

Polyphenolic compounds mitigate the oxidative damage of anammox sludge under long-term light irradiation - Zhi-Qi Ren; Rong-Rong Chang; Hao Wang; Gui-Feng Li; Bao-Cheng Huang; Ren-Cun Jin (Bioresource Technology, 2025)

A wild-allele GsPP2C-51-a1 enhances tolerance to drought stress in soybean and Arabidopsis - Cheng Liu; Xianlian Chen; Wei Han; Xiaoshuai Hao; Liang Qin; Wei Luo; Lizhi Zhao; Ning Li; Lei Sun; Jiaoping Zhang; Guangnan Xing; Jianbo He; et al. (Theoretical and Applied Genetics, 2025)

High-temperature treated oil-rich bedded rock layer and deterioration mechanism of heat transfer performance - Yanjun Shen; Ziyi Li; Cheng Peng; Jianshuai Hao (Bulletin of Engineering Geology and the Environment, 2025)

Altered resting-state functional connectivity of amygdala subregions in adults with subthreshold depression after aerobic exercise - Yihe Wang; Mengqi Zhao; Qin Li; Zeqi Hao; Jiaxi Zhang; Lina Huang; Qingguo Ding; Zhixiang Cheng; Jianxin Zhang; Huayun Li; Xize Jia (Brain Imaging and Behavior, 2025)

Bivariate Spatial Autocorrelation Analysis of Keshan Disease and Hair Selenium of Residents in Heilongjiang Province, China - Jiacheng Li; Guijin Li; Cheng Wang; Huixin Sun; Linlin Du; Shuxiu Hao; Qingyu Zeng; Cunqi Lv; Yu Zhang; Xinshu Wang; Zhifeng Xing; Tong Wang (Biological Trace Element Research, 2025)

Spatial Clusters of Low Serum Selenium: the Priorities of Selenium Supplementation to Residents of Keshan Disease Endemic Areas - Qingyu Zeng; Guijin Li; Ruixiang Wang; Cunqi Lv; Shuxiu Hao; Jiacheng Li; Huixin Sun; Linlin Du; Cheng Wang; Yu Zhang; Xinshu Wang; Yuehui Jia; et al. (Biological Trace Element Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Facile access to spirobifluorene-fused chiral multi-resonance materials with ultra-narrowband blue emission - Hu Cheng; Chen-Hao Guo; Meng Li; Yusong Guo; Zhangyi Fu; Junjie Liu; Yudong Yang; Jingbo Lan; Zhengyang Bin (Science Bulletin, 2025)

In vivo self-assembled bispecific fluorescence probe for early detection of bladder cancer and metastasis - Da-Yong Hou; Ni-Yuan Zhang; Peng Zhang; Xiang-Peng Li; Jiong-Cheng Wu; Mei-Yu Lv; Zhi-Jia Wang; Xing-Jie Hu; Jian-Xiao Liang; Hong-Lei Wang; Yue-Ze Wang; Hui-Hui You; et al. (Science Bulletin, 2025)

Efficient antibiotics removal by pig manure-based magnetic biochar-driven catalytic degradation - Yudong Li; Jian Zhang; Xiaoqing Liu; Huaqing Liu; Lei Wang; Dongle Cheng; Yanlong Wang; Wenshan Guo; Huu Hao Ngo (Journal of Water Process Engineering, 2025)

Triptolide exposure triggers ovarian inflammation by activating cGAS-STING pathway and decrease oocyte quality in mouse - Si-Yao Cheng; Yi-Fan Yang; Ya-Long Wang; Zhao-Ping Yue; Yan-Zhu Chen; Wen-Ke Wang; Zhi-Ran Xu; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Chang-Long Xu; Yu Liu (Food and Chemical Toxicology, 2025)

Single-cell transcriptome sequencing analysis of physiological and immune profiling of crucian carp (Carassius auratus) gills - Zhi-Guang Hou; Meng-Chao Xing; Jia-Xing Luo; Yi-Huan Xu; Li-Han Zhang; Xiao-Wei Gao; Jiang-Jiang Wang; Fazhan Hanafiah; Waiho Khor; Xin Hao; Xin Zhao; Cheng-Bin Wu (Fish & Shellfish Immunology, 2025)

Corrigendum to “Application of Mo2C for enhancement of co-catalytic performance of Fe3+/PS based fenton-like reaction in degrading tetracycline hydrochloride” [Chem. Eng. J. 474 (2023) 145508] - Hao Cheng; Yi Wen; Chao Huang; Ping Wang; Chengyou Sun; Chongling Feng; Jialu Xu; Li Du; Ting Yan; Min Cheng (Chemical Engineering Journal, 2025)

Construction of a Cas9-targeted mutagenesis mini-library in the upland cotton genetic standard line (TM-1) - Yunfei Hao; Jiajia Feng; Yuanyuan Li; Zhangcheng Yuan; Pengfei Miao; Hailiang Cheng; Qiaolian Wang; Youping Zhang; Limin Lv; Dongyun Zuo; Ji Liu; Guoli Song (Plant Cell Reports, 2025)

The impact of ESG performance on corporate digital transformation - Yu Cheng; Hao Li (Environment, Development and Sustainability, 2025)

Changes of Yancheng coastline near 20 years based on remote sensing technology - Yu Song; Shuang Yang; Dongxu Li; Yubao Shao; Jie Cheng; Xingxing Shan; Li Cao; Silong Li; Chao Xie; Li Shan; Delong Tian; Hao Wang; et al. (Marine Georesources & Geotechnology, 2025)

Challenges of quaternary ammonium antimicrobial agents: Mechanisms, resistance, persistence and impacts on the microecology - Jiaxin Zhang; Lei Cheng; Hao Li; Xi Chen; Lin Zhang; Tiantian Shan; Jiannan Wang; Ding Chen; Jiawei Shen; Xinxuan Zhou; Lichen Gou; Lixin Zhang; et al. (Science of The Total Environment, 2025)

Fungal bioaugmentation enhanced herbicide removal via soil microbial fuel cell: Taking Myrothecium verrucaria and haloxyfop-P as an example - Da-Cheng Hao; Fan Wang; Chengxun Li; Yaoxuan Wang; Jiayi Xue; Pei-Gen Xiao (Science of The Total Environment, 2025)

A forecasting tool for optimized emission control strategies to achieve short-term air quality attainment - Zhaoxin Dong; Shuxiao Wang; Yueqi Jiang; Jia Xing; Dian Ding; Fenfen Zhang; Dejia Yin; Qian Song; Jingyu An; Hongli Wang; Cheng Huang; Qian Wang; et al. (Journal of Environmental Management, 2025)

Modeling tree radial growth with competition and crown characteristics from an aerial perspective - Xin Liu; Fengri Li; Yuanshuo Hao; Xinyang Zou; Shoumin Cheng; Lihu Dong (Forest Ecology and Management, 2025)

Pattern recognition of multiple metal ions using fluorescent Perylenyl nanoaggregates and application in food traceability - Tianyue Liu; Yining Li; He Cheng; Ruixuan An; Xinglin Hou; Yasong Zhang; Jieyu Zhao; Hao Zhang; Jingsheng Tian; Zhiyi Yao (Food Chemistry, 2025)

Study on interfacial regulation in real food system: Cellulase-induced steady-state reconstruction of flaxseed-based plant milk and its molecular mechanisms - Qian Hao; Ziyu Deng; Ruyi Li; Yuanmeng Cheng; Yaqiong Pei; Bin Zhou; Yashu Chen; Qianchun Deng (Food Hydrocolloids, 2025)

Variation in microbial communities and network ecological clusters driven by soil organic carbon in an inshore saline soil amended with hydrochar in Yellow River Delta, China - Hui Yao; Yadong Cheng; Qingxian Kong; Xiao Wang; Ziguo Rong; Yue Quan; Xiangwei You; Hao Zheng; Yiqiang Li (Environmental Research, 2025)

Trace alkali-assisted exfoliation of silk fibers into liquid crystalline mesogens: Phase behaviors and structural manipulation - Yongfeng Wang; Qingqing Cheng; Yiyao Chen; Lianhui Li; Shuqi Wang; Mingming Hao; Pei-Xi Wang; Ting Zhang (Chemical Engineering Journal, 2025)

A hydro-stable and phase-transition-free P2-type cathode with superior cycling stability for high-voltage sodium-ion batteries - Jun Xiao; Hong Gao; Yang Xiao; Shijian Wang; Cheng Gong; Zefu Huang; Bing Sun; Chung-Li Dong; Xin Guo; Hao Liu; Guoxiu Wang (Chemical Engineering Journal, 2025)

PbI2 intercalation and residual elimination strategy for sequential inverted perovskite solar cells - Zhuowei Du; Zhu Ma; Tangjie Yu; Zhangfeng Huang; Shanyue Hou; Qianyu Liu; Yanlin Li; Yi Chen; Qiang Yang; Wei You; Junbo Yang; Hao Du; et al. (Chemical Engineering Journal, 2025)

Interfacial built-in electric field in 2D Ni(OH)2 heterojunction with the sodium organic compound for enhanced oxygen evolution catalysis - Jiao Zhou; Mingyuan Zhang; Baiyu Ren; Qian Yi; Hao Yu; Baoyue Zhang; Ang Li; Xinyi Hu; Zhong Li; Guanyu Chen; Yinfen Cheng; Rui Gao; et al. (Chemical Engineering Journal, 2025)

Correlation analysis of starch molecular structure and film properties via rearrangements of glycosidic linkages by 1,4-α-glucan branching enzyme - Yilin Dong; Zhaofeng Li; Haocun Kong; Xiaofeng Ban; Zhengbiao Gu; Hao Zhang; Yan Hong; Li Cheng; Caiming Li (Carbohydrate Polymers, 2025)

RO4929097 inhibits NICD3 to alleviate pulmonary hypertension via blocking Notch3/HIF-2α/FoxM1 signaling pathway - Hao Zhu; Cheng Li; Fang Hu; Lifu Wu; Ling Wu; Meihua Zhou; Wei Liu; Aiguo Dai (In Vitro Cellular & Developmental Biology - Animal, 2025)

Automatic and integrated detection of nucleic acid by using a dual-mode thermal controlled digital microfluidic chip - Jiaqi Liao; Chonghao Li; Jiajia Liu; Hao Cheng; Linmin Li; Guixi Tang; Ru Huang; Yating Lu; Siyue Chen; Qian Zhang; Hao Chen; Qinyuan Chen; et al. (Analytica Chimica Acta, 2025)

Potentially toxic elements in surface sediments of the Beibu Gulf, South Sea, China: Occurrence, bioavailability and probabilistic risk assessment - Qiongyuan Su; Yanan Cheng; Liangliang Huang; Shuwen Zhao; Jie Ma; Shijie Song; Nan Li; Hao Xu; Caiguang Wang (Marine Pollution Bulletin, 2024)

Time-arrival pickup method of tunnel water inrush microseismic signals based on kurtosis value and AIC method - Hao Jin; Liping Li; Shuai Cheng; Xingyuan Li (Tunnelling and Underground Space Technology, 2024)

Enhancing the overturning resistance capacity of high aspect ratio structure through hybrid base isolation and inter-storey isolation - Jingcai Zhang; Yingna Li; Hao Yang; Xin Ji; Lingxi Gu; Wangjingyi Li; Bo Wang; Liang Cheng; Chunwei Zhang (Soil Dynamics and Earthquake Engineering, 2024)

Spatial-temporal heterogeneity of sustainable development goals and their interactions and linkages in the Eurasian continent - Qian Liu; Fujia Li; Suocheng Dong; Hao Cheng; Longwu Liang; Bing Xia (Sustainable Production and Consumption, 2024)

Polystyrene microplastics alleviate the developmental toxicity of silver nanoparticles in embryo-larval zebrafish (Danio rerio) at the transcriptomic level - Qiao-hong Xiao; Hao Xiang; Ya-nan Tian; Jiao-long Huang; Ming-qun Li; Pu-qing Wang; Kai Lian; Peng-xia Yu; Meng-yao Xu; Ruo-nan Zhang; Yan Zhang; Jie Huang; et al. (Science of The Total Environment, 2024)

Specialized metabolites of the endophyte Annulohypoxylon areolatum hosted by Aconitum carmichaelii - Cheng-Yao Wang; Dong Gan; Yan Shu; Rui-Feng Mei; Jia-Qi Liu; Chen-Zhe Li; Lan Cai; Sheng-Qi Zhang; Li Zhu; Hao Zhou; Le Cai; Zhong-Tao Ding (Phytochemistry, 2024)

Assessing the discrepant role of anions in the transformation of reactive oxygen species in H2O2 and PDS system: A comparative kinetic analysis - Ling Li; Min Cheng; Hao Sun; Huan Yi; Shiyu Liu; Mingming Zhang; Yukui Fu; Xuerong Zhou; Fuhang Xu; Dengsheng Ma; Guangming Zeng; Zhengjian Yang; et al. (Journal of Hazardous Materials, 2024)

Rapid bromate determination using short-column ion chromatography-mass spectrometry: Application to bromate quantification during ozonation - Shi Cheng; Haolin Liu; Yanting Zuo; Feng Zhu; Huaicheng Zhang; Hao Zhang; Shouqiang Huang; Wentao Li; Zongli Huo; Aimin Li (Journal of Environmental Chemical Engineering, 2024)

Comprehensive review of plant-derived anti-hyperlipidemia peptides: Production, anti-hyperlipidemia mechanism, and structure-activity relationship study - Liuyi Wei; Hao Wu; Xufeng Wang; Li Wen; Bo Cui; Yunhui Cheng (Food Chemistry, 2024)

A study on the structure-functionality relationship of Solenaia oleivora protein under high-intensity ultrasonication processing - Wanwen Chen; Wu Jin; Xueyan Ma; Haibo Wen; Yanping Li; Gangchun Xu; Pao Xu; Hao Cheng (Food Chemistry, 2024)

Structural characterization of oligosaccharide from Dendrobium officinale and its properties in vitro digestion and fecal fermentation - Hao Cheng; Lei Xu; Hua Zhu; Tingting Bu; Zhenhao Li; Shuna Zhao; Kai Yang; Peilong Sun; Ming Cai (Food Chemistry, 2024)

Volatilomics of Cabernet Sauvignon grapes and sensory perception of wines are affected by canopy side in vineyards with different row orientations - Hao-Cheng Lu; Meng-Bo Tian; Ning Shi; Hui-Qing Li; Ming-Yu Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Andrea Schubert; Jun Wang (Food Chemistry, 2024)

Exceptional heatwaves and mortality in Europe: Greater impacts since the coronavirus disease 2019 outbreak - Zhiwei Li; Yinguang Fan; Zhiwei Xu; Hung Chak Ho; Shilu Tong; Cunrui Huang; Zhongliang Bai; Yiming Gai; Wenjun Cheng; Jihong Hu; Yufan Feng; Hao Zheng; et al. (Environmental Pollution, 2024)

Towards wearable multifunctional cellulose nanofiber/silver nanowire/graphene oxide film: Electromagnetic protection, antibacterial, and motion monitoring - Zheng Wang; Shi-Bo Li; Xiao Yang; Hao Wang; Li-Jing Xie; Ze-Chao Tao; Qing-Qiang Kong; Shou-Chun Zhang; Hui Jia; Dong Jiang; Cheng-Meng Chen (Chemical Engineering Journal, 2024)

Magnetic nanochain-induced anisotropic nerve assembly for spinal cord injury repair - Yangnan Hu; Hao Wei; Hui Zhang; Hong Cheng; Dongyu Xu; Huan Wang; Zeyou Zhang; Bin Zhang; Yixian Liu; Yusong Wang; Chen Zhang; Jilai Li; et al. (Chemical Engineering Journal, 2024)

Porous and high specific surface area carbon material derived from ginkgo leaves for high-performance symmetric supercapacitors - Lihua Zhang; Xiaoyang Cheng; Lingyan Li; Xinran Li; Hao Wu; Jinfeng Zheng; Jiarong Yao; Guifang Li (Biomass and Bioenergy, 2024)

Signature and function of plasma exosome-derived circular RNAs in patients with hypertensive intracerebral hemorrhage - Kejie Chen; Xiaoyuan Cheng; Shanshan Yuan; Yang Sun; Junli Hao; Quandan Tan; Yapeng Lin; Shuping Li; Jie Yang (Molecular Genetics and Genomics, 2024)

Dedolomitization arises the knife-like structure of dolostone: insights from the oolitic dolostone of Cambrian Zhangxia formation, North China Craton - Zhe-Xin Cai; Shan-Shan Li; Yi-Ning He; Tao Cui; Xin-Yu Wu; Hao-Cheng Yu; Zhao-Liang Hou; Yu-Tian Tao; Da Wang; Kun-Feng Qiu (Carbonates and Evaporites, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Reduction of tobacco alkaloid bioaccumulation in pea shoots: A comparative study of biochar derived from cow dung and maize straw - Yadong Cheng; Yuxiang Bai; Hui Yao; Xiao Wang; Yuan Yuan; Xiaojian He; Shibao Lv; Xiangwei You; Hao Zheng; Yiqiang Li (Chemosphere, 2024)

Comparing evaporation from water balance framework and multiple models on a global scale - Jinghua Xiong; Abhishek; Chong Zhang; Li Xu; Hrishikesh A. Chandanpurkar; James S. Famiglietti; Pat J.-F. Yeh; Zhongbo Yu; Ningpeng Dong; Haoran Hao; Shuang Yi; Lei Cheng; et al. (Journal of Hydrology, 2024)

Maintaining KEAP1 levels in retinal pigment epithelial cells preserves their viability during prolonged exposure to artificial blue light - Ching-Hao Li; Tsung-Min Yang; Ida Fitriana; Te-Chao Fang; Liang-Huan Wu; George Hsiao; Yu-Wen Cheng (Journal of Photochemistry and Photobiology B: Biology, 2024)

A novel cascade catalysis for one-pot enzymatically modified isoquercitrin (EMIQ) conversion from rutin and sucrose using rationally designed gradient temperature control - Yu-Fan Zhan; Zhuo-Hao Meng; Cheng-Hai Yan; Min Tan; Marriam Khurshid; Yi-Jiangcheng Li; Shao-Jun Zheng; Jun Wang (Food Chemistry, 2024)

Fabrication, characterization, and bioactivity of self-assembled carrier-free colloidal dispersions from Citrus × Limon ‘Rosso’ essential oil and tea polyphenols - Fangying Cheng; Mianhong Chen; Zhihao Duan; Ying Zou; Yunxia He; Fanke Zeng; Yuan Yuan; Tiaokun Fu; Hao Tu; Ruyi Li; Jihua Li; Wei Zhou (Food Chemistry, 2024)

Acrolein exposure affects ovarian function by interfering with glycolysis and mitochondrial energy metabolism in mouse - Yan-Zhu Chen; Wen-Ke Wang; Yi-Fan Yang; Si-Yao Cheng; Lin-Feng Li; Hao Shen; Zhi-Min Qi; Yu Liu (Environmental Pollution, 2024)

Electronic structure modulation of yttrium sites with heteroanions coordination enhances the bidirectional catalytic performance of lithium-sulfur batteries - Yongbing Jin; Nanping Deng; Geng Li; Hao Wang; Daxue Hao; Yayi Lu; Shuming Zeng; Bowen Cheng; Weimin Kang (Chemical Engineering Journal, 2024)

Conjugation-regulated lateral and stereoelectronic effects in single-molecule junctions - Xiao Wei; Xuanhao Cao; Jie Hao; Xinyue Chang; Ping Duan; Li Cheng; Keqiu Chen; Jinying Wang; Chuancheng Jia; Xuefeng Guo (Chemical Engineering Journal, 2024)

Pagoda solar evaporators with an alternating hot-cold pattern for rapid, scaling-free desalination of hypersaline brines - Zhenwei Wu; Kai Li; Ran Deng; Yu-Ren Xue; Hao-Nan Li; Hao-Cheng Yang; Zhi-Kang Xu (Chemical Engineering Journal, 2024)

Asymmetric structural strategy enables efficient MR-TADF emitters with low efficiency roll-off and doping-concentration insensitivity - Zhang-Li Cheng; Jie Li; Hui Wang; Feng Huang; Ying-Chun Cheng; Hao Wu; Xin Xiong; Tong-Yuan Zhang; Jia Yu; Jun Ye; Kai Wang; Xiao-Hong Zhang (Chemical Engineering Journal, 2024)

Reconciled estimation of Antarctic ice sheet mass balance and contribution to global sea level change from 1996 to 2021 - Rongxing Li; Guojun Li; Gang Hai; Huan Xie; Yuan Cheng; Wei Chen; Xiangbin Cui; Minghu Ding; Chunchun Gao; Tong Hao; Changqing Ke; Chuanjin Li; et al. (Science China Earth Sciences, 2024)
The Antarctic Ice Sheet (AIS) has been losing ice mass and contributing to global sea level rise (GSLR). Given its mass that is enough to cause ∼58 m of GSLR, accurate estimation of mass balance trend is critical for AIS mass loss monitoring and sea level rise forecasting. Here, we present an improved approach to reconciled solutions of mass balance in AIS and its regions from multiple contributing solutions using the input-out, altimetric, and gravimetric methods. In comparison to previous methods, such as IMBIE 2018, this approach utilizes an adaptive data aggregation window to handle the heterogeneity of the contributing solutions, including the number of solutions, temporal distributions, uncertainties, and estimation techniques. We improved the regression-based method by using a two-step procedure that establishes ensembled solutions within each method (input-output, altimetry, or gravimetry) and then estimates the method-independent reconciled solutions. For the first time, 16 contributing solutions from 8 Chinese institutions are used to estimate the reconciled mass balance of AIS and its regions from 1996 to 2021. Our results show that AIS has lost a total ice mass of ∼3213±253 Gt during the period, an equivalent of ∼8.9±0.7 mm of GSLR. There is a sustained mass loss acceleration since 2006, from 88.1±3.6 Gt yr −1 during 1996–2005 to 130.7±8.4 Gt yr −1 during 2006–2013 and further to 157.0±9.0 Gt yr −1 during 2014–2021. The mass loss signal in the West Antarctica and Antarctic Peninsula is dominant and clearly presented in the reconciled estimation and contributing solutions, regardless of estimation methods used and fluctuation of surface mass balance. Uncertainty and challenges remain in mass balance estimation in East Antarctica. This reconciled estimation approach can be extended and applied for improved mass balance estimation in the Greenland Ice Sheet and mountain glacier regions.

Amentoflavone alleviated cartilage injury and inflammatory response of knee osteoarthritis through PTGS2 - Yiheng Cheng; Xiaofeng Liu; Wenqing Qu; Xin Wang; Hao Su; Wenliang Li; Wenqiang Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Effect of elemental composition and phase transformation on lithium leaching behavior of micas in calcination-acid leaching process - Kesheng Zuo; Xuanping Zhou; Hao Wang; Zhihang Li; Kun Xiong; Hongfei Cheng (Applied Clay Science, 2024)

Reveal persistent haze pollution episodes in hefei: a perspective from ground-based and satellite observation - Zhiyuan Fang; Hao Yang; Cheng Li; Zhiqiang Kuang; Xiang Xu; Heng Jin (Air Quality, Atmosphere & Health, 2024)

Enhancing the nitrogen removal of anammox sludge by setting up novel redox mediators-mediated anammox process - Huahua Li; Hua Chen; Xinyuan He; Yi Lu; Haichun Gao; Hao Song; Shaoan Cheng (Chemosphere, 2024)

Unified scheme design and control optimization of flapping wing for next-generation manta ray robot - Qi-meng Liu; Hao Chen; Peng-ming Guo; Guang-sheng Su; Wei-kun Li; Xin-yu Zeng; Di-xia Fan; Wei-cheng Cui (Ocean Engineering, 2024)

Ecological risk assessment of castor oil based waterborne polyurethane: Mechanism of anionic/cationic state selective toxicity to Eisenia fetida - Ruiquan Hou; Hao Wu; Pengrui Du; Shengnan Li; Jun Liu; Jinzhe Chang; Suqing Huang; Dongmei Cheng; Peiwen Zhang; Zhixiang Zhang (Journal of Hazardous Materials, 2024)

Multi-scenario application of chitosan emulsions as fat replacers: Based on the regulation of chitosan hydrophobicity and emulsion rheological properties - Cheng-Zhen Nie; Yao Li; Xu-Hui Huang; Hao-Peng Wang; Xu-Song Wang; Xiu-Ping Dong; Bei-Wei Zhu; Lei Qin (Food Hydrocolloids, 2024)

Impact of diatomit on the transport behavior of unmodified and carboxyl-modified nanoplastics in saturated porous media - Yuheng Wu; Ming Wu; Zhou Cheng; Yanru Hao; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu; Guoping Lu (Environmental Pollution, 2024)

Multifunctional pH-responsive hydrogel dressings based on carboxymethyl chitosan: Synthesis, characterization fostering the wound healing - Mingxin Xiong; Yu Chen; Han-Jian Hu; Hao Cheng; Wei-Xiong Li; Shipeng Tang; Xiaolong Hu; Ling-Min Lan; Hongyan Zhang; Gang-Biao Jiang (Carbohydrate Polymers, 2024)

Development of wheat-tetraploid Thinopyrum elongatum 4EL small fragment translocation lines with stripe rust resistance gene Yr4EL - Biran Gong; Jing Gao; Yangqiu Xie; Hao Zhang; Wei Zhu; Lili Xu; Yiran Cheng; Yi Wang; Jian Zeng; Xing Fan; Lina Sha; Haiqin Zhang; et al. (Theoretical and Applied Genetics, 2024)

Correction to: Deletion of Luzp2 Does Not Cause Hearing Loss in Mice - Cheng Cheng; Guangjie Zhu; Kaijian Wang; Chuan Bu; Siyu Li; Yue Qiu; Jie Lu; Xinya Ji; Wenli Hao; Junguo Wang; Chengwen Zhu; Ye Yang; et al. (Neuroscience Bulletin, 2024)

Deletion of Luzp2 Does Not Cause Hearing Loss in Mice - Cheng Cheng; Guangjie Zhu; Kaijian Wang; Chuan Bu; Siyu Li; Yue Qiu; Jie Lu; Xinya Ji; Wenli Hao; Junguo Wang; Chengwen Zhu; Ye Yang; et al. (Neuroscience Bulletin, 2024)

A Theoretical Investigation of Coal Fracture Evolution with Hydrostatic Pressure and its Validation by CT - Changxin Zhao; Yuanping Cheng; Wei Li; Liang Wang; Zhuang Lu; Hao Wang (Natural Resources Research, 2024)

Changes in immune subsets during chemotherapy as prognosis biomarkers for multiple myeloma patients by longitudinal monitoring - Pengcheng Xu; Ying Li; Xibing Zhuang; Lei Yue; Yanna Ma; Wenjin Xue; Lili Ji; Yanxia Zhan; Yang Ou; Tiankui Qiao; Duojiao Wu; Peng Liu; et al. (Immunologic Research, 2024)

Disulfidptosis: A new type of cell death - Fei Xiao; Hui-Li Li; Bei Yang; Hao Che; Fei Xu; Gang Li; Cheng-Hui Zhou; Sheng Wang (Apoptosis, 2024)
Disulfidptosis is a novel form of cell death that is distinguishable from established programmed cell death pathways such as apoptosis, pyroptosis, autophagy, ferroptosis, and oxeiptosis. This process is characterized by the rapid depletion of nicotinamide adenine dinucleotide phosphate (NADPH) in cells and high expression of solute carrier family 7 member 11 (SLC7A11) during glucose starvation, resulting in abnormal cystine accumulation, which subsequently induces andabnormal disulfide bond formation in actin cytoskeleton proteins, culminating in actin network collapse and disulfidptosis. This review aimed to summarize the underlying mechanisms, influencing factors, comparisons with traditional cell death pathways, associations with related diseases, application prospects, and future research directions related to disulfidptosis.

Associations between exposure to brominated flame retardants and periodontitis in U.S. adults - Jia-jie Lv; Shu-yue Li; Xiang-meng Kong; Yan Zhao; Xin-yu Li; Hong Guo; Chu Feng; Cheng-hao Yang (Chemosphere, 2024)

Legacy and alternative perfluoroalkyl acids in the Yellow River on the Qinghai-Tibet Plateau: Levels, spatiotemporal characteristics, and multimedia transport processes - Wu Wen; Lijuan Gao; Hao Cheng; Lu Xiao; Shangwei Zhang; Siling Li; Xiaoman Jiang; Xinghui Xia (Water Research, 2024)

Alleviation of RO membrane fouling in wastewater reclamation plants using an enhanced acid-base chemical cleaning method - Li Zihao; Jinlong Wang; Lihua Cheng; Qiang Yang; Peizhuo Li; Xiaowan Dong; Boyan Xu; Mei Zhi; Anni Hao; How yong Ng; Xuejun Bi (Water Research, 2024)

Controllable preparation of graphene glass fiber fabric towards mass production and its application in self-adaptive thermal management - Ruojuan Liu; Fan Yang; Shuting Cheng; Xianghe Yue; Fushun Liang; Wenjuan Li; Jingnan Wang; Qinchi Zhang; Liangyu Zou; Hao Yuan; Yuyao Yang; Kangyi Zheng; et al. (Science Bulletin, 2024)

Bamboo vinegar regulates the phytoremediation efficiency of Perilla frutescens (L.) Britt. by reducing membrane lipid damage and increasing cadmium retention - Zhenguo Li; Xingyu Hao; Tianlian He; Ying Chen; Mingwei Yang; Cheng Rong; Chengzhen Gu; Qingtie Xiao; Ruiyu Lin; Xinyu Zheng (Journal of Hazardous Materials, 2024)

Rapid and non-destructive identification of Panax ginseng origins using hyperspectral imaging, visible light imaging, and X-ray imaging combined with multi-source data fusion strategies - Jiacong Ping; Zehua Ying; Nan Hao; Peiqi Miao; Cheng Ye; Changqing Liu; Wenlong Li (Food Research International, 2024)

Investigation of the effect of ultrasonication on starch-fatty acid complexes and the stabilization mechanism - Zongwei Hao; Zhaofeng Li; Qianxin Zhou; Zhenni Ma; Jiali Lv; Yanrui Wang; Ailong Hu; Juntao Cheng; Zhenyu Yu; Zhongwen Xie; Yiqun Du (Food Research International, 2024)

Tuning the planarity of molecularly imprinted covalent organic frameworks for selective extraction of ochratoxin A in alcohol samples - Hao-Ze Li; Hai-Long Qian; Shu-Ting Xu; Cheng Yang; Xiu-Ping Yan (Food Chemistry, 2024)

Microplastics footprint in nature reserves-a case study on the microplastics in the guano from Yancheng Wetland Rare Birds National Nature Reserve, China - Huimin Jiang; Hai Cheng; Shiyue Wu; Hongshan Li; Hao Chen; Zhenghao Li; Xinyun Yao; Yanan Zhang; Yaqin Chen; Shuyi Chen; Shihao Chen; Liang Zheng; et al. (Environmental Research, 2024)

FAP expression dynamics and role in silicosis: Insights from epidemiological and experimental models - Xuedan Deng; Zhiwei Cheng; Yiping Li; Meixiu Duan; Jingyi Qi; Changfu Hao; Wu Yao (Environmental Pollution, 2024)

Prediction of BLEVE-induced response of road tunnel using Transformer network with modified self-attention (SAMT) - Ruishan Cheng; Wensu Chen; Hong Hao; Qilin Li (Engineering Structures, 2024)

A multifunctional barium-modified geopolymer foam for the efficient and flexible treatment of high-sulfate coal mine drainage - Xuhao Zhang; Xiao Zhang; Minghui Ma; Rui Cheng; Chenglong Hao; Li Zhang; Jiaqi Zhang (Chemical Engineering Journal, 2024)

Corrigendum to “Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots” [Chem. Eng. J. 486 (2024) 150196] - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Nanoscale characterization of Ediacaran microfossils from lower Doushantuo formation chert nodules - Shiqi Cheng; Lianjun Feng; Chaoqun Zhang; Linhao Cui; Wei Liu; Hao Qiu; Shi He; Xuelei Chu; Xingliang Zhang; Jinhua Li (Chemical Geology, 2024)

Water flush boosts performance of elemental sulfur-based denitrification packed-bed systems: Optimization and mechanisms - Jia-Min Xu; Heng Dong; Hao-Ran Xu; Yi-Lu Sun; Yang Yu; Li-Ying Zhang; Gen-Ping Yi; Wen-Ke He; Chang-Min Wu; Ai-Jie Wang; Hao-Yi Cheng (Bioresource Technology, 2024)

Downregulating DNA methyltransferase 3B by suppressing the PI3K/Akt signaling pathway enhances the chemosensitivity of glioblastoma to temozolomide - Wenwu Kan; Linhui Gao; Jingnan Chen; Li Chen; Guojun Zhang; Bilie Hao; Min He; Xudong Chen; Cheng Wang (Molecular Neurobiology, 2024)
Glioblastoma (GBM) is the most common malignant brain tumor and has the poorest prognosis attributed to its chemoresistance to temozolomide (TMZ), the first-line drug for treating GBM. TMZ resistance represents a significant obstacle to successful GBM treatment, necessitating the development of new strategies to overcome this resistance and augment the chemosensitivity of GBM cells to TMZ. This study established a TMZ-resistant U251 (U251-TMZ) cell line by exposing it to increasing doses of TMZ in vitro. We focused on the DNA methyltransferase 3B (DNMT3B) gene, phosphorylated Akt (p-Akt), total Akt (t-Akt), phosphorylated PI3K (p-PI3K), and total PI3K (t-PI3K) protein expression. Results showed that the DNMT3B gene was significantly upregulated in the U251-TMZ cell line. The p-Akt and p-PI3K protein expression in U251-TMZ cells was also significantly elevated. Moreover, we found that DNMT3B downregulation was correlated with the increased chemosensitivity of GBM cells to TMZ. LY294002 suppressed the PI3K/Akt signaling pathway, leading to a notable inhibition of PI3K phosphorylation and a significant decrease in DNMT3B expression in U251-TMZ cells. Given that DNMT3B expression is mediated by the PI3K/Akt signaling pathway, its downregulation further increased the chemosensitivity of GBM cells to TMZ and therefore is a promising therapeutic for GBM treatment. Our results suggested that DNMT3B downregulation can inhibit the proliferation of GBM cells and induce GBM cell apoptosis in vitro. In addition, the PI3K/Akt signaling pathway plays an important role in the chemosensitivity of GBM cells to TMZ by regulating DNMT3B expression.

Unveiling the innovative green synthesis mechanism of selenium nanoparticles by exploiting intracellular protein elongation factor Tu from Bacillus paramycoides - Pei Liu; Haiyu Long; Shuai He; Han Cheng; Erdong Li; Siyu Cheng; Mengdi Liang; Zhengwei Liu; Zhen Guo; Hao Shi (Journal of Zhejiang University-SCIENCE B, 2024)

T ree diversity across multiple scales and environmental heterogeneity promote ecosystem multifunctionality in a large temperate forest region - Jie Li; Minhui Hao; Yanxia Cheng; Xiuhai Zhao; Klaus von Gadow; Chunyu Zhang (Global Ecology and Biogeography, 2024)
Aim Biodiversity across different scales provides multidimensional insurance for ecosystem functioning. Although the effects of biodiversity on ecosystem multifunctionality are well recorded in local communities, they remain poorly understood across scales (from local to larger spatial scales). This study evaluates how multiple attributes of biodiversity maintain ecosystem multifunctionality from local to regional scales, across diverse environmental gradients. Location North‐eastern China. Time Period 2017. Major Taxa Studied Woody plants. Methods We define multifunctionality using both averaged and modified multiple‐threshold approaches. Multiple dimensions of biodiversity across varying spatial scales were measured within the framework of Hill–Chao numbers. Using variance decomposition, linear mixed models and structural equation modelling, we explored how multiple attributes of tree diversity at varying spatial scales affect multifunctionality, and how these relationships are modulated by environmental drivers. Results We found that both α‐ and β‐diversity are critical for regional community multifunctionality, while the relationships between species, functional and phylogenetic diversity and multifunctionality decoupled across spatial scales and thresholds of ecosystem functioning. Phylogenetic β‐diversity and species α‐diversity are, respectively, more important for promoting high‐ and moderate‐threshold multifunctionality (e.g. EMF T90 and EMF T50 ) in regional communities. Environmental drivers typically have stronger effects than biodiversity on multifunctionality. Soil and climatic conditions had either direct effects on multifunctionality or indirect ones mediated by species α‐diversity. Environmental heterogeneity is important for high‐threshold multifunctionality, exerting directly and indirectly through phylogenetic β‐diversity. Latitude not only directly influences multifunctionality but also modulates it through species α‐diversity and phylogenetic β‐diversity. Main Conclusions This study underscores the positive effects of biodiversity on multifunctionality across multiple dimensions. Based on our findings, we conclude that any design of a forested landscape that is aimed at maximizing multifunctionality should consider maintaining high local diversity as well as forest community heterogeneity at varying scales.

Exploring seasonal variations, assembly dynamics, and relationships of bacterial communities in different habitats of marine ranching - Cheng-Zhuang Chen; Ming-Hao Yin; Lin-Jing Niu; Jin-Xin Wang; Ling Liu; Yong-Jun Sun; Wen-Ming Ju; Ping Li; Zhi-Hua Li (Marine Pollution Bulletin, 2024)

Quantifying instantaneous nitrogen oxides emissions from power plants based on space observations - Tao Tang; Tianhai Cheng; Hao Zhu; Xiaotong Ye; Donghao Fan; Xingyu Li; Haoran Tong (Science of The Total Environment, 2024)

Magnetic biochar serves as adsorbents and catalyst supports for the removal of antibiotics from wastewater: A review - Yudong Li; Jian Zhang; Dongle Cheng; Wenshan Guo; Huaqing Liu; Aiyun Guo; Xinhan Chen; Yanlong Wang; Huu Hao Ngo (Journal of Environmental Management, 2024)

Phycocyanin-derived bioactive peptide PCP3 ameliorates lipopolysaccharide-induced small intestinal inflammation in murine intestinal organoids and mice through regulating Akt and AMPK/autophagy signaling - Boxiong Wu; Haozhe Cheng; Xinran Li; Qi Yang; Wenjing Zhang; Shuai Hao; Chengtao Wang (Food Bioscience, 2024)

ZnO/g-C3N4 photocatalyst activated by low-pressure ultraviolet for restoring the SWASV signals: A fast pretreatment method for electrochemically detecting Cd2+ and Pb2+ in soil extracts - Haonan Li; Renjie He; Ning Liu; Liya Feng; Shaowen Chen; Hao Wang; Cheng Lv; Xinyi Chen; Gang Liu; Guo Zhao (Environmental Pollution, 2024)

Hollow multi-shelled structure engineering of organosilica for efficient and selective uranium extraction from seawater - Meng Cheng; Yuqi Liu; Hao Jiang; Chunling Li; Shuangqing Sun; Songqing Hu (Desalination, 2024)

Pyrolysis-free coupling strategy to synthesize two-dimensional oxygen reaction electrocatalysts for rechargeable Zn-air batteries - Peng-Fei Xie; Hao Hu; Lingzhe Fang; Xiaohua Yu; Ju Rong; Xiaoyi Qiu; Feng Wu; Tao Li; Minhua Shao; Jin-Cheng Li (Chemical Engineering Journal, 2024)

Waste plastics to prepare eutectogel: Wearable, highly deformable, transparent flexible ionic conductors - Panpan Hao; Xiujie Cheng; Xingmei Lu; Qing Zhou; Dongxia Yan; Jiayu Xin; Junli Xu; Yi Li (Chemical Engineering Journal, 2024)

Recycling alginate-like extracellular polymers (ALE) from municipal sludge: Value-added products and external impact - Ming Cheng; Chen Shi; Bo-Han Zhao; Nan Zhang; Qing-Yue Shen; Li-Ting Hao; Xiang-Yang Wang (Chemical Engineering Journal, 2024)

Metal-organic frameworks derived low-cost Cu-doped Co3O4 for efficient reduction of ultra-low nitrate concentrations to ammonia - Xiaorui Hu; Mingming Zhang; Cui Lai; Min Cheng; Fuhang Xu; Dengsheng Ma; Ling Li; Huchuan Yan; Hao Sun; Xing Fan; Biting Wang (Chemical Engineering Journal, 2024)

A blue light 3D printable hydrogel with water absorption, antibacterial, and hemostatic properties for skin wound healing - Xiu-Chong He; Xiu-Ning Chen; Yi-Hao Liu; Xinyu Zhong; Lei Qiang; Hong-Qin Wang; Fang-Zhou Wang; Jun-Song Wang; Cheng-Hui Li; Peng-Fei Zheng (Chemical Engineering Journal, 2024)

Occurrence and mechanism of sulfamethoxazole in alginate-like extracellular polymers from excess sludge - Chen Shi; Ming Cheng; Run-Gen Zeng; Cong-Cong Li; Qian Wang; Li-Ting Hao; Ran-Bin Liu; Xiao-Di Hao; Xiang-Yang Wang; Yuan-Yuan Wu (Bioresource Technology, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

True Ageing: An Up-to-date Model for Evaluating the Immune Age of the Chinese Population - Hao Cheng; Bin Li (Phenomics, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

Multi‐omics analyses reveal the signatures of metabolite transfers across trophic levels in a high‐ CO 2 ocean - Mengcheng Ye; Jiale Zhang; Mengting Xiao; Jiali Huang; Yunyue Zhou; John Beardall; John A. Raven; Guang Gao; Xiao Liang; Fenghuang Wu; Baoyi Peng; Leyao Xu; et al. (Limnology and Oceanography, 2024)
Although the diverse impacts of elevated dissolved CO 2 and warming on organisms within various trophic levels in marine food webs are well documented, we have yet to explore the biological links across different levels of biological organization from primary producers to secondary producers on an evolutionary time scale in a high‐CO 2 ocean. Here, we cultured a model marine diatom Phaeodactylum tricornutum (primary producer) in predicted future high‐CO 2 and/or warming conditions for ~ 1250 d with an experimental evolution approach and then fed them to the clam Coelomactra antiquata (secondary producer). We present an in‐depth multi‐omics analysis along the methylome (primary producer)–transcriptome (primary producer)–metabolome (primary producer)–metabolome (secondary producer) continuum. Our results showed that the downregulated terpenoid backbone biosynthesis in the methylome and transcriptome lead to decreased pyruvate levels and upregulation of some pathways (such as phenylalanine metabolism) in the metabolome of the primary producer in the long‐term warming conditions. These changes in metabolomic profile in the primary producer were then transferred to the secondary producer, resulting in changes in abundance of some metabolites, such as decreases in pyruvate, and in pyruvaldhyde (also known as methylglyoxal), and increases in 2‐hydroxylamino‐4,6‐dinitrotoluene. Our study provides a new insight into the molecular mechanisms underlying the trophic transfer from primary to secondary producers in a future high‐CO 2 ocean and may provide more accurate projections of marine ecosystem services and functions over the next century.

Establishment and characterization of the PDAC-X3 cell line: a novel Chinese-origin pancreatic ductal adenocarcinoma cell line - Changpeng Chai; Huan Tang; Xin Miao; Yuanhui Su; Lu Li; Cheng Yu; Jianfeng Yi; Zhenzhen Ye; Long Miao; Bo Zhang; Zhengfeng Wang; Wei Luo; et al. (Human Cell, 2024)

Multi-random ensemble on Partial Least Squares regression to predict wheat yield and its losses across water and nitrogen stress with hyperspectral remote sensing - Bohan Mao; Qian Cheng; Li Chen; Fuyi Duan; Xiaoxiao Sun; Yafeng Li; Zongpeng Li; Weiguang Zhai; Fan Ding; Hao Li; Zhen Chen (Computers and Electronics in Agriculture, 2024)

Regulating microbial redox reactions towards enhanced removal of refractory organic nitrogen from wastewater - Ke Shi; Bin Liang; Hao-Yi Cheng; Hong-Cheng Wang; Wen-Zong Liu; Zhi-Ling Li; Jing-Long Han; Shu-Hong Gao; Ai-Jie Wang (Water Research, 2024)

Corrigendum to “Intensified response of extreme precipitation to rising temperature over the Tibetan Plateau from CMIP6 multi-model ensembles” [J. Hydrol. 637 (2024) 131397] - Wenqing Zhang; Liu Liu; Xiuping Li; Lei Cheng; Yongming Cheng; Hao Li (Journal of Hydrology, 2024)

Hydrophobic nanosheet silicalite-1 zeolite for iodine and methyl iodide capture - Qian Zhao; Xin Li; Guangyuan Chen; Zeru Wang; Chuan Tan; Cheng Liu; Hao Zou; Jing Ma; Lin Zhu; Tao Duan (Journal of Hazardous Materials, 2024)

The mechanism of resveratrol stabilization and degradation by synergistic interactions between constituent proteins of whey protein - Xin Yin; Wusigale; Hao Cheng; Paul Van der Meeren; Li Liang (Food Research International, 2024)

Exploring the novel antioxidant peptides in low-salt dry-cured ham: Preparation, purification, identification and molecular docking - Ying-dao Nan; Bai-de Mu; Chang-xin Ge; Si-qi Chen; Ming-xun Cui; Hong-mei Li; Chang-cheng Zhao; Juan Wang; Chun-xiang Piao; Guan-hao Li (Food Chemistry, 2024)

Large-scale and facile fabrication of phenyl-containing silicone foam materials with lightweight, wide-temperature flexibility and tunable pore structure for exceptional thermal insulation - Yu-Yue Wu; Zhi-Hao Wu; Zuan-Yu Chen; Li-Dong Peng; Zi-Qi Guan; Yang Li; Cheng-Fei Cao; Guo-Dong Zhang; Jie-Feng Gao; Pingan Song; Yong-Qian Shi; Long-Cheng Tang (Chemical Engineering Journal, 2024)

Versatile MOF-based nanofibrous heterostructures for engineering the CO2 photoreduction activity and selectivity: From CO to C2H5OH - Xu-Chao Xia; Feng Cheng; Peng Sun; Amare Aregahegn Dubale; Hao Han; En-Tian Cui; Jun Song; Xiu-Li Yang; Ming-Hua Xie (Chemical Engineering Journal, 2024)

Impact of model resolution and its representativeness consistency with observations on operational prediction of PM2.5 with 3D-VAR data assimilation - Ying Wei; Xiujuan Zhao; Ziyin Zhang; Jing Xu; Siyu Cheng; Zhiquan Liu; Wei Sun; Xueshun Chen; Zifa Wang; Xin Hao; Jiandong Li; Dan Chen (Atmospheric Pollution Research, 2024)

Biosafety assessments of hexafluoropropylene trimer derivative as a fluorinated cooling fluid for electronics - Yi-Tong Zhou; Pei-Jie Zhang; Shu-Ping Wang; Chang-Hao Li; Jia-Qing Zhang; Wei-Xin Zhang; Yuan-Di Zhao; Yuan-Cheng Cao; Jin-Xuan Fan (Toxicological Research, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

The inputs of autochthonous organic carbon driven by mangroves reduce metal mobility and bioavailability in intertidal regions - Linjing Niu; Youshao Wang; Yanwu Zhou; Jiao Fei; Cuici Sun; Zhi-Hua Li; Hao Cheng (Science of The Total Environment, 2024)

Neoarchean clockwise P-T trajectories with evolution sequence from HP to UHT metamorphism during decompression: Evidence from petrology, mineralogy, and phase equilibria modeling of mafic granulites in the Sittampundi Complex, southern India - Xu Kong; Jun-Sheng Lu; Ming-Guo Zhai; Cheng-Li Zhang; M.P. George; Long-Long Gou; Yan Zhao; Wen-Hao Ao; Yu-Hua Hu; Qiang Feng; Gang Liu (Precambrian Research, 2024)

The phytochemistry, pharmacology, pharmacokinetics, quality control, and toxicity of Forsythiae Fructus: An updated systematic review - Jin-Jin Li; Zi-Hao Chen; Cheng-Jun Liu; Yu-Shuo Kang; Xin-Pu Tu; Hong Liang; Wei Shi; Feng-Xiang Zhang (Phytochemistry, 2024)

Overexpression of a nuclear receptor HR96 contributes to spirodiclofen susceptibility in Panonychus citri (McGregor) - Si-chen Li; Lu-yan Cheng; Qi-qi Yang; Ze-hao Huang; Bin-bin Shao; Shi-jiang Yu; Li-li Ding; Qi Pan; Shuang Lei; Liu Liu; Lin Cong; Chun Ran (Pesticide Biochemistry and Physiology, 2024)

Intensified response of extreme precipitation to rising temperature over the Tibetan Plateau from CMIP6 multi-model ensembles - Wenqing Zhang; Liu Liu; Xiuping Li; Lei Cheng; Yongming Cheng; Hao Li (Journal of Hydrology, 2024)

Discovery of abundant shock-induced metallic lead nanograins in lunar zirconolite - Ai-Cheng Zhang; Hao-Xuan Sun; Tian-Ran Trina Du; Jia-Ni Chen; Li-Xin Gu (Geochimica et Cosmochimica Acta, 2024)

Simulated logistical transport effects on textural change of wax apple using different packaging types during storage time - Wanqi Wei; Na Zhang; Baoqing Li; Tong Zhao; Chiyun Cheng; Cunkun Chen; Hao Deng; Ruixiang Yan (Food Packaging and Shelf Life, 2024)

Significance of non-DLVO interactions on the co-transport of levofloxacin and titanium dioxide nanoparticles in porous media - Yiqun Cui; Ming Wu; Guoping Lu; Zhou Cheng; Meng Chen; Yanru Hao; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu (Environmental Pollution, 2024)

Incomplete ionic interactions and hydrogen bonds constructing elastomers with water accelerated Self-Healing and self-healing strengthening capacities - Hao Jiang; Tong Yan; Wuting Pang; Meng Cheng; Zhihao Zhao; Tinglei He; Zhikun Wang; Chunling Li; Shuangqing Sun; Songqing Hu (Chemical Engineering Journal, 2024)

A review on anaerobic co-digestion of sewage sludge with other organic wastes for methane production: Mechanism, process, improvement and industrial application - Pengfei Li; Hao Zhao; Chongbo Cheng; Tingting Hou; Dekui Shen; Youzhou Jiao (Biomass and Bioenergy, 2024)

Swelling characteristics of compacted graphene-modified GMZ bentonite infiltrated with NaCl solution - Yu-Hao Hu; Yong-Gui Chen; Yu-Cheng Li; Wei-Min Ye; Qiong Wang; Dong-Bei Wu (Bulletin of Engineering Geology and the Environment, 2024)

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

A review of the ethnopharmacology, phytochemistry, pharmacology, pharmacokinetics and toxicology of Abri Herba (Ji-Gu-Cao) - Cheng-Jun Liu; Hong-Xin Li; Zi-Hao Chen; Jin-Jin Li; Wei Shi; Feng-Xiang Zhang (Phytochemistry, 2024)

A literature review on phosphate removal from wastewater by lanthanum-based adsorbents: From mechanisms to applications - Yao-Yao Lu; Hao Wang; Rong-Rong Chang; Wen-Bing Li; Bao-Cheng Huang; Ren-Cun Jin (Journal of Water Process Engineering, 2024)

Synergistic effects of chemical additives and mature compost on reducing H2S emission during kitchen waste composting - Yongdi Liu; Haihou Wang; Hao Zhang; Yueyue Tao; Rui Chen; Sheng Hang; Xiaoyan Ding; Meidi Cheng; Guochun Ding; Yuquan Wei; Ting Xu; Ji Li (Journal of Environmental Sciences, 2024)

Energy dissipation and seismic response reduction system for high-speed railway bridges based on multiple performance requirements - Xiuli Xu; Xu Chen; Hao Hu; Xuxu Zhou; Mengmeng Cheng; Lei Sun; Xuehong Li (Engineering Structures, 2024)

An oxygen isotope perspective on the break-up of the Rodinia supercontinent - Hao Zou; Chang-Cheng Huang; Hua-Wen Cao; Chun-Mei Liu; Hui-Dong Yu; Franco Pirajno; Xian-Hua Li (Earth-Science Reviews, 2024)

Enhancing biohydrogen production from xylose through natural FeS2 ore: Mechanistic insights - Yun Xu; Miao-yu Deng; Si-jia Li; Yi-cheng Yuan; Hao-yu Sun; Quan Wang; Rong-ping Chen; Lei Yu (Bioresource Technology, 2024)

A bipolar SMPS network for measuring atmospheric aerosols using natural air ions - Yiran Li; Jin Wu; Hao Wu; Xiaomeng Liu; Qi Zhou; Yiqun Lu; Yuhang Wu; Mengyu Liu; Hengjia Ou; Shixin Mai; Xuehui He; Huaying Song; et al. (Atmospheric Environment, 2024)

A Senescence-Associated Secretory Phenotype of Bone Marrow Mesenchymal Stem Cells Inhibits the Viability of Breast Cancer Cells - Meng Li; Jie-Xi Liu; Bo Ma; Jin-Yu Liu; Ji Chen; Fang Jin; Cheng-Hu Hu; Hao-Kun Xu; Chen-Xi Zheng; Rui Hou (Stem Cell Reviews and Reports, 2024)

Gastrodin Regulates PI3K/AKT-Sirt3 Signaling Pathway and Proinflammatory Mediators in Activated Microglia - Han-Jun Zuo; Peng-Xiang Wang; Xue-Qi Ren; Hao-Long Shi; Jin-Sha Shi; Tao Guo; Cheng Wan; Juan-Juan Li (Molecular Neurobiology, 2024)

Social parasitism behavior between two species of edible wasps in China - Cheng-Ye Wang; Hao-Yu Chen; Bing-Qing Fang; Pan-Li Yang; Zhao He; Long Sun; Jin Gan; Min Zhao; Ying Feng (Journal of Ethology, 2024)

Germplasm evaluation and identification of the population source of hard clam (Mercenaria mercenaria) in China using SSR and COI markers - JunYi Wang; DongXiu Xue; MeiJie Yang; YunLong Ji; Hao Song; Cong Zhou; Pu Shi; YongRen Li; YongJun Guo; FanYu Meng; ChangPing Lai; ShunFeng Cheng; et al. (Frontiers in Marine Science, 2024)
In aquaculture, good germplasm resources are nearly decisive for its development. The hard clam ( Mercenaria mercenaria ), a significant marine aquaculture bivalve in China, has flourished quickly since being introduced from North America in 1997. However, for numerous reasons, it has suffered from germplasm deterioration and uncertain origins. To address these issues, seven microsatellite DNA loci (SSRs) and mtCOI were employed to evaluate germplasm and trace the origins of various Chinese populations. The results of these two molecular genetic markers revealed weak genetic differentiation among all Chinese populations, with high genetic diversity observed across most individuals, except for a few outliers. This suggests an alarming situation regarding germplasm resources in China. Based on results of traceability analysis, the most likely areas of origin for the Chinese populations are Chesapeake Bay and the southern region of Cape Hatteras. This study provides a crucial theoretical foundation for the cultivation, conservation, and subsequent introduction of hard clam populations in China, thereby ensuring the sustainable growth of the hard clam breeding sector.

Screening and identification of probiotics from the intestinal tract of largemouth bass (Micropterus salmoides) for use as a feed additive and bacterial infection control - Lu Xia; Gaofeng Cheng; Pan Wang; Xinyou Wang; Zhaoran Dong; Qingjiang Mu; Jiaqian Yu; Zhihao Jiang; Jun Xiao; Hao Feng; Xiangping Li; Weiguang Kong; et al. (Aquaculture, 2024)

Experimental research on signal sensing of distributed acoustic sensing optical fiber based on Φ-OTDR in shallow water - Wei-hao Cao; Guang-li Cheng (Wave Motion, 2024)

Insights into simultaneous efficient removal of cationic and anionic dyes by nitrogen-rich seaweed carbon adsorbent - Xiaoxue Cheng; Hongping Li; Ding Jiang; Wanming Lu; Qifan Ling; Shan Zhong; Hao Chen; Bahram Barati; Xun Hu; Xun Gong; Shuang Wang (Process Safety and Environmental Protection, 2024)

Analysis of the dynamic response of submerged floating tunnels to wave-induced loads, incorporating joint mechanical properties - Jie Hou; Bo Huang; Peng Chen; Hao Ding; Jianting Zhou; Ke Li; Liang Cheng; Qingyang Ren; Dan Zhong (Ocean Engineering, 2024)

Geochemical and U-Pb isotopic insights into uranium (U) enrichment in the soil around a nuclear fuel element plant, in Southwest China - Xin Cheng; Jianing Sun; Kai Ling; Keyi Zhong; Bolin Shao; Lan Li; Shanshan Zhao; Yi Huang; Hao Song; Bo Cheng (Ore and Energy Resource Geology, 2024)

Attempts to obtain clean biochar from hyperaccumulator through pyrolysis: Removal of heavy metals and transformation of phosphorus - Zhiyuan Li; Yaji Huang; Zhicheng Zhu; Mengzhu Yu; Haoqiang Cheng; Hao Shi; Yixuan Xiao; Huikang Song; Wu Zuo; Haiyun Zhou; Sheng Wang (Journal of Hazardous Materials, 2024)

Novel CoFe-NC bimetallic catalysts for heterogeneous electro-Fenton process to remove BAA in dye wastewater - Zhi-Hao Li; Hui-Lai Liu; De-Feng Kong; Cheng Gong; Xing Chen (Journal of Environmental Chemical Engineering, 2024)

Ce enhanced low-temperature performance of Mn modified Cu-Beta zeolite catalyst for NH3-SCR - Xin Guo; Zhiyong Ding; Na Kang; Liu Yang; Yuanjiang Wang; Cheng Zhang; Zhaoqiang Li; Tiantian Zhang; Yan Wang; Yu Wang; Hao Qu (Fuel, 2024)

PM2.5 induces a senescent state in mouse AT2 cells - Peiyong Cheng; Yongqi Chen; Jianhai Wang; Ziyu Han; De Hao; Yu Li; Feifei Feng; Xuexin Duan; Huaiyong Chen (Environmental Pollution, 2024)

Ionic-confining-assisted multiple-mode tunable light emitting of carbon nanodots - Jing-Nan Hao; Zhong-Zheng Ding; Cheng-Long Shen; Guang-Song Zheng; Jia-Lu Liu; Ruo-Bing Li; Run-Wei Song; Kai-Kai Liu; Jin-Hao Zang; Lin Dong; Qing Lou; Chong-Xin Shan (Chemical Engineering Journal, 2024)

Impact of SO2 and light on chemical morphology and hygroscopicity of natural salt aerosols - Xiangrui Kong; Cheng Wu; Harsh Raj Mishra; Yuxin Hao; Mathieu Cazaunau; Antonin Bergé; Edouard Pangui; Robin Faust; Wanyu Liu; Jun Li; Sen Wang; Bénédicte Picquet-Varrault; et al. (Atmospheric Environment, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Study on the Purification Effect and Mechanism of Micro–Nano-Bubble-Based Two-Stage Air Floatation Method on the Raw Sugar Redissolved Syrup - Hao Cheng; Tingfan Tang; Qiubai Meng; Wenkang Zhang; Lijun Li (Sugar Tech, 2024)

JAML inhibits colorectal carcinogenesis by modulating the tumor immune microenvironment - Shiliang Cheng; Meng Li; Chunguang Li; Yonggang Dai; Jinhua Zhuo; Jue Wang; Jingrong Qian; Zhihao Hao (In Vitro Cellular & Developmental Biology - Animal, 2024)

Genome-wide association study reveals the genetic basis of cold tolerance in soybean - Zhiyu Wang; Wei Li; Yaning Gao; Ming Shao; Kaiyi Yin; Yixiang Pu; Hao Cheng; Deyue Yu; Fang Huang; Hengyou Zhang; Jiao Wang (Euphytica, 2024)

Identification and functional analysis of phycocyanin-derived bioactive peptides with non-small cell lung cancer cell inhibition - Boxiong Wu; Haozhe Cheng; Xinran Li; Qi Yang; Shuai Hao; Chengtao Wang; Baoguo Sun (Algal Research, 2024)

Xiashengella succiniciproducens gen. nov., sp. nov., a succinate-producing bacterium isolated from an anaerobic digestion tank in the family Marinilabiliaceae of the order Bacteroidales - Hao-Jie Huang; Xi Zhang; Xin-Wei Sun; Biao Chen; Xiu-Tong Li; Nan Zhou; Rashidin Abdugheni; Qiu-Yin Cheng; Tie-Jun Zhang; Yao Liu; Yong Jiang; Ye Deng; et al. (Archives of Microbiology, 2024)

Regime shift of the leading mode of winter surface wind speed in northwest China in 2003/04 and its possible link with Barents–Kara sea ice - Yong Wang; Zi‐Han Zhou; Xin‐Yu Liu; Cheng‐Hai Wang; Dong Xiao; Wen‐Yao Li; Hao‐Jun Qin (International Journal of Climatology, 2024)
Using the ERA‐5 reanalysis datasets, NCEP/NCAR sea ice concentration (SIC) and observed winter surface wind speed (WSWS) in northwest China during 1979–2020, this study examined the regime shift of the leading mode of observed WSWS in northwest China and investigated its possible link with the winter Barents–Kara Sea (BKS) SIC. The leading mode of observed WSWS in northwest China showed negative anomalies in southern and northeastern Xinjiang, Gansu, western and northern Shaanxi Provinces, and positive anomalies in northwestern and middle Xinjiang, Qinghai and Ningxia Provinces. The signs of WSWS in the leading mode is generally opposite to their trends during 1979–2020. Leading principal component (PC1) of observed WSWS in northwest China underwent an obvious decreasing regime shift in 2003/04, as well as the winter BKS SIC. There are significant correlations between PC1 and BKS SIC on both interdecadal and interannual timescales. Decadal decrease of BKS SIC is accompanied with a positive phase of Scandinavia pattern (SP) with positive anomalies of 500‐hPa geopotential height over subtropical North Atlantic, Arctic‐Ural region and southern Asia, and negative anomalies over northern North Atlantic‐West Europe and Siberia regions. BKS SIC and SP significantly influenced the Northern China Wind Index (NCWI) at 200 hPa on interdecadal timescale, which was related to the PC1 on both interdecadal and interannual timescales after removing the signal of Arctic Oscillation. Meridional configuration of Siberian cyclonic anomaly and southern Asian anticyclonic anomaly associated with the winter BKS SIC could enhance the intensity of NCWI, which favoured the increase of observed WSWS in northwest China and thereby may contribute to the regime shift in 2003/04 of the leading mode. However, there were still some stations showing decreasing regime shift, which mainly located at the region of steeping terrain. These decreasing changes of WSWS may be related to circumfluence effect of terrain, urbanization and local microclimate, and these reasons still need further detailed study.

The leaching behavior of heavy metal from contaminated mining soil: The effect of rainfall conditions and the impact on surrounding agricultural lands - Fei Wang; Wei Li; Hao Wang; Yuanan Hu; Hefa Cheng (Science of The Total Environment, 2024)

Effect of pre-cladding dust layer on filtration and pulse-jet cleaning performance of filter media - Hui Cheng; Shihang Li; Gengjun Li; Gangcheng Peng; Yingchao Wei; Hao Jin; Shuda Hu; Changgeng Gui; Fubao Zhou (Process Safety and Environmental Protection, 2024)

IiAGL6 participates in the regulation of stamen development and pollen formation in Isatis indigotica - Liu Yang; Xin Qiao; Hao-En He; Wei-Wei Yi; Ya-Nan Gao; Xiao-Min Tan; Hao Cheng; Xiao-Fang Hou; Ye-Ye Ma; Hong-Li Wang; Xuan Huang; Yan-Qin Ma; et al. (Plant Science, 2024)

Coupled dynamic analysis for wave action on a tension leg-type submerged floating tunnel in the frequency domain - Bo Huang; Wenlong Luo; Yue Chen; Jianting Zhou; Hao Ding; Ke Li; Liang Cheng; Dan Zhong (Ocean Engineering, 2024)

Characteristics of NOX and NH3 emissions from in-use heavy-duty diesel vehicles with various aftertreatment technologies in China - Liqiang He; Gang Li; Xiaomeng Wu; Shaojun Zhang; Miao Tian; Zhenhua Li; Cheng Huang; Qingyao Hu; Ye Wu; Jiming Hao (Journal of Hazardous Materials, 2024)

Potassium isotopes as a tracer of hydrothermal alteration in ore systems - Kun-Feng Qiu; Rolf L. Romer; Zheng-Yu Long; Hao-Cheng Yu; Simon Turner; Ruo-Qi Wan; Xiao-Qiang Li; Zi-Yue Gao; Jun Deng (Geochimica et Cosmochimica Acta, 2024)

Simultaneous determination of enantiomer residues of metalaxyl and its metabolite metalaxyl acid in animal muscle tissues by chiral liquid chromatography-tandem mass spectrometry - Hao Zhou; Qi Shan; Limin He; Meiyu Zhang; Cheng Zhao; Guangming Zheng; Lichun Li; Feng Xu; Lisha Ma; Yi Yin (Food Chemistry, 2024)

Response of plastic film mulched maize to soil and atmospheric water stresses in an arid irrigation area - Cheng Li; Jingui Wang; Yunxin Zhang; Hao Feng; Wenxin Zhang; Kadambot H.M. Siddique (European Journal of Agronomy, 2024)

Intercalation of HKUST-1: A strategy for conferring GOM with accurate size-sieving, self-cleaning, and antibacterial multi-functionalities - Xiao Ke Zheng; Hao Yu; Wen Li Gan; Yi Liang; Xinyi Hu; Tao Tang; Yinfen Cheng; Hao Yao; Jian Zhen Ou (Desalination, 2024)

Long-life high-voltage all-solid-state batteries enabled by bismuth (III)triflate mediated polymer electrolytes - Hao Yan; Jiaqi Hu; Yi-Xiao Deng; Ying Hu; Jin-Cheng Zheng; Wenrong Li; Tinglu Song; Yang Dai (Chemical Engineering Journal, 2024)

Acetylcholine Analog-Modified Albumin Nanoparticles for the Enhanced and Synchronous Brain Delivery of Saponin Components of Panax Notoginseng - Ying Yu; Li Yun Wang; Yan Chi Liu; Hao Cui; Cheng Yuan; Cheng Xiao Wang (Pharmaceutical Research, 2024)

Autophagy inhibition mediated by trillin promotes apoptosis in hepatocellular carcinoma cells via activation of mTOR/STAT3 signaling - Guangjie Zhan; Tiantian Wei; Huichen Xie; Xiaoming Xie; Jun Hu; Hao Tang; Yating Cheng; Huaifeng Liu; Shujing Li; Guohua Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Identification of lncRNA-miRNA-mRNA Networks in the Lenticular Nucleus Region of the Brain Contributes to Hepatolenticular Degeneration Pathogenesis and Therapy - Wenjie Hao; Wenming Yang; Yue Yang; Ting Cheng; Taohua Wei; Lulu Tang; Nannan Qian; Yulong Yang; Xiang Li; Hailin Jiang; Meixia Wang (Molecular Neurobiology, 2024)
Long non-coding RNAs (lncRNAs) are a recently discovered group of non-coding RNAs that play a crucial role in the regulation of various human diseases, especially in the study of nervous system diseases which has garnered significant attention. However, there is limited knowledge on the identification and function of lncRNAs in hepatolenticular degeneration (HLD). The objective of this study was to identify novel lncRNAs and determine their involvement in the networks associated with HLD. We conducted a comprehensive analysis of RNA sequencing (RNA-seq) data, reverse transcription-quantitative polymerase chain reaction (RT-qPCR), and computational biology to identify novel lncRNAs and explore their potential mechanisms in HLD. We identified 212 differently expressed lncRNAs, with 98 upregulated and 114 downregulated. Additionally, 32 differently expressed mRNAs were found, with 15 upregulated and 17 downregulated. We obtained a total of 1131 pairs of co-expressed lncRNAs and mRNAs by Pearson correlation test and prediction and annotation of the lncRNA-targeted miRNA-mRNA network. The differential lncRNAs identified in this study were found to be involved in various biological functions and signaling pathways. These include translational initiation, motor learning, locomotors behavior, dioxygenase activity, integral component of postsynaptic membrane, neuroactive ligand-receptor interaction, nuclear factor-kappa B (NF-κB) signaling pathway, cholinergic synapse, sphingolipid signaling pathway, and Parkinson’s disease signaling pathway, as revealed by the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses. Six lncRNAs, including XR_001782921.1 ( P < 0.01), XR_ 001780581.1 ( P < 0.01), ENSMUST_00000207119 ( P < 0.01), XR_865512.2 ( P < 0.01), TCONS_00005916 ( P < 0.01), and TCONS_00020683 ( P < 0.01), showed significant differences in expression levels between the model group and normal group by RT-qPCR. Among these, four lncRNAs (TCONS_00020683, XR_865512.2, XR_001780581.1, and ENSMUST00000207119) displayed a high degree of conservation. This study provides a unique perspective for the pathogenesis and therapy of HLD by constructing the lncRNA-miRNA-mRNA network. This insight provides a foundation for future exploration in this field.

Investigation of organic contaminants in the blubber of a blue whale (Balaenoptera musculus) first stranded on the coast of Taiwan - Jing-O. Cheng; Pei-Ling Wang; Li-Chin Chou; Chig-Wei Chang; Hao Ven Wang; Wei-Cheng Yang; Fung-Chi Ko (Environmental Science and Pollution Research, 2024)

Enzyme-free sensitive SERS biosensor for the detection of thalassemia-associated microRNA-210 using a cascade dual-signal amplification strategy - Qiying Chen; Huagan Chen; Hongxing Kong; Ruijue Chen; Si Gao; Ying Wang; Pei Zhou; Wenyi Huang; Hao Cheng; Lijun Li; Jun Feng (Analytica Chimica Acta, 2024)

Potential risk, leaching behavior and mechanism of heavy metals from mine tailings under acid rain - Wei Li; Yu Deng; Hao Wang; Yuanan Hu; Hefa Cheng (Chemosphere, 2024)

Molecular oxygen activation: Innovative techniques for environmental remediation - Lili Zhou; Yuting Liu; Hao Shi; Yurui Qing; Cheng Chen; Liguo Shen; Mingzhu Zhou; Bisheng Li; Hongjun Lin (Water Research, 2024)

Mechanistic insights into the effects of diuron exposure on Alexandrium pacificum - Dan Huang; Cai-Qin Cheng; Jiang-Bing Qiu; Yun Huang; Hao-Yun Zhang; Zhen-Hao Xu; Si-Wei Wu; Yi-Tong Huang; Jian Chen; Li-Gong Zou; Wei-Dong Yang; Xiao-Fei Zheng; et al. (Water Research, 2024)

Emodin suppresses adipogenesis of bone marrow derived mesenchymal stem cells from aplastic anemia via increasing TRIB3 expression - Xianning Zhang; Lulu Liu; Jian Wang; Mingkang Yao; Lei Liu; Haihui Liu; Saisai Ren; Peng Wei; Panpan Cheng; Xiyu Li; Hao Zhang; Mingtai Chen (Tissue and Cell, 2024)

Temperature acclimation improves high temperature tolerance of rainbow trout (Oncorhynchus mykiss) by improving mitochondrial quality and inhibiting apoptosis in liver - Hao Li; Haibo Yu; Xiaotian Zhang; Wenhao Huang; Cheng Zhang; Chi Wang; Qinfeng Gao; Shuanglin Dong (Science of The Total Environment, 2024)

Uranium speciation and distribution on the surface of Shewanella putrefaciens in the presence of inorganic phosphate and zero-valent iron under anaerobic conditions - Guo-Xiu Xuan; Guo-Hao Zhang; Wen-Cai Cheng; Chun-Yan Ma; Qing-Rong Li; En-Tong Liu; Wen-Ge He; Fa-Qin Dong; Xiao-An Li; Zheng-Guo Chen; Xiao-Qin Nie (Science of The Total Environment, 2024)

Ultrasensitive fluorescence detection of gonyautoxins in seawater using a novel molecularly imprinted nanoprobe - Huan Xu; Ziru Lian; Xiaochen Hao; Fang Li; Ren-Cheng Yu (Science of The Total Environment, 2024)

Cattle manure hydrochar posed a higher efficiency in elevating tomato productivity and decreasing greenhouse gas emissions than plant straw hydrochar in a coastal soil - Xiao Wang; Qingxian Kong; Yadong Cheng; Chenghao Xie; Yuan Yuan; Hao Zheng; Xueyang Yu; Hui Yao; Yue Quan; Xiangwei You; Chengsheng Zhang; Yiqiang Li (Science of The Total Environment, 2024)

A new method of the hydrocarbon secondary migration research: Numerical simulation - Hao Xu; Jun Li; Xiaorong Luo; Ming Cheng; Chao Li; Xiaoying Zhang; Huanquan Pan (Marine and Petroleum Geology, 2024)

The long-term spatial and temporal distributions of polychlorinated naphthalene air concentrations in Fildes Peninsula, West Antarctica - Tariku Bekele Gebru; Qinghua Zhang; Cheng Dong; Yanfen Hao; Cui Li; Ruiqiang Yang; Yingming Li; Guibin Jiang (Journal of Hazardous Materials, 2024)

Bacterial carbonic anhydrase-induced carbonates mitigate soil erosion in biological soil crusts - Zhimao Mai; Qiqi Chen; Lin Wang; Jian Zhang; Hao Cheng; Hongfei Su; Si Zhang; Jie Li (Journal of Environmental Management, 2024)

Shale oil potential and mobility in low- to medium-maturity lacustrine shales: A case study of the Yanchang Formation shale in southeast Ordos Basin, China - Huairen Cao; Jun Shi; Zhao-Wen Zhan; Hao Wu; Xiaoyu Wang; Xin Cheng; Haolin Li; Yan-Rong Zou; Ping'an Peng (International Journal of Coal Geology, 2024)

One-stone, two birds: Three-dimensional structure and rich-inorganic solid electrolyte interface derived from Bi nanoparticles modified Ti3C2/CNT/rGO aerogel for anode-free potassium metal batteries - Dong-Ting Zhang; Mao-Cheng Liu; Min-Peng Li; Zi-Zhou Yuan; Yu-Xia Hu; Hao Chen; Chen-Yang Li; Ling-Bin Kong; Kun Zhao; Jun-Qiang Ren; Bao Liu (Chemical Engineering Journal, 2024)

Deciphering the role of hydraulic retention time (HRT) in integrated fixed-film activated sludge (IFAS) system under aniline stress: Effects on microbial succession and communication - Nan-ping Wu; Bin Tan; Meng Li; Naif Abdullah Al-Dhabi; Bing Lin; Qi He; Hao-nan Shen; Jia-jing Cheng; Wangwang Tang; Qian Zhang (Chemical Engineering Journal, 2024)

A new cyclohexenone derivative from phomopsis sp. XM-01 - Cheng-Yao Wang; Dong Gan; Chen-Zhe Li; Li Zhu; Xiao-Ran Zhang; Ya-Ni Li; Xiu-Hong Wu; Hao Zhou; Le Cai (Natural Product Research, 2024)

Rheumatoid arthritis is a protective factor against Alzheimer’s disease: a bidirectional two-sample Mendelian randomization study - Guo-Shuai Li; Yong-Ze Yang; Guo-Rong Ma; Peng-Fei Li; Qing-Hao Cheng; An-Ren Zhang; Zhuang-Zhuang Zhang; Fu-Kang Zhang; Xin Yang; Hua Fan; Hong-Zhang Guo (Inflammopharmacology, 2024)

Stronger latitudinal phylogenetic patterns in woody angiosperm assemblages with higher dispersal abilities in China - Lu Jin; Jia‐Jia Liu; Qiao‐Ming Li; Lu‐Xiang Lin; Xiao‐Na Shao; Tian‐Wen Xiao; Bu‐Hang Li; Xiang‐Cheng Mi; Hai‐Bao Ren; Yan Zhu; Xiu‐Juan Qiao; Ju‐Yu Lian; et al. (Journal of Biogeography, 2024)
Aim The equator‐to‐poles decline in the number of species, namely the latitudinal diversity gradient (LDG), is the most conspicuous pattern in biology, yet the underlying mechanisms of this pattern remain controversial. Species dispersal could have strong effects on large‐scale species distributions but has rarely been considered in understanding the LDG. Here we sought to examine how dispersal ability may influence the latitudinal phylogenetic patterns of woody angiosperm assemblages. Location China. Taxon Woody angiosperms. Methods Based on a highly supported mega‐phylogeny constructed from plastid genomes, we assessed the patterns of phylogenetic relatedness and dissimilarity of 1184 trees with three different seed dispersal modes (i.e. zoochory, anemochory and autochory) in 12 permanent forest dynamic plots covering tropical, subtropical and temperate zones in China. Results We found that, compared with zoochorous and anemochorous species, the less vagile autochorous trees exhibited a much weaker latitudinal pattern in phylogenetic relatedness and higher phylogenetic dissimilarity among plots. The phylogenetic dissimilarity pattern of autochorous trees was explained more by geographic distance than environmental factors, consistent with a dominant role for dispersal limitation. Main Conclusions Our study, for the first time, demonstrates that seed dispersal mode strongly influences the latitudinal phylogenetic patterns of woody angiosperm assemblages in China and highlights the importance of interaction between dispersal limitation and environmental filtering in determining the large‐scale distribution of forest biodiversity.

Establishment and characterization of DPC-X4: a novel mixed-type ampullary cancer cell line - Changpeng Chai; Huan Tang; Jianfeng Yi; Lu Li; Cheng Yu; Yuanhui Su; Long Miao; Zhenzhen Ye; Zhengfeng Wang; Wei Luo; Jinjing Hu; Hui Zhang; et al. (Human Cell, 2024)

Three new cardenolides from the fruits of Cascabela thevetia (L.) Lippold and their cytotoxic activities - Juan Long; Jia-Cheng Ouyang; Yu-Hao Luo; Qi-Jing Wu; Xiao-Tong Liao; Zhi-Le Chen; Qi-Lin Wang; Xiao-Yan Liang; Li Liu; Xue-Mei Yang; Xiao-San Li (Natural Product Research, 2024)

Model test research of wave-induced submarine landslide based on Fibre Bragg Grating sensing technology - Shang Gao; Shuai Cheng; Qing Jin; Shucai Li; Hao Jin; Sheng Wang; Yuxue Chen (Ocean Engineering, 2024)

Quantification and visualization of groundwater contamination prevention regionalization based on analytic hierarchy process method (AHP) in Guangdong-Hong Kong-Macao Greater Bay Area, South China - Zhou Cheng; Guoping Lu; Ming Wu; Zhaohui Li; Yirong Deng; Jinzhe Wu; Yanru Hao; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu (Journal of Hydrology, 2024)

Neogene morphotectonic evolution of the East Asian Continental Shelf - Haohao Cheng; Yanhui Suo; Xuesong Ding; Sanzhong Li; Ze Liu; Syed Wajid Hanif Bukhari; Guangzeng Wang; Pengcheng Wang; Liangliang Wang; Hao Dong; Xianzhi Cao; Xu Han; et al. (Geomorphology, 2024)

Combining with volatilomic profiling and chemometrics to explore the volatile characteristics in five different dried Zanthoxylum bungeanum maxim - Jinze Feng; Lifang Hao; Haobin Zhu; Maoying Li; Yulin Liu; Qiuxiao Duan; Lili Jia; Dongmei Wang; Cheng Wang (Food Research International, 2024)

Highly efficient activation of periodate by a manganese-modified biochar to rapidly degrade methylene blue - Jiamin Gong; Honghui Jiang; Xiang Li; Hao Cheng; Ziqi Wang; Jingju Cai; Meifang Li; Ping Wang; Hui Wang; Xi Hu; Xinjiang Hu (Environmental Research, 2024)

Agglomeration inhibition mechanism of SiO2 in the Ca(OH)2/CaO thermochemical heat storage process: A reactive molecular dynamics study - Kun Wang; Cheng-Ming Zhang; Bo-Chao Liu; Li Yang; Chun-Hua Min; Zhong-Hao Rao (Chemical Engineering Journal, 2024)

A multifunctional emitter with synergistical adjustment of rigidity and flexibility for high-performance data-recording and organic light-emitting devices with “hot exciton” channel - Guowei Chen; Wen-Cheng Chen; Yaozu Su; Ruicheng Wang; Jia-Ming Jin; Hui Liang; Bingxue Tan; Dehua Hu; Shaomin Ji; Hao-Li Zhang; Yanping Huo; Yuguang Ma (Chemical Engineering Journal, 2024)

Potentiation of the lateral habenula-ventral tegmental area pathway underlines the susceptibility to depression in mice with chronic pain - Chun-Kui Zhang; Pan Wang; Yuan-Yuan Ji; Jian-Shuai Zhao; Jun-Xiang Gu; Xian-Xia Yan; Hong-Wei Fan; Ming-Ming Zhang; Yu Qiao; Xiao-Die Liu; Bao-Juan Li; Ming-Hui Wang; et al. (Science China Life Sciences, 2024)

Fabrication and characterization of coated microneedle patches based on PEGDA for transdermal administration of metformin - Bo Zhou; Zhendong Guo; Peiwen Zhao; Hao Wang; Siyan Dong; Bo Cheng; Jing Yang; Binbin Li; Xinyu Wang (Drug Delivery and Translational Research, 2024)

Net greenhouse gas balance in U.S. croplands: How can soils be part of the climate solution? - Yongfa You; Hanqin Tian; Shufen Pan; Hao Shi; Chaoqun Lu; William D. Batchelor; Bo Cheng; Dafeng Hui; David Kicklighter; Xin‐Zhong Liang; Xiaoyong Li; Jerry Melillo; et al. (Global Change Biology, 2024)
Agricultural soils play a dual role in regulating the Earth's climate by releasing or sequestering carbon dioxide (CO 2 ) in soil organic carbon (SOC) and emitting non‐CO 2 greenhouse gases (GHGs) such as nitrous oxide (N 2 O) and methane (CH 4 ). To understand how agricultural soils can play a role in climate solutions requires a comprehensive assessment of net soil GHG balance (i.e., sum of SOC‐sequestered CO 2 and non‐CO 2 GHG emissions) and the underlying controls. Herein, we used a model‐data integration approach to understand and quantify how natural and anthropogenic factors have affected the magnitude and spatiotemporal variations of the net soil GHG balance in U.S. croplands during 1960–2018. Specifically, we used the dynamic land ecosystem model for regional simulations and used field observations of SOC sequestration rates and N 2 O and CH 4 emissions to calibrate, validate, and corroborate model simulations. Results show that U.S. agricultural soils sequestered Tg CO 2 ‐C year −1 in SOC (at a depth of 3.5 m) during 1960–2018 and emitted Tg N 2 O‐N year −1 and Tg CH 4 ‐C year −1 , respectively. Based on the GWP100 metric (global warming potential on a 100‐year time horizon), the estimated national net GHG emission rate from agricultural soils was Tg CO 2 ‐eq year −1 , with the largest contribution from N 2 O emissions. The sequestered SOC offset ~28% of the climate‐warming effects resulting from non‐CO 2 GHG emissions, and this offsetting effect increased over time. Increased nitrogen fertilizer use was the dominant factor contributing to the increase in net GHG emissions during 1960–2018, explaining ~47% of total changes. In contrast, reduced cropland area, the adoption of agricultural conservation practices (e.g., reduced tillage), and rising atmospheric CO 2 levels attenuated net GHG emissions from U.S. croplands. Improving management practices to mitigate N 2 O emissions represents the biggest opportunity for achieving net‐zero emissions in U.S. croplands. Our study highlights the importance of concurrently quantifying SOC‐sequestered CO 2 and non‐CO 2 GHG emissions for developing effective agricultural climate change mitigation measures.

A Dual Functional Fluorescent Probe Based on Phenothiazine for Detecting Hg2+ and ClO− and its Applications - Cheng-lu Zhang; Chang Liu; Shi-ru Nie; Yang Zhang; Jing-hao Guo; Xiang-ling Li; Cui Liu (Journal of Fluorescence, 2023)

Clarification of the phosphorus release mechanism for recovering phosphorus from biofilm sludge in alternating aerobic/anaerobic biofilm system - Hao Zhang; Shuang-Shuang Zhang; Wei Zhang; Wu-Cheng Ma; Yang Pan; Lin Chen; Liang Zhu; Yi-Ping Li; Jing-Ru Li (Science of The Total Environment, 2023)

Strategies for fertilizer management to achieve higher yields and environmental and fertilizer benefits of rice production in China - Zongkui Chen; Xinrui Li; Tao Liu; Hao Fu; Xiaojuan Yuan; Qingyue Cheng; Qin Liao; Yue Zhang; Weitao Li; Yongjian Sun; Zhiyuan Yang; Jun Ma; et al. (Science of The Total Environment, 2023)

Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

Ion-etched zeolitic imidazolate framework (ZIF) derived transition metal phosphides with a thin carbon shell as high-performance trifunctional catalyst for oxygen reduction, oxygen evolution and hydrogen evolution reactions - Hao Lei; Wenzheng Li; Jinbo Fei; Shuailong Guo; Yao Liu; Qingjiang Liu; Lukuan Cheng; Yan Huang (Journal of Environmental Chemical Engineering, 2023)

CO2-assisted synthesis of graphitic resin-based activated carbon for ultrahigh selective adsorption of VOCs under humid conditions - Jinjin Li; Tangying Cheng; Hao Wu; Linjun Yang (Fuel, 2023)

Vineyard soil heterogeneity and harvest date affect volatolomics and sensory attributes of Cabernet Sauvignon wines on a meso-terroir scale - Hao-Cheng Lu; Meng-Bo Tian; Xiao Han; Ning Shi; Hui-Qing Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (Food Research International, 2023)

Cannabidiol protects the liver from α-Amanitin-induced apoptosis and oxidative stress through the regulation of Nrf2 - Haowei Wang; Genmeng Yang; Xiaoxing Zhang; Huijie Zhang; Yan Liu; Chan Wang; Lin Miao; Yi Li; Yizhen Huang; Hanxin Teng; Shangwen Wang; Hao Cheng; et al. (Food and Chemical Toxicology, 2023)

Insights into metal/carbon materials activation of persulfate from a structure–property perspective: Performances, tunable reaction pathways and toxicity - Hao Ge; Min Cheng; DanLian Huang; Ming Yan; Zhen Wei; Gaoxia Zhang; Li Du; Guangfu Wang; Hongda Liu; Shaoheng Liu; Yongxi Chen (Chemical Engineering Journal, 2023)

Effects of salinity on sulfur-dominated autotrophic denitrification microorganisms: Microbial community succession, key microorganisms and response mechanisms - Zhuo-Ran Li; Xue-Ning Zhang; Hong-Cheng Wang; Hao-Yi Cheng; Ai-Jie Wang; Yan-Qing Zhang; Chong-Wei Cui; Yi-Lu Sun (Chemical Engineering Journal, 2023)

Hydrophobic carbon with hollow and hierarchical porous structures for efficient VOCs removal from complex exhaust gases: Experiments and DFT calculations - Jinjin Li; Tangying Cheng; Hao Wu; Linjun Yang (Chemical Engineering Journal, 2023)

Wood frame structured carbons with integrated sieving layer for propylene/propane separation - Cheng-Tong Wang; Wen-Cui Li; Shuang Xu; Ru-Shuai Liu; Guang-Ping Hao; An-Hui Lu (Chemical Engineering Journal, 2023)

Controllable reduction of absorbance and two-step reaction for 3D-printed SiC ceramics with micron-level periodic structure - Dou Yang; Hao Li; Wenqiang Yang; Minggang Zhang; Hui Mei; Shixiang Zhou; Jin Zhao; Tong Zhao; Yuekai Yan; Chengyu Liang; Lei Qiao; Laifei Cheng; et al. (Chemical Engineering Journal, 2023)

An epi-allele of SMS causes Sanming dominant genic male sterility in rice - Yachun Yang; Cheng Zhang; Hao Li; Zeyuan Yang; Zuntao Xu; Dewei Tai; Dahu Ni; Pengcheng Wei; Chengxin Yi; Jianbo Yang; Yong Ding (Science China Life Sciences, 2023)

Improving Blood Monocyte Energy Metabolism Enhances Its Ability to Phagocytose Amyloid-β and Prevents Alzheimer’s Disease-Type Pathology and Cognitive Deficits - Zhi-Hao Liu; Yu-Di Bai; Zhong-Yuan Yu; Hui-Yun Li; Jie Liu; Cheng-Rong Tan; Gui-Hua Zeng; Yun-Feng Tu; Pu-Yang Sun; Yu-Juan Jia; Jin-Cai He; Yan-Jiang Wang; et al. (Neuroscience Bulletin, 2023)

White matter alterations in mild cognitive impairment revealed by meta-analysis of diffusion tensor imaging using tract-based spatial statistics - Longfei Li; Wei Yang; Yu Wan; Hailong Shen; Ting Wang; Liangliang Ping; Chuanxin Liu; Min Chen; Hao Yu; Shushu Jin; Yuqi Cheng; Xiufeng Xu; et al. (Brain Imaging and Behavior, 2023)

Transcriptome analysis of flower colour reveals the correlation between SNP and differential expression genes in Phalaenopsis - Yu Ding; Ma-Yin Wang; Ding-Hai Yang; Dai-Cheng Hao; Wei-Shi Li; Peng Ling; Shang-Qian Xie (Genes & Genomics, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Corrigendum: Identifying the wetlands of international importance in Beibu Gulf along the East Asian – Australasian Flyway, based on multiple citizen science datasets - Ningxin Tang; Yanju Ma; Sixin Li; Yizhu Yan; Cheng Cheng; Gang Lu; Fei Li; Liuxuan Lv; Peilin Qin; Hoai Bao Nguyen; Quang Hao Nguyen; Trong Trai Le; et al. (Frontiers in Marine Science, 2023)

Synthesis and evaluation of in vitro and in vivo anti -Toxoplasma gondii activity of tetraoxane-substituted ursolic acid derivatives - Ya-Lan Wang; Li-Li Jin; Xu Cheng; Wei-Feng Yan; Hao Deng; Qing-Kun Shen; Zhe-Shan Quan; Chun-Mei Jin; Chang-Hao Zhang (Natural Product Research, 2023)

Relationship of individual and mixed urinary metals exposure with liver function in the China National Human Biomonitoring (CNHBM) of Zhejiang Province - Ping Cheng; Yi Tao; Jinfeng Hu; Hongxin Wang; Ruifang Zhao; Shenghua Mei; Yin Yang; Fugen Ye; Zhijian Chen; Hao Ding; Mingluan Xing; Peiwei Xu; et al. (Chemosphere, 2023)

Impacts of land use on climate in the Taihu Basin based on WRF model - Manqiu Hao; Cheng Gao; Guofang Li; Boyao Zhang; Jing Zhu; Yong Xu (Urban Climate, 2023)

Effects of species mixtures on soil water storage in the semiarid hilly gully region - Dong Cheng; Lei Jiao; Guangyao Gao; Jianbo Liu; Weiliang Chen; Zongshan Li; Yingfei Bai; Hao Wang; Liwei Zhang (Science of The Total Environment, 2023)

Atmospheric saccharides over the East China Sea: Assessment of the contribution of sea-land emission and the aging of levoglucosan - Mengxin Fu; Hao Li; Lan Wang; Mengke Tian; Xiaofei Qin; Xuan Zou; Cheng Chen; Guochen Wang; Congrui Deng; Kan Huang (Science of The Total Environment, 2023)

GPCR signaling contributes to immune characteristics of microenvironment and process of EBV-induced lymphomagenesis - Jie Xiong; Yu-Ting Dai; Wen-Fang Wang; Hao Zhang; Chao-Fu Wang; Tong Yin; Shu Cheng; Hui-Juan Zhong; Shan-He Yu; Lu Jiang; Sheng-Yue Wang; Hai Fang; et al. (Science Bulletin, 2023)

Effects of beauvericin on the blood cells of Bombyx mori - Yong Bi; Lingzhi Wu; Baozhen Li; Yanping Hao; Zixiao Li; Jiwei Zhang; Aiying Cheng; Guizhen Yuan; Jinhua Fan (Journal of Invertebrate Pathology, 2023)

Nitrogen removal performance and C, N, S transformation under dry-wet alterations of heterotrophic-autotrophic sequential bioretention system amended with waste reed and sulfur - Zhaoying Liu; Liyuan Wu; Yang Hao; Yu Cheng; Chaohong Tan; Jia Wang; Haiyan Li (Journal of Cleaner Production, 2023)

Co-pyrolysis of industrial sludge with phytoremediation residue: Improving immobilization of heavy metals at high temperature - Zhiyuan Li; Yaji Huang; Zhicheng Zhu; Mengzhu Yu; Haoqiang Cheng; Hao Shi; Wu Zuo; Haiyun Zhou; Sheng Wang (Fuel, 2023)

Dietary cultured supernatant mixture of Cetobacterium somerae and Lactococcus lactis improved liver and gut health, and gut microbiota homeostasis of zebrafish fed with high-fat diet - Shenghui Li; Hongwei Yang; Ya Jin; Qiang Hao; Shubin Liu; Qianwen Ding; Yuanyuan Yao; Yalin Yang; Chao Ran; Chenglong Wu; Shengkang Li; Kaimin Cheng; et al. (Fish & Shellfish Immunology, 2023)

Tailor-made yolk-shell nanocomposites of star-shape Au and porous organic polymer for nitrogen electroreduction to ammonia - Hongming He; Hao-Ming Wen; Ping Li; Hong-Kai Li; Cheng-Peng Li; Zhihong Zhang; Miao Du (Chemical Engineering Journal, 2023)

Tailoring pore structures in poly(propylene-co-1-butene) membranes: Unlocking versatility for advanced applications - Xian Zhang; Cheng-Ye Zhu; Wangbei Cao; Zhao-Yu Ma; Hao-Nan Li; Hong-Qing Liang; Chuan-Jie Fang; Xiao-Jun Huang; Zhi-Kang Xu (Chemical Engineering Journal, 2023)

Flexible and MOF-808 uniformly assembled polyimide nanofiber membranes with excellent mechanical properties for rapid degradation of chemical warfare agents - Zhikang Cheng; Xiang Li; Li Zhang; Zupei Yuan; Haimin Zheng; Hao Guo; Xu Zhao; Jie Chen; Yu Pan; Xiaoxiao Chen; Yanlai Feng; Zhouai Luo; et al. (Chemical Engineering Journal, 2023)

Seasonal differences in continental outflows and marine emissions of organic aerosols in the East China Sea: Insight from the variation of saccharides - Hao Li; Lan Wang; Xiaofei Qin; Guochen Wang; Mengxin Fu; Cheng Chen; Jian Xu; Congrui Deng; Kan Huang (Atmospheric Research, 2023)

Short-term effect of meteorological factors and extreme weather events on daily outpatient visits for dry eye disease between 2013 and 2020: a time-series study in Urumqi, China - Si-Yu Gui; Fei Wang; Jian-Chao Qiao; Xin-Chen Wang; Zhi-Hao Huang; Fan Yang; Cheng-Yang Hu; Fang-Biao Tao; Li-Ming Tao; Dong-Wei Liu; Xiang-Long Yi; Zheng-Xuan Jiang (Environmental Science and Pollution Research, 2023)

Multi-stage adsorption of methyl orange on the nitrogen-rich biomass-derived carbon adsorbent: DFT and MD evaluation - Xiaoxue Cheng; Ding Jiang; Hao Chen; Bahram Barati; Chuan Yuan; Hongping Li; Shuang Wang (Chemosphere, 2023)

Quantification of two-site kinetic transport parameters of polystyrene nanoplastics in porous media - Yuheng Wu; Zhou Cheng; Ming Wu; Yanru Hao; Guoping Lu; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu (Chemosphere, 2023)

Monitoring and management of abandoned, lost and discarded fishing gear (ALDFG) in Penghu Islands, Taiwan - Wen-Hong Liu; Hung-An Chang; Hao-Tang Jhan; Chih-Cheng Lin; Li-Shu Chen; Chung-Lun Liu; Kuo-Huan Ting (Marine Pollution Bulletin, 2023)

Performance of road tunnel subjected to BLEVE occurring inside adjacent tunnel - Ruishan Cheng; Wensu Chen; Hong Hao; Jingde Li (Tunnelling and Underground Space Technology, 2023)

Lithospheric velocity structure of South China Sea basin from ocean bottom seismometer ambient noise tomography - Liqun Cheng; Yinxia Fang; Xiongwei Niu; Tingzi Li; Chongzhi Dong; Yanghui Zhao; Hao Hu; Fansheng Kong; Pingchuan Tan; Aiguo Ruan; Shaoping Lu; Jianke Fan; et al. (Tectonophysics, 2023)

Fire effects on soil carbon cycling pools in forest ecosystems: A global meta-analysis - Yue Cheng; Peng Luo; Hao Yang; Honglin Li; Chuan Luo; Honghong Jia; Yu Huang (Science of The Total Environment, 2023)

Synergistic driving effects of risk factors on human brucellosis in Datong City, China: A dynamic perspective from spatial heterogeneity - Li Shen; Ming-hao Sun; Wen-tao Ma; Qing-wu Hu; Chen-xi Zhao; Zu-rong Yang; Cheng-hao Jiang; Zhong-jun Shao; Kun Liu (Science of The Total Environment, 2023)

Provenance changes of the Yangtze River Delta sediments since ∼3.6 Ma: Evidence from heavy mineral assemblages and detrital zircon U–Pb ages spectra - Shefeng Hao; Yu Cheng; Bingfei Gao; Xiangqian Li; Shiyin Xu; Ding Luo (Quaternary International, 2023)

Geodynamic controls on the Paleo-Asian oceanic plate evolution: Constraints from Paleozoic intrusive suites along the northern margin of the North China Block - Jialiang Li; Chen Wu; Lin Cheng; Hao Yang; Di-Cheng Zhu; Jingao Liu (Lithos, 2023)

Recovering phosphorus and lithium separately from wastewater and brine using a novel coupled biofilm-precipitation system - Hao Zhang; Shuang-Shuang Zhang; Wei Zhang; Wu-Cheng Ma; Yi-Ping Li; Lin Chen; Liang Zhu; Yang Pan (Journal of Water Process Engineering, 2023)

Response mechanism of groundwater dynamics to Freeze–thaw process in seasonally frozen soil areas: A comprehensive analysis from site to regional scale - Hang Lyu; Han Li; Pan Zhang; Chijitai Cheng; Hao Zhang; Shenshen Wu; Qicheng Ma; Xiaosi Su (Journal of Hydrology, 2023)

Lipid metabolic links between serum pyrethroid levels and the risk of incident type 2 diabetes: A mediation study in the prospective design - Chengyong Jia; Gaokun Qiu; Hao Wang; Shiyang Zhang; Jun An; Xu Cheng; Peiwen Li; Wending Li; Xin Zhang; Handong Yang; Kun Yang; Tao Jing; et al. (Journal of Hazardous Materials, 2023)

Superior pore size for enhancing the competitive adsorption of VOCs under high humid conditions: An experiment and molecular simulation study - Jinjin Li; Yin Yin; Tangying Cheng; Heng Chen; Linjun Yang; Hao Wu (Journal of Environmental Chemical Engineering, 2023)

Biofilm formation and development during the pyrite bioleaching of moderately thermophilic microorganisms - Li Shen; Jinju Cheng; Junjun Wang; Yejuan Zhang; Hao Zhou; Xueling Wu; Jiaokun Li; Weiming Zeng (Hydrometallurgy, 2023)

Physics-supervised ensemble learning model for predicting failure modes of reinforced concrete columns - Bo Yu; Hao Cheng; Zecheng Yu; Bing Li; Qiang Zhang (Engineering Structures, 2023)

Carbon-based hierarchical porous structure accelerates heterogeneous nucleation of PEG molecules for solar/electro-driven thermal energy storage - Ruze Liu; Ang Li; Jinyan Liu; Wengeng Liu; Hao Zheng; Qingyang Du; Xiao Chen; Cheng Dong (Chemical Engineering Journal, 2023)

Facilitating Li+ conduction channels and suppressing lithium dendrites by introducing Zn-based MOFs in composite electrolyte membrane with excellent thermal stability for solid-state lithium metal batteries - Shengbin Luo; Nanping Deng; Hao Wang; Qiang Zeng; Yanan Li; Weimin Kang; Bowen Cheng (Chemical Engineering Journal, 2023)

Application of Mo2C for enhancement of co-catalytic performance of Fe3+/PS based fenton-like reaction in degrading tetracycline hydrochloride - Hao Cheng; Yi Wen; Chao Huang; Ping Wang; Chengyou Sun; Chongling Feng; Jialu Xu; Li Du; Ting Yan; Min Cheng (Chemical Engineering Journal, 2023)

Flame-retardant Janus ramie fabric with unidirectional liquid transportation, moisture-wicking, and oil/water separation properties - Huihui Wang; Cheng Hao; Tong Shu; Pandeng Li; Tianyi Yu; Longjiang Yu; Ning Yan (Chemical Engineering Journal, 2023)

Multi-valent mRNA vaccines against monkeypox enveloped or mature viron surface antigens demonstrate robust immune response and neutralizing activity - Niubing Zhang; Xiang Cheng; Yilong Zhu; Ouyang Mo; Huiqing Yu; Liqi Zhu; Juan Zhang; Linlin Kuang; Ying Gao; Ruiyuan Cao; Xiaozhen Liang; Haikun Wang; et al. (Science China Life Sciences, 2023)

NRF2 Antagonizes HIV-1 Tat and Methamphetamine-Induced BV2 Cell Ferroptosis by Regulating SLC7A11 - Shucheng Lin; Hao Cheng; Genmeng Yang; Chan Wang; Chi-Kwan Leung; Shuwei Zhang; Yi Tan; Huijie Zhang; Haowei Wang; Lin Miao; Yi Li; Yizhen Huang; et al. (Neurotoxicity Research, 2023)

A two-step non-nominal troposphere monitor for GBAS - Jiaxiang Li; Hao Yin; Jianhua Cheng; Liang Li; Chun Jia; Jiachang Jiang (GPS Solutions, 2023)

Assessment of 13 essential and toxic trace elements in tumor and peritumoral brain tissues from human glioblastoma - Hao-Long Zeng; Binmei Jia; Qing Yang; Fengbo Zeng; Huijun Li; Chao-Xi Li; Liming Cheng (JBIC Journal of Biological Inorganic Chemistry, 2023)

Association of urinary bisphenols with thyroid function in the general population: a cross-sectional study of an industrial park in China - Yang Hu; Shiming Lai; Ying Li; Xiaodong Wu; Mingluan Xing; Xueqing Li; Dandan Xu; Yuan Chen; Jie Xiang; Ping Cheng; Xiaofeng Wang; Zhijian Chen; et al. (Environmental Science and Pollution Research, 2023)

Identifying the wetlands of international importance in Beibu Gulf along the East Asian – Australasian Flyway, based on multiple citizen science datasets - Ningxin Tang; Yanju Ma; Sixin Li; Yizhu Yan; Cheng Cheng; Gang Lu; Fei Li; Liuxuan Lv; Peilin Qin; Hoai Bao Nguyen; Quang Hao Nguyen; Trong Trai Le; et al. (Frontiers in Marine Science, 2023)
The Beibu Gulf (Gulf of Tonkin, Vinh Bac Bo in Vietnamese), located midway along the East Asian-Australasian Flyway (EAAF), is a critical stopover and wintering region for migratory waterbirds. This transboundary coastal region, spanning between China and Vietnam, harbors diverse wetland habitats that provide refuge to waterbird species, including highly threatened species such as the spoon-billed sandpiper (CR) and the black-faced spoonbill (EN). However, the scarcity of comprehensive assessments regarding waterbird abundances, distribution, key wetland habitats, and regional threats hinders our understanding of its conservation significance at the flyway level. Further research is needed to address these knowledge gaps and facilitate effective conservation efforts in the Beibu Gulf. By synthesizing accessible citizen science datasets and published records from wetland sites in south China and northeast Vietnam, we concluded that at least 97 waterbird species used the Gulf’s wetlands during their annual cycle. Among surveys conducted from 2014 to 2022, 5 and 11 waterbird species were considered as first and second class protected species under the National Key Protected Wild Animal List in China; 2 species were listed as Critically Endangered on the IUCN Red List, 4 as Endangered and 2 as Vulnerable, underlying the critical importance of the Beibu Gulf for the survival of these species. Our study identified 25 sites in the Beibu Gulf that met the criteria for designation as internationally important wetlands. Alarmingly, less than a quarter (n = 5, or 20%) of these sites benefit from national or international protection. Localized threats, including aquatic resource harvesting, hunting, and aquaculture/fisheries, were widespread in the region. This study provides a crucial scientific baseline for continued waterbird monitoring, site prioritization, and the development of effective habitat management plans to conserve vital coastal wetland habitats in the Beibu Gulf in China and Vietnam.

University-driven coastal partnerships to address ghost gear pollution: A case study in Penghu Islands of Taiwan - Chih-Cheng Lin; Kuo-Huan Ting; Hao-Tang Jhan; Chung-Lun Liu; Li-Shu Chen; Wen-Hong Liu (Marine Policy, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Suppression effects and mechanisms of three typical solid suppressants on titanium hydride dust explosions - Shi-zhou Li; Yang-fan Cheng; Rui Wang; Meng Li; Run Li; Hong-hao Ma (Process Safety and Environmental Protection, 2023)

Open-framework hybrid zinc/tin selenide as an ultrafast adsorbent for Cs+, Ba2+, Co2+, and Ni2+ - Yang Liu; Feng-Qi Shi; Xin Hao; Meng-Yu Li; Lin Cheng; Cheng Wang; Kai-Yao Wang (Journal of Hazardous Materials, 2023)

Heterogeneous ultra-thin FeCo-LDH@Co(OH)2 nanosheets facilitated electrons transfer for oxygen evolution reaction - Xian Yang; Jun Cheng; Yang Xu; Hao Li; Weifeng Tu; Junhu Zhou (Chemical Engineering Journal, 2023)

IrCo single-atom alloy catalysts with optimized d-band center for advanced alkali-Al/acid hybrid fuel cell - Mengtian Zhang; Hao Li; Fei-Xiang Ma; Liang Zhen; Yue Du; Cheng-Yan Xu (Chemical Engineering Journal, 2023)

Electrospun polyvinyl alcohol-chitosan dressing stimulates infected diabetic wound healing with combined reactive oxygen species scavenging and antibacterial abilities - Haibing Liu; Rong Chen; Pinkai Wang; Jinlang Fu; Zinan Tang; Jiajun Xie; Yanhong Ning; Jian Gao; Qiang Zhong; Xin Pan; Ding Wang; Mingyuan Lei; et al. (Carbohydrate Polymers, 2023)

Simultaneous phosphorus recovery from wastewater and sludge by a novel denitrifying phosphorus removal system - Hao Zhang; Wei Zhang; Shuang-Shuang Zhang; Wu-Cheng Ma; Liang Zhu; Yi-Ping Li; Yang Pan; Lin Chen (Bioresource Technology, 2023)

Activation of Pgk1 Results in Reduced Protein Aggregation in Diverse Neurodegenerative Conditions - Hao Chen; Yajie Li; Jingwen Gao; Qi Cheng; Lei Liu; Rong Cai (Molecular Neurobiology, 2023)

A methodological framework of landslide quantitative risk assessment in areas with incomplete historical landslide information - Xia Li; Jiu-Long Cheng; De-Hao Yu (Journal of Mountain Science, 2023)

Farm size increase alters the contribution of land use types to sources of river sediment - Hao Guo; Yong Li; Toyin Peter Abegunrin; Kayode Steven Are; Xu Wang; Cheng Tang; Tingting Chen; Zhigang Huang (Agriculture, Ecosystems & Environment, 2023)

The role of exosomes and their enhancement strategies in the treatment of osteoarthritis - Linzhen Huang; Ge Dong; Jie Peng; Ting Li; Mi Zou; Kaibo Hu; Yuan Shu; Tao Cheng; Liang Hao (Human Cell, 2023)

A feedback control method for plant factory environment based on photosynthetic rate prediction model - Hao Wang; Xiangyu Meng; Zerui Chen; Xihai Zhang; Ruifeng Cheng; Yi Zhang; Wei Li; Weixian Song; Yu Zhang (Computers and Electronics in Agriculture, 2023)

Response of buried box-shaped road tunnel against internal BLEVE and its damage mitigation - Ruishan Cheng; Wensu Chen; Hong Hao; Jingde Li (Tunnelling and Underground Space Technology, 2023)

Safety assessment of organic micropollutants in reclaimed water: Chemical analyses, ecological risk assessments, and in vivo endocrine-disrupting studies - Fei Zhao; Yinfei Hao; Qianru Xu; Zhineng Hao; Xinhui Li; Lihua Cheng; Dong Chen; Xueqing Shi; Yihua Xiao; Penghao Wei; Xuejun Bi (Science of The Total Environment, 2023)

Study on the wet dust collection mechanism of metal-based filter screens and the effect of its inclination angle on dust removal performance - Shuda Hu; Shihang Li; Hui Cheng; Hao Jin; Jun Hou; Changgeng Gui; Xingyue Chen; Liang Yuan; Fubao Zhou (Process Safety and Environmental Protection, 2023)

Association between meteorological factors and COVID-19 transmission in low- and middle-income countries: A time-stratified case-crossover study - Yu Wang; Yiran Lyu; Shilu Tong; Cheng Ding; Lan Wei; Mengying Zhai; Kaiqiang Xu; Ruiting Hao; Xiaochen Wang; Na Li; Yueyun Luo; Yonghong Li; et al. (Environmental Research, 2023)

Design and operation insights concerning a pilot-scale S0-driven autotrophic denitrification packed-bed process - Yi-Lu Sun; Zhuo-Ran Li; Xue-Ning Zhang; Heng Dong; Zhi-Min Qian; Shan Yi; Wei-Qin Zhuang; Hao-Yi Cheng; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Strong and continuous MXene/sodium alginate composite fibers prepared by immersion rotary jet spinning process with outstanding electromagnetic interference shielding performance - Guoxin Zhao; Chao Sui; Linlin Miao; Junjiao Li; Lei Wen; Gong Cheng; Chenxi Zhao; Weizhe Hao; Yuna Sang; Jiaxuan Li; Zhuochao Zhang; Yushun Zhao; et al. (Chemical Engineering Journal, 2023)

Pyrite coupled with steel slag to enhance simultaneous nitrogen and phosphorus removal in constructed wetlands - Ying Liu; Xiao-Hui Liu; Hong-Cheng Wang; Zhi-Ling Li; Bin Liang; Yi-Lu Sun; Hao-Yi Cheng; Shao-Yong Lu; Ai-Jie Wang (Chemical Engineering Journal, 2023)

Improvement in bacterial cellulose production by co-culturing Bacillus cereus and Komagataeibacter xylinus - Wenchao Li; Xinxin Huang; Huan Liu; Hao Lian; Bin Xu; Wenjin Zhang; Xuewen Sun; Wei Wang; Shiru Jia; Cheng Zhong (Carbohydrate Polymers, 2023)

Ammoniated straw incorporation increases maize grain yield while decreasing net greenhouse gas budget on the Loess Plateau, China - Jinchao Li; Yue Li; Zhipeng Yang; Yanxin Fang; Cheng Li; Yulong Shi; Nanping Lin; Qinge Dong; Kadambot H.M. Siddique; Hao Feng; Naijiang Wang (Agriculture, Ecosystems & Environment, 2023)

Competitive adsorption characteristics of VOCs and water vapor by activated carbon prepared from Fe/N-doped pistachio shell - Tangying Cheng; Jinjin Li; Xiuwei Ma; Linjun Yang; Lei Zhou; Hao Wu (Environmental Science and Pollution Research, 2023)

Nighttime light perspective in urban resilience assessment and spatiotemporal impact of COVID-19 from January to June 2022 in mainland China - Yaohui Liu; Wenyi Liu; Xinyu Zhang; Yu Lin; Guoqiang Zheng; Zhan Zhao; Hao Cheng; Lutz Gross; Xiaoli Li; Benyong Wei; Fei Su (Urban Climate, 2023)

Divergent accumulation of amino sugars and lignins mediated by soil functional carbon pools under tropical forest conversion - Tengteng Li; Hao Cheng; Yue Li; Zhijian Mou; Xiaomin Zhu; Wenjia Wu; Jing Zhang; Luhui Kuang; Jun Wang; Dafeng Hui; Hans Lambers; Jordi Sardans; et al. (Science of The Total Environment, 2023)

Climate changes in the Hexi Corridor, western China over the past 13.3 ka - Yanzhen Li; Rui Zhang; Hao Long; Peng Cheng; David B. Kemp; Ze Zhang; Chunju Huang; Mengyang Hou; Yue Li; Shizhen Jia; Zhixiang Wang; Liangcheng Tan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Corrigendum to “Aggravated multi-source air pollution exposure caused by open fires in China” [J. Clean. Prod. 394 (2023) 136402] - Xiaoyang Li; Tianhai Cheng; Hao Zhu; Xiaotong Ye (Journal of Cleaner Production, 2023)

Antimicrobial cellulose paper tuned with chitosan fibers for high-flux oil/water separation - Hao Ling; Lei Wang; Qixuan Lin; Quanbo Huang; Xiaoqian Zhang; Junli Ren; Ning Li; Cheng Zhou; Zhiwei Lin; Jingpeng Zhou; Wenguang Wei; Xiaohui Wang (Carbohydrate Polymers, 2023)

Carbon-containing additives changes the phosphorus flow by affecting humification and bacterial community during composting - Shuxin Li; Shaoqi Xu; Shuo Chen; Hao Zhang; Yabin Zhan; Kaixue Jia; Meidi Cheng; Yuquan Wei (Bioresource Technology, 2023)

Simulation of compound flooding in Japan using a nationwide model - Wei Huang; Yinglong Joseph Zhang; Zhuo Liu; Hao-Cheng Yu; Yi Liu; Sam Lamont; Yu Zhang; Feyera Hirpa; Ting Li; Brett Baker; Wang Zhan; Shabaz Patel; et al. (Natural Hazards, 2023)

Plasma cell-free DNA promise monitoring and tissue injury assessment of COVID-19 - Xin Jin; Yanqun Wang; Jinjin Xu; Yimin Li; Fanjun Cheng; Yuxue Luo; Haibo Zhou; Shanwen Lin; Fei Xiao; Lu Zhang; Yu Lin; Zhaoyong Zhang; et al. (Molecular Genetics and Genomics, 2023)
Coronavirus 2019 (COVID-19) is a complex disease that affects billions of people worldwide. Currently, effective etiological treatment of COVID-19 is still lacking; COVID-19 also causes damages to various organs that affects therapeutics and mortality of the patients. Surveillance of the treatment responses and organ injury assessment of COVID-19 patients are of high clinical value. In this study, we investigated the characteristic fragmentation patterns and explored the potential in tissue injury assessment of plasma cell-free DNA in COVID-19 patients. Through recruitment of 37 COVID-19 patients, 32 controls and analysis of 208 blood samples upon diagnosis and during treatment, we report gross abnormalities in cfDNA of COVID-19 patients, including elevated GC content, altered molecule size and end motif patterns. More importantly, such cfDNA fragmentation characteristics reflect patient-specific physiological changes during treatment. Further analysis on cfDNA tissue-of-origin tracing reveals frequent tissue injuries in COVID-19 patients, which is supported by clinical diagnoses. Hence, our work demonstrates and extends the translational merit of cfDNA fragmentation pattern as valuable analyte for effective treatment monitoring, as well as tissue injury assessment in COVID-19.

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

In-situ mechanochemically tailorable 2D gallium oxyselenide for enhanced optoelectronic NO2 gas sensing at room temperature - Tao Tang; Zhong Li; Yin Fen Cheng; Hua Guang Xie; Xuan Xing Wang; Yong Li Chen; Liang Cheng; Yi Liang; Xin Yi Hu; Chu Manh Hung; Nguyen Duc Hoa; Hao Yu; et al. (Journal of Hazardous Materials, 2023)

Evaluating the threshold limit value of acceptable exposure concentration for exposure to bioaerosols in a wastewater treatment plant: Reverse-quantitative microbial risk assessment and sensitivity analysis - Beibei Cui; Dongzi An; Haojun Li; Xi Luo; Hao Zhu; Ming Li; Xiaojun Ai; Jiaxin Ma; Wajid Ali; Cheng Yan (Journal of Hazardous Materials, 2023)

Preparation of underwater superoleophobic ZIF-67 composite membrane with high antibacterial activity and emulsion separation efficiency - Shuhao Xu; Qijin Tang; Shudi Li; Tengfei Liao; Huajing Cheng; Tong Lu; Nan Jiang; Zhong Lu; Cailong Zhou; Hao Yang (Journal of Environmental Chemical Engineering, 2023)

Important effects of polypropylene on migration of ciprofloxacin in groundwater - Yanna Chen; Cehui Mo; Ming Wu; Yanru Hao; Zhou Cheng; Guoping Lu; Qusheng Li; Bill X. Hu; Jianfeng Wu; Jichun Wu (Journal of Environmental Chemical Engineering, 2023)

Optimization of electrolysis process, storage conditions and sterilization effect of slightly acidic electrolytic water prepared by titanium suboxide electrode - Zhen Li; Xue Wang; Xinyuan Li; Siyuan Guo; Shanshan Li; Baoping Chen; Yi Cheng; Hao Xu; Wei Yan (Journal of Environmental Chemical Engineering, 2023)

The effect of interfacial tension on CO2 oil-based foam stability under different temperatures and pressures - Zhoujie Wang; Songyan Li; Dongliang Peng; Hao Cheng; Yaohui Wei (Fuel, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

A comparative study of different iron minerals on phosphorus capture from municipal wastewater and subsequent recovery as vivianite through acidogenic fermentation - Shi-Xu Wang; Yun-Xin Huang; Hao Wang; Yao-Yao Lu; Wen-Long He; Jing Li; Nian-Si Fan; Bao-Cheng Huang; Ren-Cun Jin (Chemical Engineering Journal, 2023)

Enhanced potassium-ion storage performance of bimetallic-sulfide based on regulatory reaction mechanism - Shengyang Li; Hao Chen; Qiusheng Zhang; Hongli Deng; Song Chen; Xiaohua Shen; Yizhi Yuan; Yifang Ding; Yingliang Cheng; Hongtao Sun; Jian Zhu; Bingan Lu (Chemical Engineering Journal, 2023)

Suppressing charge injection and preventing the extension of electrical trees of polymer-based composites through two-dimensional metal–organic frameworks nanosheets - Zhicheng Li; Zhongbin Pan; Xu Fan; Hao Wang; Yu Cheng; Xiangping Ding; Songhan Shi; Peng Li; Jinjun Liu; Jiwei Zhai (Chemical Engineering Journal, 2023)

Self-supported N-doped hierarchical Co3O4 electrocatalyst with abundant oxygen vacancies for acidic water oxidation - Xian Yang; Jun Cheng; Hao Li; Yang Xu; Weifeng Tu; Junhu Zhou (Chemical Engineering Journal, 2023)

Differential Diagnosis of DCIS and Fibroadenoma Based on Ultrasound Images: a Difference-Based Self-Supervised Approach - Jin Yin; Jia-Jun Qiu; Jing-Yan Liu; Yi-Yue Li; Qi-Cheng Lao; Xiao-Rong Zhong; Mengling Feng; Hao Du; Shao-Liang Peng; Yu-Lan Peng (Interdisciplinary Sciences: Computational Life Sciences, 2023)

OrMKK3 Influences Morphology and Grain Size in Rice - Ying Hua Pan; Li Jun Gao; Yun Tao Liang; Yan Zhao; Hai Fu Liang; Wei Wei Chen; Xing Hai Yang; Dong Jin Qing; Ju Gao; Hao Wu; Juan Huang; Wei Yong Zhou; et al. (Journal of Plant Biology, 2023)

The neuroprotective effects of peracetylated chitosan oligosaccharides against β-amyloid-induced cognitive deficits in rats - Cui Hao; Minmin Han; Wei Wang; Cheng Yang; Jigang Wang; Yunliang Guo; Tao Xu; Lijuan Zhang; Chunxia Li (Marine Life Science & Technology, 2023)

Kinetics of PCDD/Fs from feed to cow milk and its implications for food safety - Yanfen Hao; Chu Wang; Pu Wang; Jie Cheng; Hao Xian; Mei Liu; Zengwei Li; Jie Ma; Yingming Li; Ruiqiang Yang; Qinghua Zhang; Xiaoou Su; et al. (Science of The Total Environment, 2023)

The underlying mechanisms of PM2.5 and O3 synergistic pollution in East China: Photochemical and heterogeneous interactions - Yawei Qu; Tijian Wang; Cheng Yuan; Hao Wu; Libo Gao; Congwu Huang; Yasong Li; Mengmeng Li; Min Xie (Science of The Total Environment, 2023)

Air pollution exposure and heart failure: A systematic review and meta-analysis - Dongdong Zhang; Weiling Chen; Cheng Cheng; Hao Huang; Xi Li; Pei Qin; Chuanqi Chen; Xinping Luo; Ming Zhang; Jing Li; Xizhuo Sun; Yu Liu; et al. (Science of The Total Environment, 2023)

Quantum neuronal sensing of quantum many-body states on a 61-qubit programmable superconducting processor - Ming Gong; He-Liang Huang; Shiyu Wang; Chu Guo; Shaowei Li; Yulin Wu; Qingling Zhu; Youwei Zhao; Shaojun Guo; Haoran Qian; Yangsen Ye; Chen Zha; et al. (Science Bulletin, 2023)

Vulnerability of farmers and herdsmen households in Inner Mongolian plateau to arid climate disasters and their development model - Wenlong Li; Suocheng Dong; Haiying Lin; Fujia Li; Hao Cheng; Zhuang Jin; Shan Wang; Hasbaggen Zhang; Pengshen Hou; Bing Xia (Journal of Cleaner Production, 2023)

Effects of spray drying and freeze drying on the structure and emulsifying properties of yam soluble protein: A study by experiment and molecular dynamics simulation - Hao-nan Nie; Hui Dong; Yun-long Chen; Miao-miao Hao; Jia-nan Chen; Zi-cheng Tang; Qing-zheng Liu; Jiang-kuo Li; Xiang-bin Xu; You-lin Xue (Food Chemistry, 2023)

A new cyclopentenone derivative from Trichoderma atroviride HH-01 - Li Zhu; Jia-Peng Wang; Feng Hao; Dong Gan; Xiao-Ran Zhang; Chen-Zhe Li; Cheng-Yao Wang; Liang Zhang; Le Cai (Natural Product Research, 2023)

Quantitative Assessment of Climate Change Impacts on Forest Ecosystems - Dan Liu; Hao Yan; Cheng Long Yu; Shi Ping Yin; Cheng Wei Wang; Li Juan Gong (Forest Science, 2023)
Characterizing and predicting the response of terrestrial ecosystems to global change is part of the fundamental challenges of contemporary ecology and ecological conservation. The assessment of climate change impact on forest ecosystems has rarely used a multi-index fusion method for quantitative evaluation. We used forest distribution, net primary productivity, and vegetation coverage to establish an assessment model of the impact of climate change on forest ecosystems. We analyzed the change characteristics of these indicators in the Heilongjiang Province of China. Our results indicate the following: (1) from 2001 to 2019, the forest area in Heilongjiang Province ranged from 234,000 to 246,000 km2. The forest net primary productivity (NPP) ranged from 4.40 to 5.55 MgC·ha-1·yr-1, and the vegetation coverage ranged from 42.42% to 67.64%. The forest NPP and the vegetation coverage showed a significant upward trend. (2) The values of forest ecological roles were significantly positively correlated with the climatic potential. (3) The contribution rate of climate change to forest ecosystem change was negatively correlated with forest coverage, which varied from 4.79% to 18.07% in different regions (cities) of the province. Study Implications: Assessing the influence of climate on forest ecosystems comprehensively and accurately before the government prepares ecological measures is necessary. However, the responses of vegetation coverage and net primary productivity to climate change may not be consistent, so climate studies that consider forest ecosystem change trends by a single indicator may have confounding results. We established a model for evaluating the impact of climate change on forest ecosystems to solve this problem. This knowledge may provide a reference for the response, adaptation, and vulnerability assessment of forest ecosystems to climate change.

Elucidating colony bloom formation mechanism of a harmful alga Phaeocystis globosa (Prymnesiophyceae) using metaproteomics - Hua-Min Cheng; Shu-Feng Zhang; Xiao-Lian Ning; Jian-Xiang Peng; Dong-Xu Li; Hao Zhang; Kun Zhang; Lin Lin; Si-Qi Liu; Walker O. Smith; Da-Zhi Wang (Science of The Total Environment, 2023)

A mechanism study of methylene blue adsorption on seaweed biomass derived carbon: From macroscopic to microscopic scale - Ding Jiang; Hongping Li; Xiaoxue Cheng; Qifan Ling; Hao Chen; Bahram Barati; Quanfeng Yao; Abdelfatah Abomohra; Xun Hu; Pietro Bartocci; Shuang Wang (Process Safety and Environmental Protection, 2023)

Characterization of a novel Pseudomonas mosselii 9-1 capable of nitrate reduction to ammonium, ammonium assimilation, and denitrification in aerobic conditions - Xiaoni Cai; Ruijie Liu; Mengjie Cheng; Tianjia Liu; Yue Zhang; Xinke Li; Yanhua Zeng; Hao Long; Wei Ren; Zhen-yu Xie (Journal of Water Process Engineering, 2023)

Performance study of a double-regenerator room temperature magnetic refrigerator with 26 °C temperature span - Gao Lei; Wang Pengyu; Guo Yaru; Dai Mohan; Pei Hao; Huang Jiaohong; Jin Peiyu; Liu Cuilan; Zhang Yingde; Cheng Juan; Zhang Jianping; Li Leilei (International Journal of Refrigeration, 2023)

Decapentaplegic retards lipolysis during metamorphosis in Bombyx mori and Drosophila melanogaster - Wenliang Qian; Mengge Guo; Jian Peng; Tujing Zhao; Zheng Li; Yan Yang; Hao Li; Xing Zhang; Kirst King-Jones; Daojun Cheng (Insect Biochemistry and Molecular Biology, 2023)

Effects of chlorination on microplastics pollution: Physicochemical transformation and chromium adsorption - Manhong Miao; Bingqing Yu; Xuhua Cheng; Tianwei Hao; Yuanyuan Dou; Min Zhang; Yao Li (Environmental Pollution, 2023)

Severe shoot topping slows down berry sugar accumulation rate, alters the vine growth and photosynthetic capacity, and influences the flavoromics of Cabernet Sauvignon grapes in a semi-arid region - Hao-Cheng Lu; Meng-Bo Tian; Ning Shi; Xiao Han; Hui-Qing Li; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (European Journal of Agronomy, 2023)

Chronic exposure to environmentally relevant concentrations of carbamazepine interferes with anxiety response of adult female zebrafish through GABA /5-HT pathway and HPI axis - Cheng-Ting Xie; Mei-Ling Tan; Ying-Wen Li; Qi-Liang Chen; Yan-Jun Shen; Zhi-Hao Liu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

The eradication of biofilm for therapy of bacterial infected chronic wound based on pH-responsive micelle of antimicrobial peptide derived biodegradable microneedle patch - Xiao-Ling Lei; Kai Cheng; Yong Li; Zi-Tao Zhong; Xiao-Lin Hou; Lai-Bo Song; Fang Zhang; Jian-Hao Wang; Yuan-Di Zhao; Qiu-Ran Xu (Chemical Engineering Journal, 2023)

Identifying the hygroscopic properties of fine aerosol particles from diverse sources in urban atmosphere and the applicability in prediction of cloud nuclei - Jingye Ren; Fang Zhang; Lu Chen; Gang Cao; Mengyu Liu; Xue Li; Hao Wu; Yiling Cheng; Zhanqing Li (Atmospheric Environment, 2023)

Genetic and enzymatic characterization of two novel blaNDM-36, -37 variants in Escherichia coli strains - Wanshan Ma; Bo Zhu; Wen Wang; Qian Wang; Xiaodi Cui; Yujiao Wang; Xiutao Dong; Xiaofeng Li; Jianping Ma; Fang Cheng; Xiaohong Shi; Liang Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
The widespread of different NDM variants in clinical Enterobacterales isolates poses a serious public health concern, which requires continuous monitoring. In this study, three E. coli strains carrying two novel bla NDM variants of bla NDM-36, -37 were identified from a patient with refractory urinary tract infection (UTI) in China. We conducted antimicrobial susceptibility testing (AST), enzyme kinetics analysis, conjugation experiment, whole-genome sequencing (WGS), and bioinformatics analysis to characterize the bla NDM-36, -37 enzymes and their carrying strains. The bla NDM-36, -37 harboring E. coli isolates belonged to ST227, O9:H10 serotype and exhibited intermediate or resistance to all β-lactams tested except aztreonam and aztreonam/avibactam. The genes of bla NDM-36, -37 were located on a conjugative IncHI2-type plasmid. NDM-37 differed from NDM-5 by a single amino acid substitution (His261Tyr). NDM-36 differed from NDM-37 by an additional missense mutation (Ala233Val). NDM-36 had increased hydrolytic activity toward ampicillin and cefotaxime relative to NDM-37 and NDM-5, while NDM-37 and NDM-36 had lower catalytic activity toward imipenem but higher activity against meropenem in comparison to NDM-5. This is the first report of co-occurrence of two novel bla NDM variants in E. coli isolated from the same patient. The work provides insights into the enzymatic function and demonstrates the ongoing evolution of NDM enzymes.

Assessing the Coordinate Development Between Economy and Ecological Environment in China’s 30 Provinces from 2013 to 2019 - Bing Rong; Cheng-jun Chu; Zhen Zhang; Ya-ting Li; Shu-hao Yang; Qian Wang (Environmental Modeling & Assessment, 2023)

Pharmacokinetics and residue elimination of metalaxyl enantiomers in snakehead (Channa argus) - Hao Zhou; Meiyu Zhang; Qi Shan; Heqing Huang; Meiling Zhang; Shugui Liu; Jiawei Lin; Lisha Ma; Guangming Zheng; Lichun Li; Cheng Zhao; Xiaoxin Dai; et al. (Aquaculture, 2023)

Feeding the world using speed breeding technology - Ying Xu; Hongbing Luo; Hao Zhang; Wai-Shing Yung; Man-Wah Li; Hon-Ming Lam; Cheng Huang (Trends in Plant Science, 2023)

Continued decline of global soil moisture content, with obvious soil stratification and regional difference - Tianling Qin; Jianming Feng; Xin Zhang; Chenhao Li; Jingjing Fan; Cheng Zhang; Biqiong Dong; Hao Wang; Denghua Yan (Science of The Total Environment, 2023)

Impact of satellite AOD data on top-down estimation of biomass burning particulate matter emission - Xiaotong Ye; Tianhai Cheng; Xiaoyang Li; Hao Zhu (Science of The Total Environment, 2023)

Corrigendum to “Induction of core symptoms of autism spectrum disorders by in vivo CRISPR/Cas9-based gene editing in the brain of adolescent rhesus monkeys” [Sci. Bull. 66(9) (2021) 937–946] - Shi-Hao Wu; Xiao Li; Dong-Dong Qin; Lin-Heng Zhang; Tian-Lin Cheng; Zhi-Fang Chen; Bin-Bin Nie; Xiao-Feng Ren; Jing Wu; Wen-Chao Wang; Ying-Zhou Hu; Yi-lin Gu; et al. (Science Bulletin, 2023)

Rapid origin identification of chrysanthemum morifolium using laser-induced breakdown spectroscopy and chemometrics - Nan Hao; Xin Gao; Qian Zhao; Peiqi Miao; Jiawei Cheng; Zheng Li; Changqing Liu; Wenlong Li (Postharvest Biology and Technology, 2023)

Bioimmobilization and transformation of chromium and cadmium in the fungi-microalgae symbiotic system - Junjun Wang; Qinghua Tian; Linlin Cui; Jinju Cheng; Hao Zhou; Yejuan Zhang; Anan Peng; Li Shen (Journal of Hazardous Materials, 2023)

Appropriate oxygen vacancies and Mo-N bond synergistically modulate charge transfer dynamics of MoO3−x/S-CN for superior photocatalytic disinfection: Unveiling synergistic effects and disinfection mechanism - Ya-Ya Yang; Cheng-Gang Niu; Da-Wei Huang; Hai Guo; Hao-Peng Feng; Lu Li; Hui-Yun Liu; Qian-Qian Fan; Meng-Zhu Qin (Journal of Hazardous Materials, 2023)

Fabrication of whey-protein-stabilized G/O/W emulsion for the encapsulation and retention of -ascorbic acid and α-tocopherol - Muhammad Aslam Khan; Huayan Bao; Hao Cheng; Shuai Feng; Yanmei Wang; Li Liang (Journal of Food Engineering, 2023)

Aggravated multi-source air pollution exposure caused by open fires in China - Xiaoyang Li; Tianhai Cheng; Hao Zhu; Xiaotong Ye (Journal of Cleaner Production, 2023)

Accelerated Fe(III)/Fe(II) cycle for rapid elimination of Rhodamine B by a novel Mo2C co-catalytic Fe2+/H2O2 system - Hao Cheng; Xinyan Li; Chao Huang; Jian Zhu; Ping Wang; Heng Cao; Chongling Feng; Dingxun Ling; Hao Liu; Min Cheng (Journal of Cleaner Production, 2023)

Hybrid persulfate/sonocatalysis for degradation of acid orange 7 in the presence of Ag2O/CuWO4 composite: Operating parameters and sonocatalytic mechanism - Yang-Cheng Liu; Xuan Liu; Xin Wang; Zi-Hao Li; Chang-Lan Chen; Zheng Xiang (Journal of Cleaner Production, 2023)

Manipulating the severe shoot topping delays the harvest date and modifies the flavor composition of Cabernet Sauvignon wines in a semi-arid climate - Hao-Cheng Lu; Li Hu; Yao Liu; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (Food Chemistry, 2023)

Volatomics of ‘Cabernet Sauvignon’ grapes and wines under the fan training system revealed the nexus of microclimate and volatile compounds - Meng-Bo Tian; Yao Liu; Hao-Cheng Lu; Li Hu; Yu Wang; Chi-Fang Cheng; Wu Chen; Shu-De Li; Fei He; Chang-Qing Duan; Jun Wang (Food Chemistry, 2023)

Fe, N, S co-doped cellulose paper carbon fibers as an air-cathode catalyst for microbial fuel cells - Demin Jiang; Huina Chen; Hao Xie; Kai Cheng; Liang Li; Kun Xie; Yuqiao Wang (Environmental Research, 2023)

Fouling characteristic of reverse osmosis membrane for reclaimed water treatment operating under cold winter condition - Zi-Hao Li; Guo-Wei Ni; Jin-Long Wang; Lin Zhou; Qiang Yang; Pei-Zhuo Li; Ai-Li Gao; Tong Yu; Li-Hua Cheng; Xue-Jun Bi (Desalination, 2023)

Three birds with one stone: Contemporaneously boosting passive, active and self-healing properties for long-term anticorrosion coatings - Meng Cheng; Junhao Liu; Yuqi Liu; Hao Jiang; Chunling Li; Shuangqing Sun; Songqing Hu (Chemical Engineering Journal, 2023)

Effect of landing disturbance caused by capping materials on the control efficiency of contaminated sediment capping - Bin Wang; Wei Zhu; Yong Wu; Hao Hou; Lin Cheng; Xiaoge Xu; Yuehong Li; Xiaowei Lin; Chengxin Fan (Journal of Soils and Sediments, 2023)

Plastic film-mulched ridges and straw-mulched furrows increase soil carbon sequestration and net ecosystem economic benefit in a wheat-maize rotation - Xiaoqi Luo; Cheng Li; Nanping Lin; Naijiang Wang; Xiaosheng Chu; Hao Feng; Haixin Chen (Agriculture, Ecosystems & Environment, 2023)

High cholesterol intake remodels cholesterol turnover and energy homeostasis in Nile tilapia (Oreochromis niloticus) - Rui-Xin Li; Ling-Yun Chen; Samwel M. Limbu; Yu-Cheng Qian; Wen-Hao Zhou; Li-Qiao Chen; Yuan Luo; Fang Qiao; Mei-Ling Zhang; Zhen-Yu Du (Marine Life Science & Technology, 2023)
The roles of dietary cholesterol in fish physiology are currently contradictory. The issue reflects the limited studies on the metabolic consequences of cholesterol intake in fish. The present study investigated the metabolic responses to high cholesterol intake in Nile tilapia ( Oreochromis niloticus ), which were fed with four cholesterol-contained diets (0.8, 1.6, 2.4 and 3.2%) and a control diet for eight weeks. All fish-fed cholesterol diets showed increased body weight, but accumulated cholesterol (the peak level was in the 1.6% cholesterol group). Then, we selected 1.6% cholesterol and control diets for further analysis. The high cholesterol diet impaired liver function and reduced mitochondria number in fish. Furthermore, high cholesterol intake triggered protective adaptation via (1) inhibiting endogenous cholesterol synthesis, (2) elevating the expression of genes related to cholesterol esterification and efflux, and (3) promoting chenodeoxycholic acid synthesis and efflux. Accordingly, high cholesterol intake reshaped the fish gut microbiome by increasing the abundance of Lactobacillus spp. and Mycobacterium spp., both of which are involved in cholesterol and/or bile acids catabolism. Moreover, high cholesterol intake inhibited lipid catabolic activities through mitochondrial β-oxidation, and lysosome-mediated lipophagy, and depressed insulin signaling sensitivity. Protein catabolism was elevated as a compulsory response to maintain energy homeostasis. Therefore, although high cholesterol intake promoted growth, it led to metabolic disorders in fish. For the first time, this study provides evidence for the systemic metabolic response to high cholesterol intake in fish. This knowledge contributes to an understanding of the metabolic syndromes caused by high cholesterol intake or deposition in fish.

Life cycle assessment of integrated bioelectrochemical-constructed wetland system: environmental sustainability and economic feasibility evaluation - Ying-Ke Fang; Hong-Cheng Wang; Pan-Hao Fang; Bin Liang; Kun Zheng; Qi Sun; Xi-Qi Li; Ran Zeng; Ai-Jie Wang (Resources, Conservation and Recycling, 2023)

Four new Myrioneuron alkaloids from Mycetia effusa (Myrioneuron effusum) - Xiao-Hui Li; Jia-Hui Zhang; Yu Zhang; Ying-Tong Di; Yu-Cheng Gu; Mingming Cao; Xiao-Jiang Hao (Phytochemistry Letters, 2023)

A new phragmalin-type limonoid from the roots of Trichilia sinensis - Shou-Bai Liu; Jin-Ling Yang; Hui-Qin Chen; Cheng-min Yang; Hao Wang; Cai-Hong Cai; Jing-Zhe Yuan; Wen-Li Mei; Hao-Fu Dai (Phytochemistry Letters, 2023)

Introducing water factors improves simulations of maize stomatal conductance models under plastic film mulching in arid and semi-arid irrigation areas - Cheng Li; Naijiang Wang; Xiaoqi Luo; Yue Li; Tibin Zhang; Dianyuan Ding; Qin'ge Dong; Hao Feng; Wenxin Zhang (Journal of Hydrology, 2023)

Real-world emission characteristics of carbonyl compounds from agricultural machines based on a portable emission measurement system - Wenhan Yu; Xianbao Shen; Bobo Wu; Lei Kong; Kaijie Xuan; Cheng Zhao; Xinyue Cao; Xuewei Hao; Xin Li; Hanyu Zhang; Zhiliang Yao (Journal of Environmental Sciences, 2023)

Heterogeneous degradation of cefotaxime sodium with peroxymonosulfate activated by an effective and magnetically separable Ni0.5Zn0.5Fe2O4 catalyst - Hangdao Qin; Hao Cheng; Wei Shi; Sizhan Wu; Jing Chen; Jiming Huang; Hui Li (Journal of Environmental Chemical Engineering, 2023)

Nitrogen-doped porous biochar for selective adsorption of toluene under humid conditions - Tangying Cheng; Ye Bian; Jinjin Li; Xiuwei Ma; Linjun Yang; Lei Zhou; Hao Wu (Fuel, 2023)

Synthesis, characterization, and anticancer activity of protamine sulfate stabilized selenium nanoparticles - Wanwen Chen; Xiaojiao Li; Hao Cheng; Xiaobei Zhan; Wenshui Xia (Food Research International, 2023)

Epitaxial deposition of Zn (0 0 2) for stable zinc metal anodes - Yao Lu; Tao Wang; Zheng Li; Hao Cheng; Ke Peng; Zhongliang Tian (Chemical Engineering Journal, 2023)

Eco-friendly recyclable high performance ramie yarn reinforced polyimine vitrimer composites - Pandeng Li; Cheng Hao; Huihui Wang; Tian He; Tong Shu; Cong Li; Longjiang Yu; Ning Yan (Chemical Engineering Journal, 2023)

3D-printed SiC lattices integrated with lightweight quartz fiber/silica aerogel sandwich structure for thermal protection system - Hui Mei; Hao Li; Zhipeng Jin; Liangjun Li; Dou Yang; Chengyu Liang; Laifei Cheng; Litong Zhang (Chemical Engineering Journal, 2023)

Insight into FeOOH-mediated advanced oxidation processes for the treatment of organic polluted wastewater - Hao Weng; Yang Yang; Chen Zhang; Min Cheng; Wenjun Wang; Biao Song; Hanzhuo Luo; Deyu Qin; Cheng Huang; Fanzhi Qin; Keteng Li (Chemical Engineering Journal, 2023)

Different roles of primary and secondary sources in reducing PM2.5: Insights from molecular markers in Pearl River Delta, South China - Kong Yang; Duo-Hong Chen; Xiang Ding; Jun Li; Yu-Qing Zhang; Tao Zhang; Qiao-Yun Wang; Jun-Qi Wang; Qian Cheng; Hao Jiang; Ping Liu; Zi-Rui Wang; et al. (Atmospheric Environment, 2023)

Synthetic Biology Technologies And Genetically Engineering Strategies For Enhanced Cell Therapeutics - Siyu Li; Hao Tang; Cheng Li; Jiajia Ma; Maqsood Ali; Qi Dong; Jiajia Wu; Yang Hui; Chongran Sun (Stem Cell Reviews and Reports, 2023)

When Does a Light Sphere Break Ice Plate Most by Using Its Net Buoyance? - Bao-Yu Ni; Hao Tan; Shao-Cheng Di; Chen-Xi Zhang; Zhiyuan Li; Luofeng Huang; Yan-Zhuo Xue (Journal of Marine Science and Engineering, 2023)
A free-rising buoyant sphere can break an ice plate floating above it. The problem is when the light sphere breaks the ice plate most, or the optimal relative density of the sphere which can break the ice plate the most severely. This experimental study was done to answer this problem. A set of experimental devices were designed, and a high-speed camera system was adopted to record the whole dynamic process, including the free-rising of the sphere, the collision between the sphere and the ice plate, the crack initiation and propagation, as well as the breakup of the ice plate. The failure mode of the ice plate under impact load was analyzed. It was found that conical cracks were formed under the reflected tensile wave at the top surface of the ice plate. On this basis, the influences of ice thickness, the initial submergence depth, and the relative density of the sphere on icebreaking were further investigated. An optimal relative density of the sphere was found when the sphere was released at a certain initial submergence depth, at which point the ice was damaged the most severely. For example, when the dimensionless initial submergence depth of the sphere was 2.31, the optimal relative density of the sphere was close to 0.4, with the probability of the ice plate breakup as high as 91.7%. It was also found from the experiments that the degree of damage to the ice plate correlated well with the kinetic energy of the sphere just before collision. Results showed that the optimal relative density can be estimated by theoretical analysis of the kinetic energy of the sphere, which will provide a reference for potential icebreaking applications in the future.

Covalent organic frameworks@ZIF-67 derived novel nanocomposite catalyst effectively activated peroxymonosulfate to degrade organic pollutants - Yuanyuan Li; Jingbo Feng; Yan Zhang; Chen Wang; Junjie Hao; Yukun Wang; Yinyin Xu; Xiuwen Cheng (Chemosphere, 2023)

Residue depletion of danofloxacin in Yellow River carp (Cyprinus carpio haematopterus) following multiple oral administration - Zhe-Wen Song; Fang Yang; Yue Liu; Hao-Tian Shao; Mei Zhang; Jun-Cheng Chen; Kai-Li Ma; Fan Yang (Aquaculture, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Mid- to late Holocene vegetation response to relative sea-level fluctuations recorded by multi-proxy evidence in the Subei Plain, eastern China - Yu Cheng; Junwu Shu; Shefeng Hao; Bingfei Gao; Xiangqian Li; Feng Yuan; Xinqing Zou (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Regeneration mechanism of a novel high-performance biochar mercury adsorbent directionally modified by multimetal multilayer loading - Li Jia; Peng Cheng; Yue Yu; Shi-hu Chen; Chen-xing Wang; Ling He; Hao-tian Nie; Jian-cheng Wang; Jian-chun Zhang; Bao-guo Fan; Yan Jin (Journal of Environmental Management, 2023)

Spatial–temporal pattern, driving mechanism and optimization policies for embodied carbon emissions transfers in multi-regional tourism: Case study of provinces in China - Suocheng Dong; Bing Xia; Fujia Li; Hao Cheng; Zehong Li; Yu Li; Wenbiao Zhang; Yang Yang; Qian Liu; Shantong Li (Journal of Cleaner Production, 2023)

Atmospheric environment monitoring technology and equipment in China: A review and outlook - Youwen Sun; Ting Yang; Huaqiao Gui; Xin Li; Weigang Wang; Jun Duan; Shushuai Mao; Hao Yin; Bin Zhou; Jianlei Lang; Haijin Zhou; Cheng Liu; et al. (Journal of Environmental Sciences, 2023)

Region, vintage, and grape maturity co-shaped the ionomic signatures of the Cabernet Sauvignon wines - Xiao Han; Hao-Cheng Lu; Yu Wang; Xiao-Tong Gao; Hui-Qing Li; Meng-Bo Tian; Ning Shi; Ming-Yu Li; Xiao-Li Yang; Fei He; Chang-Qing Duan; Jun Wang (Food Research International, 2023)

Smart polymer with rapid self-healing and early corrosion reporting capabilities: Design, performance and mechanism - Hao Jiang; Zhikun Wang; Meng Cheng; Wuting Pang; Yizeng Mou; Fanjie Meng; Chunling Li; Shuangqing Sun; Songqing Hu; Zhigang Di; Bingjie Lian (Chemical Engineering Journal, 2023)

O-hetero-Fe-N3.6 active sites in ZIF-derived carbon nanotubes for the electrocatalytic oxygen evolution reaction - Xian Yang; Jun Cheng; Xiao Yang; Yang Xu; Hao Li; Weifu Sun; Weifeng Tu; Junhu Zhou (Chemical Engineering Journal, 2023)

Nitrogen and phosphorus co-doped porous carbons (NPCs) for peroxydisulfate (PDS) activation towards tetracycline degradation: Defects enhanced adsorption and non-radical mechanism dominated by electron transfer - Minxian Cheng; Yichu Zhang; Bo Lai; Lingzhen Wang; Shengjiong Yang; Kailong Li; Dongqi Wang; Yaoguo Wu; Guang-Hao Chen; Jin Qian (Chemical Engineering Journal, 2023)

An injectable, self-healing composite hydrogel with enhanced near-infrared photo-antibacterial therapeutic effects for accelerated wound healing - Jiameng Wang; Hao Cheng; Weiyi Chen; Peide Han; Xiaohong Yao; Bin Tang; Wangping Duan; Pengcui Li; Xiaochun Wei; Paul K. Chu; Xiangyu Zhang (Chemical Engineering Journal, 2023)

Effect of different vegetation restoration on soil properties in the semi-arid Loess Plateau of China - Wenjie Wu; Guangjie Chen; Tingfang Meng; Cheng Li; Hao Feng; Bingcheng Si; Kadambot H.M. Siddique (CATENA, 2023)

Identification of two migratory colon ILC2 populations differentially expressing IL-17A and IL-5/IL-13 - Hongzhi Liu; Liang Li; Yanyun Hao; Jialu Li; Zhaoyuan Liu; Jingjing Qi; Jingjing Zhang; Ningbo Wu; Dandan Wu; Caixia Gao; Lei Chen; Lei Shen; et al. (Science China Life Sciences, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Distribution and changes in microplastics in Taihu Lake and cyanobacterial blooms formed by the aggregation of Microcystis colonies - Bin Wang; Wei Zhu; Silin Wu; Hao Hou; Lin Cheng; Xiaoge Xu; Yuehong Li; Xiaowei Lin; Zongpu Xue (Environmental Science and Pollution Research, 2022)

Passive Cavitation Enhancement Mapping via an Ultrasound Dual-Mode phased array to monitor blood-brain barrier opening - Trung Nguyen Hoang; Hsiang-Ching Lin; Chih-Hong Tsai; Cheng-Kai Jan; Hao-Li Liu (Journal of Medical and Biological Engineering, 2022)

Effect of nitrogen functional groups on competitive adsorption between toluene and water vapor onto nitrogen-doped spherical resorcinol-formaldehyde resin-based activated carbon - Jinjin Li; Tangying Cheng; Xiuwei Ma; Xueyan Hou; Hao Wu; Linjun Yang (Environmental Science and Pollution Research, 2022)

Dissolved organic matter–assisted phytoremediation potential of cotton for Cd-contaminated soil: a relationship between dosage and phytoremediation efficiency - Tao Min; Tong Luo; Hao He; Jie Qin; Yan Wang; Liyang Cheng; Sibo Ru; Junhua Li (Environmental Science and Pollution Research, 2022)

Large-scale comparative transcriptome analysis of Nicotiana tabacum response to Ralstonia solanacearum infection - Muna Alariqi; Hao Wei; Junqi Cheng; Yiwen Sun; Hanyue Zhu; Tianwang Wen; Yapei Li; Chenglin Wu; Shuangxia Jin; Jinglin Cao (Plant Biotechnology Reports, 2022)

Immunogenicity and protective efficacy of a DNA vaccine inducing optimal expression of the SARS-CoV-2 S gene in hACE2 mice - Zhuo-xin Li; Sheng Feng; He Zhang; Xin-yu Zhuang; Chao Shang; Shi-yu Sun; Ji-cheng Han; Yu-biao Xie; Jin-yong Zhang; Wei Wang; Cheng-hui Li; Guan-yu Zhao; et al. (Archives of Virology, 2022)

Ferroptosis induced by the biocontrol agent Pythium oligandrum enhances soybean resistance to Phytophthora sojae - Yang Cheng; Huanxin Zhang; Wenyi Zhu; Qing Li; Rui Meng; Kun Yang; Ziqian Guo; Ying Zhai; Haijing Zhang; Rui Ji; Hao Peng; Daolong Dou; et al. (Environmental Microbiology, 2022)
Ferroptosis is a newly discovered form of cell death accompanied by iron accumulation and lipid peroxidation. Both biotic and abiotic stresses can induce ferroptosis in plant cells. In the case of plant interactions with pathogenic Phytophthora oomycetes, the roles of ferroptosis are still largely unknown. Here, we performed transcriptome analysis on soybean plants treated with the biocontrol agent Pythium oligandrum , a soilborne and non‐pathogenic oomycete capable of inducing plant resistance against Phytophthora sojae infection. Expression of homologous soybean genes involved in ferroptosis and resistance was reprogrammed upon P. oligandrum treatment. Typical hallmarks for characterizing ferroptosis were detected in soybean hypocotyl cells, including decreased glutathione (GSH) level, accumulation of ferric ions, and lipid peroxidation by reactive oxygen species (ROS). Meanwhile, ferroptosis‐like cell death was triggered by P. oligandrum to suppress P. sojae infection in soybean. Protection provided by P. oligandrum could be attenuated by the ferroptosis inhibitor ferrostatin‐1 (Fer‐1), suggesting the critical role of ferroptosis in soybean resistance against P. sojae . Taken together, these results demonstrate that ferroptosis is a P. oligandrum ‐inducible defence mechanism against oomycete infection in soybean.

Removal of Cd from contaminated farmland soil by washing with residues of traditional Chinese herbal medicine extracts - Yi Wang; Yuan Li; Shuai Yang; Qi-hao Wang; Shao-cheng Si; Han-yi Mei; Guo-ming Liu; Xiang-liang Pan; Yong-ming Luo (Environmental Science and Pollution Research, 2022)

Experimental Investigation of the Dynamic Behavior of Submerged Floating Tunnels under Regular Wave Conditions - Fang Wang; Ke Li; Bo Huang; Liang Cheng; Hao Ding (Journal of Marine Science and Engineering, 2022)
Submerged floating tunnels (SFTs) are an innovative traffic structure for transportation in deep and long-distance ocean environments. SFTs have the risk of being subjected to wave action in the complex ocean environment. Therefore, in order to ensure the safety and stability of SFTs during their service, the dynamic behavior of an SFT subjected to the action of waves is experimentally investigated in this study. Based on the wave–current flume, a physical scale-model experiment of an SFT for studying the dynamic behavior of an SFT subjected to regular waves interactions is deeply and thoroughly explored. The results show that the wave outputs from the wave-making system are verified to be reliable. The influence of major load parameters on the dynamic behavior of the SFT are deeply and thoroughly explored. The effects of wave height and wave period on acceleration, wave pressure, anchor cable force and displacement in an SFT are discussed. This experimental study has theoretical and practical significant for SFT design and safety.

What are the disease burden and its sensitivity analysis of workers exposing to Staphylococcus aureus bioaerosol during warm and cold periods in a wastewater treatment plant? - Jiaxin Ma; Dongzi An; Beibei Cui; Manli Liu; Hao Zhu; Ming Li; Xiaojun Ai; Wajid Ali; Cheng Yan (Environmental Science and Pollution Research, 2022)

Quantitative microbial risk assessment with nasal/oral breathing pattern for S. aureus bioaerosol emission from aeration tanks and residual sludge storage yard in a wastewater treatment plant - Cheng Yan; Xiao-yan Zhao; Xi Luo; Dong-zi An; Hao Zhu; Ming Li; Xiao-jun Ai; Wajid Ali (Environmental Science and Pollution Research, 2022)

Spatial and seasonal variation and sources of deposition fluxes of polycyclic aromatic hydrocarbons (PAHs) in Shanghai - Jian Wu; Chenyan Sha; Dayan Li; Cheng Shen; Hao Tang; Shenfa Huang (Environmental Science and Pollution Research, 2022)

Contact toxicity and repellence of essential oil from Senecio scandens and its major components against three stored product insects - Fang He; Jing-Yu Liu; Li-Jiang Chen; Zi-Qian Cheng; Meng-Qi Cheng; Shu-Shan Du; Yu-Li Sang; Yan-Jun Hao (Natural Product Research, 2022)

Association of urinary or blood heavy metals and mortality from all causes, cardiovascular disease, and cancer in the general population: a systematic review and meta-analysis of cohort studies - Xianwei Guo; Wanying Su; Ning Li; Qiuxia Song; Hao Wang; Qiwei Liang; Yaru Li; Scott Lowe; Rachel Bentley; Zhen Zhou; Evelyn J. Song; Ce Cheng; et al. (Environmental Science and Pollution Research, 2022)

Genome-wide association study of SARS-CoV-2 infection in Chinese population - Jie Fan; Quan-Xin Long; Ji-Hua Ren; Hao Chen; Meng-Meng Li; Zheng Cheng; Juan Chen; Li Zhou; Ai-Long Huang (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Synthesis and in vitro biological evaluation of novel dendrocandin analogue as potential anti-tumor agent - Jing-Yun Yan; Hao-Nan Yang; Ning Yang; Yin-Rong Xie; Xiu-Li Sun; Ye-Wei Huang; Cheng-Ting Zi; Xuan-Jun Wang; Jun Sheng (Natural Product Research, 2022)

Armochaetoglasins J and K: new cytochalasans from Chaetomium globosum - Li Cheng; Xi Zheng; Qin Li; Meng-Sha Wei; Chun-Mei Chen; Hu-Cheng Zhu; Chang-Li Zeng; Xin-Cai Hao; Yong-Hui Zhang (Natural Product Research, 2022)

A Three-Dimensional Slip Velocity Model for Water-Lubricated Hydrodynamic Journal Bearings - Yandong Gu; Jinwu Cheng; Hao Sun; Ao Liang; Li Cheng (Journal of Marine Science and Engineering, 2022)
Hydrodynamic journal bearings, coated with polytetrafluoroethylene (PTFE) and lubricated by water, have been widely used in ships and large-scale pumps, and the function is to maintain the stability of rotor system. However, slip velocity exists on the PTFE-coated surface, whose effect is still an open question. This study aims to investigate the static characteristics of water-lubricated hydrodynamic journal bearings under three-dimensional slip velocity boundary conditions. Firstly, under the non-slip boundary condition, the CFD (computational fluid dynamics) method with ANSYS Fluent is verified based on the Reynolds lubrication equation and the open literature. Then, a three-dimensional slip velocity equation that is based on the Navier slip velocity boundary condition is proposed and embedded into Fluent. Finally, the effects of slip length on the static characteristics are analyzed. Under the same eccentricity ratio, with the increase in slip length, the load capacity decreases due to the decrease of the pressure circumferential gradient, and the friction power decreases. Under the same eccentricity ratio and the same slip length, with the increase in the attitude angle, the load capacity and friction power increase. However, under the non-slip boundary condition, the effects of attitude angle on the load capacity and friction power are insignificant. This paper could provide a reference for studying slip velocity in the hydrodynamic journal bearing.

LncRNA TARID induces cell proliferation through cell cycle pathway associated with coronary artery disease - Zheng Cheng; Yonghong Zhang; Yang Zhuo; Jie Fan; Ying Xu; Mengmeng Li; Hao Chen; Li Zhou (Molecular Biology Reports, 2022)

Experimental Investigation of Wave-Induced Forces on a Large Quasi-Elliptical Cylinder during Extreme Events - Zhiying Yang; Hao Ding; Ke Li; Liang Cheng; Bo Huang; Qingyang Ren (Journal of Marine Science and Engineering, 2022)
Large quasi-elliptical cylinders are extensively used in ocean engineering. To enhance a better understanding of the hydrodynamic wave force on such quasi-elliptical cylinders during extreme events, a series of experiments on extreme wave interaction with a quasi-elliptical cylinder were conducted. A series of waves with various wave heights, wave periods, and wave incident directions were tested to investigate the wave parameter effect and wave directionality effect on the wave forces on the quasi-elliptical structure. The experimental results indicate that the extreme wave-induced forces on the quasi-elliptical cylinder are strongly correlated to the wave period and wave incident direction. The peak forces on the quasi-elliptical model do not vary monotonically with the increasing wave period but show an increase followed by a decrease. Both the longitudinal and transversal forces are significantly increased when the wave incident direction changes from 0° to 45° and the wave directionality effect is enhanced when the wave period is decreased. Additionally, the inertial force equation was applied to the wave force estimation for such quasi-elliptical cylinders, and the inertia coefficient CM was fitted based on the experimental results of α = 0°.

Coupling effect of biocementation-fiber reinforcement on mechanical behavior of calcareous sand for ocean engineering - Chao-Sheng Tang; Hao Li; Xiao-Hua Pan; Li-Yang Yin; Liang Cheng; Qing Cheng; Bo Liu; Bin Shi (Bulletin of Engineering Geology and the Environment, 2022)

Influence of the NAO on Wintertime Surface Air Temperature over East Asia: Multidecadal Variability and Decadal Prediction - Jianping Li; Tiejun Xie; Xinxin Tang; Hao Wang; Cheng Sun; Juan Feng; Fei Zheng; Ruiqiang Ding (Advances in Atmospheric Sciences, 2022)
In this paper, we investigate the influence of the winter NAO on the multidecadal variability of winter East Asian surface air temperature (EASAT) and EASAT decadal prediction. The observational analysis shows that the winter EASAT and East Asian minimum SAT (EAmSAT) display strong in-phase fluctuations and a significant 60–80-year multidecadal variability, apart from a long-term warming trend. The winter EASAT experienced a decreasing trend in the last two decades, which is consistent with the occurrence of extremely cold events in East Asia winters in recent years. The winter NAO leads the detrended winter EASAT by 12–18 years with the greatest significant positive correlation at the lead time of 15 years. Further analysis shows that ENSO may affect winter EASAT interannual variability, but does not affect the robust lead relationship between the winter NAO and EASAT. We present the coupled oceanic-atmospheric bridge (COAB) mechanism of the NAO influences on winter EASAT multidecadal variability through its accumulated delayed effect of ∼15 years on the Atlantic Multidecadal Oscillation (AMO) and Africa–Asia multidecadal teleconnection (AAMT) pattern. An NAO-based linear model for predicting winter decadal EASAT is constructed on the principle of the COAB mechanism, with good hindcast performance. The winter EASAT for 2020–34 is predicted to keep on fluctuating downward until ∼2025, implying a high probability of occurrence of extremely cold events in coming winters in East Asia, followed by a sudden turn towards sharp warming. The predicted 2020/21 winter EASAT is almost the same as the 2019/20 winter.

Circular RNA circ_0008934 promotes hepatocellular carcinoma growth and metastasis through modulating miR-1305/TMTC3 axis - Jia-Xi Li; Jin-Jiang Wang; Zhou-Feng Deng; Hao Zheng; Chun-Mei Yang; Ying Yuan; Cheng Yang; Fang-Fang Gu; Wei-Qi Wu; Guang-Lei Qiao; Li-Jun Ma (Human Cell, 2022)

A comprehensive exploration on the health risk quantification assessment of soil potentially toxic elements from different sources around large-scale smelting area - Chang-Chen Huang; Li-Mei Cai; Yao-Hui Xu; Luo Jie; Lai-Guo Chen; Guo-Cheng Hu; Hui-Hao Jiang; Xu-Bang Xu; Jing-Xian Mei (Environmental Monitoring and Assessment, 2022)

A New Species of Paradiplozoon (Monogenea: Diplozoidae), A Gill Parasite of the Schizothorax Fish (Cyprinidae: Schizothoracinae) from the Yarkand River, Xinjiang, China - Kadirden Arken; Cui-Lan Hao; Ai-Ming Guo; Wen-Run Zhang; Meng-Jie Rong; Wuljan Kamal; Sheng-Li Tian; Munira Kadir; Cheng Yue (Acta Parasitologica, 2022)

Evaluating carbon emissions of China’s waste management strategies for building refurbishment projects: contributing to a circular economy - Wenting Ma; Jian Li Hao; Cheng Zhang; Luigi Di Sarno; Adam Mannis (Environmental Science and Pollution Research, 2022)

Different changes in pre- and postsynaptic components in the hippocampal CA1 subfield after transient global cerebral ischemia - Yan Zhang; Bai-Hong Tan; Shuang Wu; Cheng-Hao Wu; Jia-Le Suo; Yue Gui; Cheng-Mei Zhou; Yan-Chao Li (Brain Structure and Function, 2022)

Dietary Calcium Alleviates Fluorine-Induced Liver Injury in Rats by Mitochondrial Apoptosis Pathway - Haojie Li; Zijun Hao; Li Wang; Jiarong Yang; Yangfei Zhao; Xiaofang Cheng; Haiyan Yuan; Jinming Wang (Biological Trace Element Research, 2022)

Using computational fluid dynamic simulation with Flow-3D to reveal the origin of the mushroom stone in the Xiqiao Mountain of Guangdong, China - Jian-cheng Li; Wei Wang; Yan-ming Zheng; Xiao-hao Wen; Jing Feng; Li Sheng; Chen Wang; Ming-kun Qiu (Journal of Mountain Science, 2022)

GC–MS fingerprints of essential oils from agarwood grown in wild and artificial environments - Cheng-piao Tian; Xing-dong Yao; Jia-hao Lu; Li-qun Shen; Ai-qun Wu (Trees, 2021)

The adsorption properties of microporous activated carbon prepared from pistachio nut shell for low-concentration VOCs under low-medium temperatures - Tangying Cheng; Jinjin Li; Xiuwei Ma; Lei Zhou; Hao Wu; Linjun Yang (Environmental Science and Pollution Research, 2021)

Establishment of an immortalized cell line derived from the pupal ovary of Mythimna separata (Lepidoptera: Noctuidae) and identification of the cell source - Yan Tong; Lu-Qiang Cheng; Xuan Li; Xu-Peng Yu; Rui-Hao Shu; Ji-Hong Zhang; Qian Meng; Qi-Lian Qin; Kai Tang; Jian-Xiang Xu; Huan Zhang (Cell and Tissue Research, 2021)

Impact of rhizosphere microorganisms on arsenic (As) transformation and accumulation in a traditional Chinese medical plant - Jiao-Jiao Li; Long Yang; Cui-Ping Miao; Ya-Jun Teng; Zi-Hao Fu; Chang-Lei Cheng; Xue-Xiu Chang; Yu Qian; Li-Xing Zhao (Environmental Science and Pollution Research, 2021)

Co-editing PINK1 and DJ-1 Genes Via Adeno-Associated Virus-Delivered CRISPR/Cas9 System in Adult Monkey Brain Elicits Classical Parkinsonian Phenotype - Hao Li; Shihao Wu; Xia Ma; Xiao Li; Tianlin Cheng; Zhifang Chen; Jing Wu; Longbao Lv; Ling Li; Liqi Xu; Wenchao Wang; Yingzhou Hu; et al. (Neuroscience Bulletin, 2021)
Whether direct manipulation of Parkinson’s disease (PD) risk genes in the adult monkey brain can elicit a Parkinsonian phenotype remains an unsolved issue. Here, we used an adeno-associated virus serotype 9 (AAV9)-delivered CRISPR/Cas9 system to directly co-edit PINK1 and DJ-1 genes in the substantia nigras (SNs) of two monkey groups: an old group and a middle-aged group. After the operation, the old group exhibited all the classic PD symptoms, including bradykinesia, tremor, and postural instability, accompanied by key pathological hallmarks of PD, such as severe nigral dopaminergic neuron loss (>64%) and evident α-synuclein pathology in the gene-edited SN. In contrast, the phenotype of their middle-aged counterparts, which also showed clear PD symptoms and pathological hallmarks, were less severe. In addition to the higher final total PD scores and more severe pathological changes, the old group were also more susceptible to gene editing by showing a faster process of PD progression. These results suggested that both genetic and aging factors played important roles in the development of PD in the monkeys. Taken together, this system can effectively develop a large number of genetically-edited PD monkeys in a short time (6–10 months), and thus provides a practical transgenic monkey model for future PD studies.

Acute associations between air pollution on premature rupture of membranes in Hefei, China - Chao Zhang; Sha Li; Gan-lan Guo; Jing-wen Hao; Peng Cheng; Li-lin Xiong; Shu-ting Chen; Ji-yu Cao; Yu-wen Guo; Jia-hu Hao (Environmental Geochemistry and Health, 2021)

Characterization of AV422 from Haemaphysalis flava ticks in vitro - Lei Liu; Hao Tang; De-yong Duan; Jin-bao Liu; Jie Wang; Li-li Feng; Tian-yin Cheng (Experimental and Applied Acarology, 2021)

Long-term impact of ambient air pollution on preterm birth in Xuzhou, China: a time series study - Sha Li; Lei Peng; Xiaochang Wu; Geng Xu; Peng Cheng; Jingwen Hao; Zhaohui Huang; Meng Xu; Shuting Chen; Chao Zhang; Jiahu Hao (Environmental Science and Pollution Research, 2021)

Noise reduction method of microseismic signal of water inrush in tunnel based on variational mode method - Liping Li; Hao Jin; Yanhao Chen; Shuai Cheng; Huijiang Hu; Sheng Wang (Bulletin of Engineering Geology and the Environment, 2021)

Sorghum breeding in the genomic era: opportunities and challenges - Huaiqing Hao; Zhigang Li; Chuanyuan Leng; Cheng Lu; Hong Luo; Yuanming Liu; Xiaoyuan Wu; Zhiquan Liu; Li Shang; Hai-Chun Jing (Theoretical and Applied Genetics, 2021)

In-Situ Seawater Gamma Spectrometry with LaBr3 Detector at a Nuclear Power Plant Outlet - Daowei Dou; Zhi Zeng; Wen Yu; Ming Zeng; Wu Men; Feng Lin; Hao Ma; Jianping Cheng; Junli Li (Journal of Marine Science and Engineering, 2021)
In a nuclear emergency, the application of in situ spectrometers for monitoring environmental radioactivity is significantly important, as information on the type and activity of radionuclides released from the accident can be obtained quickly. However, in emergency environmental radiological monitoring, a balance between energy resolution and detecting efficiency must be considered in selecting an appropriate detector. In this study, in situ gamma spectrometry was conducted with the LaBr3 detector to determine the radioactivity of seawater at the discharging outlet of a coastal nuclear power plant in southeast China. The results show that the LaBr3 scintillator has excellent energy resolution and detection efficiency, making it a promising detector for emergency monitoring.

Assessment of GCMs simulation performance for precipitation and temperature from CMIP5 to CMIP6 over the Tibetan Plateau - Yurui Lun; Liu Liu; Lei Cheng; Xiuping Li; Hao Li; Zongxue Xu (International Journal of Climatology, 2021)
General circulation models (GCMs) are indispensable for climate change adaptive study over the Tibetan Plateau (TP), which is the potential trigger and amplifier in global climate fluctuations. With the release of Coupled Model Intercomparison Project Phase 6 (CMIP6), 24 GCMs from CMIP5 and CMIP6 were comparatively evaluated for precipitation and air temperature simulations based on the China Meteorological Forcing Dataset (CMFD). Rank score results showed that CMIP6 models generally performed better than CMIP5 for precipitation and surface air temperature over the TP. According to multimodel ensembles (MMEs) of the optimal GCMs for each climate variable, the overestimation of precipitation was both present in CMIP5 and CMIP6, but the results of CMIP6 MMEs were relatively lower in the mid‐west and northern edge of the TP. Furthermore, CMIP6 offered a better performance of precipitation in summer and autumn. For temperature, CMIP6 MMEs were able to reduce the relatively large cold bias that appeared in CMIP5 MMEs in northwest areas to about 1°C and had a smaller bias in spring and winter. Moreover, the investigation into the simulation effects of precipitation at different elevation zones demonstrated that the improved ability of CMIP6 MMEs to reduce bias was mainly concentrated in the elevation zones of 2,000–3,000 m and over 5,000 m, where the precipitation bias was more than 200%. Additionally, CMIP6 MMEs of temperature were able to reduce the bias to less than 2°C in each elevation zone, with the minimum bias of −0.22°C distributed in the region with altitudes from 3,000 to 4,000 m, while the biases of CMIP5 MMEs in the region of 4,000–5,000 m and over 5,000 m were smaller than those of CMIP6 MMEs. Findings obtained in this study could provide a scientific reference for related climate change research over the TP. GCMs of CMIP6 perform better than those of CMIP5 for precipitation and temperature over the TP. Multimodel ensembles (MMEs) of CMIP6 effectively reduce the overestimation of precipitation from CMIP5 MMEs by 40 mm at the annual scale. Improved ability of CMIP6 MMEs shows a significant elevation dependency, especially in elevation zones of 2,000–3,000 m and over 5,000 m for precipitation.

Identification of differentially expressed genes associated with aluminum resistance in the soybean plant - Jing-xuan Wang; Bo Wang; Lu-bin Cui; Hao Xie; Run-zhi Li; Cheng Wang; Zhang-jie Nan; Yu-shu Liu; Jing-yu Ma; Yun-jin Sun; Wei-yu Li (Physiology and Molecular Biology of Plants, 2021)

Syntheses and anticancer activities of novel glucosylated (−)-epigallocatechin-3-gallate derivatives linked via triazole rings - Bo-Ya Shi; Ze-Hao Wang; Ning Zhang; Yin-Rong Xie; Xiu-Li Sun; Hao-Nan Yang; Yi-Long Wu; Cheng-Ting Zi; Xuan-Jun Wang; Jun Sheng (Medicinal Chemistry Research, 2021)

Design of supercontinuum laser hyperspectral light detection and ranging (LiDAR) (SCLaHS LiDAR) - Guoqing Zhou; Xiang Zhou; Youjian Song; Donghui Xie; Long Wang; Guangjian Yan; Minglie Hu; Bowen Liu; Weidong Shang; Chenghu Gong; Cheng Wang; Huaguo Huang; et al. (International Journal of Remote Sensing, 2021)

Orbital-scale Asian summer monsoon variations: Paradox and exploration - Hai Cheng; Haiwei Zhang; Yanjun Cai; Zhengguo Shi; Liang Yi; Chenglong Deng; Qingzhen Hao; Youbing Peng; Ashish Sinha; Hanying Li; Jingyao Zhao; Ye Tian; et al. (Science China Earth Sciences, 2021)

Cyclic Direct Shear Test on Rock Sample with Stepped Structural Plane - Binyao Hao; Liangxiao Xiong; Yunlin Li; Yuanpeng Liu; Zhuoer Cheng; Yinke Li (Geotechnical and Geological Engineering, 2021)

Short-term effects of ambient temperature on preterm birth: a time-series analysis in Xuzhou, China - Peng Cheng; Lei Peng; Jingwen Hao; Sha Li; Chao Zhang; Lianjie Dou; Weinan Fu; Fan Yang; Jiahu Hao (Environmental Science and Pollution Research, 2021)

An analysis on the adoption of an interregional carbon emission reduction allocation approach in the context of China’s interprovincial carbon emission transfer - Yang Yang; Suocheng Dong; Fujia Li; Hao Cheng; Zehong Li; Yu Li; Shantong Li (Environment, Development and Sustainability, 2021)

Effects of straw returning levels on carbon footprint and net ecosystem economic benefits from rice-wheat rotation in central China - Shi-hao Li; Li-jin Guo; Cou-gui Cao; Cheng-fang Li (Environmental Science and Pollution Research, 2021)

PapA , a peptidoglycan‐associated protein, interacts with OmpC and maintains cell envelope integrity - Yun‐Hao Wang; Hong‐He Chen; Zhou Huang; Xiao‐Jing Li; Nan Zhou; Chang Liu; Cheng‐Ying Jiang; De‐Feng Li; Shuang‐Jiang Liu (Environmental Microbiology, 2021)
Summary The bacterial cell envelope is critical to support and maintain cellular life. In Gram‐negative bacterial cells, the outer membrane and the peptidoglycan layer are two important parts of the cell envelope and they harbour abundant proteins. Here, we report the identification and characterization of a previously unknown p eptidoglycan‐ a ssociated p rotein, PapA, from the Gram‐negative Comamonas testosteroni . PapA bound peptidoglycan with its C‐terminal domain and interacted with the outer‐membrane porin OmpC. The PapA‐OmpC complex riveted the outer membrane and the peptidoglycan layer, and played a role in maintaining cell envelope integrity. When papA was disrupted, the mutant CNB‐1Δ papA apparently had an outer membrane partly separated from the peptidoglycan layer. Phenotypically, the mutant CNB‐1Δ papA lost chemotactic responses and had longer lag‐phase of growth, less flagellation and higher sensitivity to harsh environments. Totally, 1093 functionally unknown PapA homologues were identified from the public NR protein database and they were mainly distributed in Burkholderiales of Betaproteobacteria. Our finding provides a clue that the PapA homologous proteins might function as a rivet to maintain cell envelope integrity in those Gram‐negative bacteria.

Design of the Blade under Low Flow Velocity for Horizontal Axis Tidal Current Turbine - Jun-Hua Chen; Xian-Cheng Wang; Hao Li; Chu-Hua Jiang; Ling-Jie Bao (Journal of Marine Science and Engineering, 2020)
The blade is the key component for energy capture in horizontal axis tidal current turbine, and the blade’s design is directly related to the efficiency of the power generation device. The seawater flow velocity is a crucial parameter for blade design. Since the seawater velocity changes constantly, it is extremely important to determine the design velocity of the blade. This article proposes a calculation method for the design velocity of the blade so that the designed blade can achieve better energy collection efficiency under a variable flow velocity. This study performed the following investigations: (1) The author tested and analyzed the seawater velocity variation at the experimental site, determining the designed flow velocity via calculations; (2) The author combined the blade element momentum and Wilson’s optimization design method using the MATLAB software to calculate the blade shape parameters and predict the performance under a number of different flow velocity forecasts; (3) When testing the device under sea conditions, the experimental results showed that the performance capture devices and digital projections are basically the same, which verifies the validity and effectiveness of the design method.

Mapping quantitative trait loci associated with stem-related traits in maize (Zea mays L.) - Qiqi Shang; Degui Zhang; Rong Li; Kaixin Wang; Zimeng Cheng; Zhiqiang Zhou; Zhuanfang Hao; Jinbao Pan; Xinhai Li; Liyu Shi (Plant Molecular Biology, 2020)

High-throughput sequencing reveals the molecular mechanisms determining the stay-green characteristic in soybeans - Cheng Wang; Le Gao; Run Zhi Li; Ye Wang; Yang Ying Liu; Xin Zhang; Hao Xie (Journal of Biosciences, 2020)

Estimation of surface energy fluxes in the permafrost region of the Tibetan Plateau based on in situ measurements and the surface energy balance system model - Jimin Yao; Lianglei Gu; Cheng Yang; Hao Chen; Jiemin Wang; Yongjian Ding; Ren Li; Lin Zhao; Yao Xiao; Yongping Qiao; Jianzong Shi; Caiping Chen (International Journal of Climatology, 2020)
The surface energy balance is a key issue in land surface process research and important for studies of climate and hydrology. In this paper, the surface energy fluxes (net radiation, ground heat flux, sensible heat flux and latent heat flux) at the Tanggula (TGL) and Xidatan (XDT) sites were measured and the distributions of the regional surface energy fluxes on the Tibetan Plateau were obtained using a revised surface energy balance system (SEBS) model. The results show that the surface energy fluxes have obvious seasonal variations. At both sites, the sensible heat flux is highest in spring and lowest in summer, and the latent heat flux is highest in summer and lowest in winter. The high elevation, snow cover, freeze–thaw process, precipitation, vegetation and soil texture are important influencing factors for land surface energy fluxes. The time‐phase difference between the net radiation and ground heat flux for bare soils is estimated to be 2–3 hr. The ratio of ground heat flux and net radiation ranged from approximately 0.18 to 0.33, and a parameterization scheme for the remote sensing of ground heat flux over the Tibetan Plateau bare soil in summer is developed. The simulation results of the regional surface energy fluxes show that the distributions of surface parameters, such as vegetation, soil texture and soil moisture content, are important for understanding regional changes in the surface energy fluxes.

Analysis of genetic architecture and favorable allele usage of agronomic traits in a large collection of Chinese rice accessions - Xiuxiu Li; Zhuo Chen; Guomin Zhang; Hongwei Lu; Peng Qin; Ming Qi; Ying Yu; Bingke Jiao; Xianfeng Zhao; Qiang Gao; Hao Wang; Yunyu Wu; et al. (Science China Life Sciences, 2020)

Lagged response of Adélie penguin (Pygoscelis adeliae) abundance to environmental variability in the Ross Sea, Antarctica - Xintong Chen; Xiao Cheng; Baogang Zhang; Hao Meng; Di Wu; Miao Zhang; Ming Ji; Xianglan Li (Polar Biology, 2020)

Liquiritin inhibits proliferation and induces apoptosis in HepG2 hepatocellular carcinoma cells via the ROS-mediated MAPK/AKT/NF-κB signaling pathway - Jia-Ru Wang; Tian-Zhu Li; Cheng Wang; Shu-Mei Li; Ying-Hua Luo; Xian-Ji Piao; Yu-Chao Feng; Yi Zhang; Wan-Ting Xu; Yu Zhang; Tong Zhang; Shi-Nong Wang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Overexpression of PREX1 in oral squamous cell carcinoma indicates poor prognosis - Shu-Cheng Wan; Hao Wu; Hao Li; Wei-Wei Deng; Yao Xiao; Cong-Cong Wu; Lei-Lei Yang; Wen-Feng Zhang; Zhi-Jun Sun (Journal of Molecular Histology, 2020)

Overexpression miR-486-3p Promoted by Allicin Enhances Temozolomide Sensitivity in Glioblastoma Via Targeting MGMT - Henggang Wu; Xu Li; Tiehui Zhang; Guojun Zhang; Jingnan Chen; Li Chen; Min He; Bilie Hao; Cheng Wang (NeuroMolecular Medicine, 2020)
Glioblastoma is the most common primary tumor of the central nervous system that develops chemotherapy resistance. Previous studies showed that Allicin could inhibit multiple cancer cells including glioblastoma, but the function of Allicin in glioblastoma is still unclear. Our work aimed to investigate the underlying molecular mechanism. The results showed that miR-486-3p levels were greatly increased in glioblastoma during Allicin treatment. Overexpression of miR-486-3p increased chemosensitivity to temozolomide (TMZ) in vitro and in vivo. O6-methylguanine-DNA methyltransferase (MGMT) was identified as a direct target of miR-486-3p, and miR-486-3p overexpression prevented the protein translation of MGMT. Moreover, overexpression of MGMT restored miR-486-3p-induced chemosensitivity to TMZ. Taken together, our studies revealed that Allicin could upregulate miR-486-3p and enhance TMZ sensitivity in glioblastoma. The results suggested that in the future, Allicin can be used as an adjuvant therapy with TMZ to improve the prognosis of patients, and miR-486-3p may be a potential target for glioblastoma treatment to improve the curative effects.

Mixture of Pb, Zn and Cu on root permeability and radial oxygen loss in the mangrove Bruguiera gymnorrhiza - Hao Cheng; You-Shao Wang; Chang-Da Li; Zhi-Hong Ye; Shafi Muhammad; Mei-Lin Wu; Fun-Lin Sun (Ecotoxicology, 2020)

Dynamics of radial oxygen loss in mangroves subjected to waterlogging - Hao Cheng; Mei-Lin Wu; Chang-Da Li; Fu-Lin Sun; Cui-Ci Sun; You-Shao Wang (Ecotoxicology, 2020)

Salt tolerance and exclusion in the mangrove plant Avicennia marina in relation to root apoplastic barriers - Hao Cheng; Anifiok Inyang; Chang-Da Li; Jiao Fei; Yan-Wu Zhou; You-Shao Wang (Ecotoxicology, 2020)

First detection and genomic characteristics of bovine torovirus in dairy calves in China - Hao Li; Bin Zhang; Hua Yue; Cheng Tang (Archives of Virology, 2020)

Enhanced Oral Delivery of Curcumin via Vitamin E TPGS Modified Nanodiamonds: a Comparative Study on the Efficacy of Non-covalent and Covalent Conjugated Strategies - Dandan Liu; Sen Qiao; Bingchao Cheng; Dongyang Li; Jisuan Chen; Qingyin Wu; Hao Pan; Weisan Pan (AAPS PharmSciTech, 2020)

Mapping and characterization of major QTL for spike traits in common wheat - Cheng-Hao Kuang; Xiao-Fang Zhao; Ke Yang; Zhi-Peng Zhang; Li Ding; Zhi-En Pu; Jian Ma; Qian-Tao Jiang; Guo-Yue Chen; Ji-Rui Wang; Yu-Ming Wei; You-Liang Zheng; et al. (Physiology and Molecular Biology of Plants, 2020)

Inhibition of glycolysis ameliorate arthritis in adjuvant arthritis rats by inhibiting synoviocyte activation through AMPK/NF-кB pathway - Ying Wang; Hao Xian; Jiajia Qi; Fang Wei; Xiu Cheng; Sha Li; Qing Wang; Zhaoyang Liu; Yun Yu; Jing Zhou; Xiaojin Sun; Hao Liu; et al. (Inflammation Research, 2020)

Antiviral activity of Illicium verum Hook. f. extracts against grouper iridovirus infection - Mingzhu Liu; Qing Yu; Hehe Xiao; Yi Yi; Hao Cheng; Dedi Fazriansyah Putra; Yaming Huang; Qin Zhang; Pengfei Li (Journal of Fish Diseases, 2020)
Grouper iridovirus causes high mortality rates in cultured groupers, and effective treatment for grouper iridovirus infection is urgently required. Illicium verum Hook. f. is a well‐known medicinal plant with a variety of biological activities. The aim of this study was to analyse the use of I. verum extracts to treat grouper iridovirus infection. The safe working concentration of each I. verum extract was identified both in vitro and in vivo as follows: I. verum aqueous extract (IVAE) ≤ 500 μg/ml; I. verum ethanol extract (IVEE) ≤ 250 μg/ml; shikimic acid (SKA) ≤ 250 μg/ml; trans‐anethole (TAT) ≤ 800 μg/ml; 3,4‐dihydroxybenzoic acid (DDBA) ≤ 400 μg/ml; and quercetin (QCE) ≤ 50 μg/ml. The inhibitory activity of each I. verum extract against grouper iridovirus infection was analysed using aptamer (Q2)‐based fluorescent molecular probe (Q2‐AFMP) and RT‐qPCR. All of the I. verum extracts displayed dose‐dependent antiviral activities against grouper iridovirus. Based on the achieved per cent inhibition, IVAE, IVEE, DDBA and QCE were associated with the greatest antiviral activity (all > 90%). Together, our results indicate that I. verum extracts have effective antiviral properties, making it an excellent potential source material for the development of effective treatment for grouper iridovirus infection.

Research on Gas Outburst Coal Seam Mining Technology Based on the Theory of Gob-Side Entry Retaining - Yongkui Shi; Xin Wang; Jian Hao; Jiahui Lin; Weijia Cheng; Jun Chen; Xiao Li (Geotechnical and Geological Engineering, 2020)

Alternation of back-arc extension and compression in an overriding plate: evidence from Cretaceous structures in the western Liaoning region, eastern China - Nan Su; Guang Zhu; Cheng Liu; Shuai Zhang; Yunjian Li; Hao Yin; Xiaodong Wu (International Journal of Earth Sciences, 2020)

The enhanced SO3 formation by alkali-metal sulfates from ash in the post-flame region during the combustion of high-alkali coal - Haiping Xiao; Qiyong Cheng; Hao Shi; Jian Li; Yu Ru (Environmental Science and Pollution Research, 2020)

Two new species of Encyrtidae (Hymenoptera: Chalcidoidea) from China, parasitoid of Antecerococcus roseus (Green) (Hemiptera: Cerococcidae) on Boehmeria nivea (L.) Gaud - Guo-Hao Zu; Ze-Ning Yang; Xin-Sheng Cao; Yuan-Hong Wang; Cheng-De Li (Phytoparasitica, 2020)

The giant Zaozigou Au-Sb deposit in West Qinling, China: magmatic- or metamorphic-hydrothermal origin? - Kun-Feng Qiu; Hao-Cheng Yu; Jun Deng; Duncan McIntire; Zong-Yang Gou; Jian-Zhen Geng; Zhao-Shan Chang; Rui Zhu; Kang-Ning Li; Richard Goldfarb (Mineralium Deposita, 2020)

Interaction between CA repeat microsatellites and HIF1α regulated the transcriptional activity of porcine IGF1 promoter - Hongwei Geng; Linlin Hao; Yunyun Cheng; Chunli Wang; Shan Huang; Wenzhen Wei; Rui Yang; Haoyang Li; Songcai Liu; Hao Yu; Huayi Lu (Journal of Applied Genetics, 2020)

PDGFRβ-targeted TRAIL specifically induces apoptosis of activated hepatic stellate cells and ameliorates liver fibrosis - Rui Li; Zhao Li; Yanru Feng; Hao Yang; Qiuxiao Shi; Ze Tao; Jingqiu Cheng; Xiaofeng Lu (Apoptosis, 2020)

The root endophytic fungus Serendipita indica improves resistance of Banana to Fusarium oxysporum f. sp. cubense tropical race 4 - Chunzhen Cheng; Dan Li; Quan Qi; Xueli Sun; Mensah Raphael Anue; Bodjrenou Mahoudjro David; Yongyan Zhang; Xiangyang Hao; Zihao Zhang; Zhongxiong Lai (European Journal of Plant Pathology, 2020)

Evolution and Current Applications of Robot-Assisted Fracture Reduction: A Comprehensive Review - Jing-Xin Zhao; Changsheng Li; Hongliang Ren; Ming Hao; Li-Cheng Zhang; Pei-Fu Tang (Annals of Biomedical Engineering, 2020)

Correction to: Recombination between homoeologous chromosomes induced in durum wheat by the Aegilops speltoides Su1-Ph1 suppressor - Hao Li; Le Wang; Ming-Cheng Luo; Fang Nie; Yun Zhou; Patrick E. McGuire; Assaf Distelfeld; Xiongtao Dai; Chun-Peng Song; Jan Dvorak (Theoretical and Applied Genetics, 2019)

Recombination between homoeologous chromosomes induced in durum wheat by the Aegilops speltoides Su1-Ph1 suppressor - Hao Li; Le Wang; Ming-Cheng Luo; Fang Nie; Yun Zhou; Patrick E. McGuire; Assaf Distelfeld; Xiongtao Dai; Chun-Peng Song; Jan Dvorak (Theoretical and Applied Genetics, 2019)

Trends in particulate matter and its chemical compositions in China from 2013–2017 - Yuesi Wang; Wenjie Li; Wenkang Gao; Zirui Liu; Shili Tian; Rongrong Shen; Dongsheng Ji; Shuai Wang; Lili Wang; Guiqian Tang; Tao Song; Mengtian Cheng; et al. (Science China Earth Sciences, 2019)

Intensive Potato Production by Farmers in DeHong, China - Canhui Li; Chaoxu Guan; Jicai Cheng; Youwei Luo; Dahai Hao; Peter VanderZaag (American Journal of Potato Research, 2019)

Multi‐model analysis of climate impacts on plant photosynthesis in China during 2000–2015 - Hao Yan; Shao‐Qiang Wang; Jun‐Bang Wang; Yun Cao; Ling‐Ling Xu; Men‐Xin Wu; Lu Cheng; Liu‐Xi Mao; Feng‐Hua Zhao; Xian‐Zhou Zhang; Yun‐Fen Liu; Yan‐Fen Wang; et al. (International Journal of Climatology, 2019)
Differences, arising from differences in gross primary production (GPP) model structures and driving forces, have fuelled arguments concerning interannual changes of GPP in China since 2000. To better investigate the interannual variability of GPP and its covariance with climate factors in China, this study adopted a multi‐model analysis based on three GPP models (i.e., Terrestrial Ecosystem Carbon flux model [TEC], Breathing Earth System Simulator model [BESS], and MOD17 GPP model). The results show that annual GPP in China increased by 0.021–0.057 Pg C year −1 from 2000 to 2015 attributable to atmospheric‐CO 2 fertilization effects and favourable climate change, that is, increasing precipitation ( P r ) and temperature ( T a ). However, northern China and southern China had a large difference in the amplitude of these GPP changes; annual GPP increased by 0.017–0.039 Pg C year −1 in northern China but only 0.001–0.018 Pg C year −1 in southern China. Northern China and southern China occupy contrasting climate zones and this contrast produced different interannual variability of GPP through different mechanisms. Northern China has a dry climate with GPP changes sensitive to P r . As a result, more P r along with higher T a in northern China produced the strong uptrend of GPP from 2000 to 2015. In contrast, southern China has a wet climate with its GPP sensitive to solar radiation and T a . For the interval of 2000–2015, decreasing radiation plus drought exerted a negative influence on GPP in southern China. This study highlights the diverse mechanisms in which climate change affects GPP in dry and wet climate zones. A robust multi‐model analysis is preferred to reduce uncertainties arising from a single GPP model and its driving data.

Two typical merging events of oceanic mesoscale anticyclonic eddies - Zi-Fei Wang; Liang Sun; Qiu-Yang Li; Hao Cheng (Ocean Science, 2019)
The long-term theoretical “energy paradox” of whether the final state of two merging anticyclones contains more energy than the initial state is studied by considering two typical merging events of ocean mesoscale eddies. The results demonstrate that the total mass (volume), total circulation (area integration of vorticity), and total angular momentum (AM) are conserved if the orbital AM relative to the center of mass is taken into account as the eddies rotate around the center of mass before merging. For subsurface merging, the mass trapped by the Taylor–Proudman effect above the subsurface eddies should also be included. Both conservation laws of circulation and orbital AM have been overlooked in previous theoretical studies. As a result of fusion during merging, the total eddy kinetic energy decreases slightly. In contrast, the total eddy potential energy (EPE) increases after merging. The increase in EPE is mostly supported by the loss of gravitational potential energy (PE) via eddy sinking below the original level prior to merging. This implies that the merging of eddies requires background gravitational PE to be converted to EPE. In contrast, the vorticity and enstrophy consequently decrease after merging. Thus, the eddy merging effect behaves as a “large-scale energy pump” in an inverse energy cascade. It is noted that eddy conservation and conversion laws depend on the laws of physical dynamics, even if additional degrees of freedom can be provided in a mathematical model.

Purification and characterization of an endo-xylanase from Trichoderma sp., with xylobiose as the main product from xylan hydrolysis - Li-Hao Fu; Nan Jiang; Cheng-Xi Li; Xue-Mei Luo; Shuai Zhao; Jia-Xun Feng (World Journal of Microbiology and Biotechnology, 2019)

Correction to: SPECT/CT imaging of apoptosis in aortic aneurysm with radiolabeled duramycin - Chengkai Hu; Hui Tan; Qingyu Lin; Mieradilijiang Abudupataer; Yun Zhao; Jun Li; Jiawei Gu; Dengfeng Cheng; Chunsheng Wang; Kai Zhu; Hao Lai (Apoptosis, 2019)

Adventitious root cultures of Oplopanax elatus inhibit LPS-induced inflammation via suppressing MAPK and NF-κB signaling pathways - Wen Tian; Xuan-Mei Piao; Cheng-Ri Yin; Xiao-Long Jiang; Hao-Ding Sun; Xiao-Li An; Jun Jiang; Mei-Lan Lian (In Vitro Cellular & Developmental Biology - Animal, 2019)

Investment Environment Assessment and Strategic Policy for Subjects of Federation in Russia - Fujia Li; Qian Liu; Suocheng Dong; Hao Cheng; Yu Li; Yang Yang; Bair Tsydypov; Alexey Bilgaev; Alexander Ayurzhanaev; Xiaoyan Bu; Bing Xia (Chinese Geographical Science, 2019)

SPECT/CT imaging of apoptosis in aortic aneurysm with radiolabeled duramycin - Chengkai Hu; Hui Tan; Qingyu Lin; Mieradilijiang Abudupataer; Yun Zhao; Jun Li; Jiawei Gu; Dengfeng Cheng; Chunsheng Wang; Kai Zhu; Hao Lai (Apoptosis, 2019)

Alterations in intestinal microbiota of colorectal cancer patients receiving radical surgery combined with adjuvant CapeOx therapy - Cheng Kong; Renyuan Gao; Xuebing Yan; Linsheng Huang; Jide He; Hao Li; Jie You; Huanlong Qin (Science China Life Sciences, 2019)

Experimental investigation on the mechanical characteristics of gas-bearing coal considering the impact of moisture - Ming-yi Chen; Yuan-ping Cheng; Jing-chun Wang; Hao-ran Li; Ning Wang (Arabian Journal of Geosciences, 2019)

Tamarixetin protects against cardiac hypertrophy via inhibiting NFAT and AKT pathway - Cheng Fan; Yuan Li; Hui Yang; Yuqian Cui; Hao Wang; Heng Zhou; Jianning Zhang; Binfeng Du; Qian Zhai; Dawei Wu; Xiaomei Chen; Haipeng Guo (Journal of Molecular Histology, 2019)

Assessment of 12 Metals and Metalloids in Blood of General Populations Living in Wuhan of China by ICP-MS - Hao-Long Zeng; Huijun Li; Jie Lu; Qing Guan; Liming Cheng (Biological Trace Element Research, 2019)

A miR-511-binding site SNP in the 3′UTR of IGF-1 gene is associated with proliferation and apoptosis of PK-15 cells - Wenzhen Wei; Gang Wang; Yunyun Cheng; Rui Yang; Jie Song; Shan Huang; Haoyang Li; Hongwei Geng; Hao Yu; Songcai Liu; Linlin Hao (In Vitro Cellular & Developmental Biology - Animal, 2019)

Elaboration in type, primary structure, and bioactivity of polysaccharides derived from mollusks - Ling Chong Wang; Liu Qing Di; Jun Song Li; Li Hong Hu; Jian Ming Cheng; Hao Wu (Critical Reviews in Food Science and Nutrition, 2019)

Waterlogging tolerance of Bidens pilosa translates to increased competitiveness compared to native Bidens biternata - Maofeng Yue; Hao Shen; Weihua Li; Jinfeng Chen; Wanhui Ye; Xingshan Tian; Aiguo Yin; Shuiming Cheng (Plant and Soil, 2019)

Correction to: A new species of Microterys (Hymenoptera: Encyrtidae) from Northeast China, parasitoid of Parthenolecanium corni (Bouché) (Hemiptera: Coccidae) - Guo-Hao Zu; Cheng-De Li; Yuan-Hong Wang (Phytoparasitica, 2019)

Successful Treatment of Eczema-Like Mucormycosis in a Child by Combination of Intravenous Drip and Percutaneous Injection Amphotericin B - Mei-hua Fu; Jia Liu; Guan-zhao Liang; Cheng-rang Li; Xiao-mei Zhu; Le Wang; Hao Chen; Wen-long Hu; Gui-xia Lv; Wei-da Liu (Mycopathologia, 2019)

A bioactive new protostane-type triterpenoid from Alisma plantago - aquatica subsp. orientale (Sam.) Sam. - Ya-Li Wang; Jian-Chao Zhao; Jia-Hao Liang; Xiang-Ge Tian; Xiao-Kui Huo; Lei Feng; Jing Ning; Chao Wang; Bao-Jing Zhang; Gang Chen; Ning Li; Cheng-Peng Sun (Natural Product Research, 2019)

Attribute recognition model for risk assessment of water inrush - Jing Wang; Shu-cai Li; Li-ping Li; Peng Lin; Zhen-hao Xu; Cheng-lu Gao (Bulletin of Engineering Geology and the Environment, 2019)

An amino acid duplication/insertion in the Bm126 gene of Bombyx mori nucleopolyhedrovirus alters viral gene expression as shown by differential gene expression analysis - Jinshan Huang; Jingfeng Li; Chen Cheng; Xudong Tang; Xingjia Shen; Bifang Hao (Archives of Virology, 2019)

Correction to: Magnesium deficiency affects secondary lignification of the vascular system in Citrus sinensis seedlings - Jing-Hao Huang; Jing Xu; Xin Ye; Tu-Yan Luo; Li-Hua Ren; Guo-Cheng Fan; Yi-Ping Qi; Qiang Li; Rhuanito S. Ferrarezi; Li-Song Chen (Trees, 2019)

Magnesium deficiency affects secondary lignification of the vascular system in Citrus sinensis seedlings - Jing-Hao Huang; Jing Xu; Xin Ye; Tu-Yan Luo; Li-Hua Ren; Guo-Cheng Fan; Yi-Ping Qi; Qiang Li; Rhuanito S. Ferrarezi; Li-Song Chen (Trees, 2019)

Correction to: A new species of Anagyrus (Hymenoptera: Encyrtidae) from China, parasitoid of Phenacoccus solani Ferris (Hemiptera: Pseudococcidae) on Lycoris radiata (L’Her.) Herb. - Guo-Hao Zu; Yuan-hong Wang; Yan-Zhou Zhang; Cheng-De Li; Xu Zhang (Phytoparasitica, 2019)

Functional analysis of the UL24 protein of suid herpesvirus 1 - Chao Ye; Jing Chen; Xuefei Cheng; Shasha Zhou; Shan Jiang; Jingjing Xu; Hao Zheng; Wu Tong; Guoxin Li; Guangzhi Tong (Virus Genes, 2019)

Anti-senescence effect and molecular mechanism of the major royal jelly proteins on human embryonic lung fibroblast (HFL-I) cell line - Chen-min Jiang; Xin Liu; Chun-xue Li; Hao-cheng Qian; Di Chen; Chao-qiang Lai; Li-rong Shen (Journal of Zhejiang University-SCIENCE B, 2018)

Optimization of Hydrolysis Conditions for the Isolation of Angiotensin-I Converting Enzyme (ACE) Inhibitory Peptides from Rhopilema hispidum - Zhenliang Sun; Huanlong Qin; Duo Cao; Xuebing Yan; Hao Li; Linsheng Huang; Xiao Qu; Cheng Kong; Man Wang (Journal of Ocean University of China, 2018)

A new species of Microterys (Hymenoptera: Encyrtidae) from Northeast China, parasitoid of Parthenolecanium corni (Bouché) (Hemiptera: Coccidae) - Guo-Hao Zu; Cheng-De Li; Yuan-Hong Wang (Phytoparasitica, 2018)

Complete Genome Sequence of Clostridium kluyveri JZZ Applied in Chinese Strong-Flavor Liquor Production - Yansheng Wang; Bin Li; Hong Dong; Xunduan Huang; Ruiyu Chen; Xingjie Chen; Laoji Yang; Bing Peng; Guopai Xie; Wei Cheng; Biao Hao; Changrun Li; et al. (Current Microbiology, 2018)

Repaglinide-irbesartan drug interaction: effects of SLCO1B1 polymorphism on repaglinide pharmacokinetics and pharmacodynamics in Chinese population - Qi Pei; Jun-Yan Liu; Ji-Ye Yin; Guo-Ping Yang; Shi-Kun Liu; Yi Zheng; Pan Xie; Cheng-Xian Guo; Mi Luo; Hong-Hao Zhou; Xi Li; Zhao-Qian Liu (European Journal of Clinical Pharmacology, 2018)

The regulation of skeletal muscle fiber-type composition by betaine is associated with NFATc1/MyoD - Jingjing Du; Linyuan Shen; Peiwen Zhang; Zhendong Tan; Xiao Cheng; Jia Luo; Xue Zhao; Qiong Yang; Hao Gu; An’an Jiang; Jideng Ma; Qianzi Tang; et al. (Journal of Molecular Medicine, 2018)

An evaluation of the economic, social, and ecological risks of China-Mongolia-Russia high-speed railway construction and policy suggestions - Suocheng Dong; Yang Yang; Fujia Li; Hao Cheng; Jingnan Li; Alexey Bilgaev; Zehong Li; Yu Li (Journal of Geographical Sciences, 2018)

Joint structural and physiological control on the interannual variation in productivity in a temperate grassland: A data‐model comparison - Zhongmin Hu; Hao Shi; Kaili Cheng; Ying‐Ping Wang; Shilong Piao; Yue Li; Li Zhang; Jianyang Xia; Lei Zhou; Wenping Yuan; Steve Running; Longhui Li; et al. (Global Change Biology, 2018)
Given the important contributions of semiarid region to global land carbon cycle, accurate modeling of the interannual variability (IAV) of terrestrial gross primary productivity (GPP) is important but remains challenging. By decomposing GPP into leaf area index (LAI) and photosynthesis per leaf area (i.e., GPP_leaf), we investigated the IAV of GPP and the mechanisms responsible in a temperate grassland of northwestern China. We further assessed six ecosystem models for their capabilities in reproducing the observed IAV of GPP in a temperate grassland from 2004 to 2011 in China. We observed that the responses to LAI and GPP_leaf to soil water significantly contributed to IAV of GPP at the grassland ecosystem. Two of six models with prescribed LAI simulated of the observed IAV of GPP quite well, but still underestimated the variance of GPP_leaf, therefore the variance of GPP. In comparison, simulated pattern by the other four models with prognostic LAI differed significantly from the observed IAV of GPP. Only some models with prognostic LAI can capture the observed sharp decline of GPP in drought years. Further analysis indicated that accurately representing the responses of GPP_leaf and leaf stomatal conductance to soil moisture are critical for the models to reproduce the observed IAV of GPP_leaf. Our framework also identified that the contributions of LAI and GPP_leaf to the observed IAV of GPP were relatively independent. We conclude that our framework of decomposing GPP into LAI and GPP_leaf has a significant potential for facilitating future model intercomparison, benchmarking and optimization should be adopted for future data‐model comparisons.

Cystatin C Induces Insulin Resistance in Hippocampal Neurons and Promotes Cognitive Dysfunction in Rodents - Lan Luo; Jinyu Ma; Yue Li; Zongkang Hu; Chengfeng Jiang; Hao Cai; Cheng Sun (Neuroscience Bulletin, 2018)

A Neuron-Specific Gene Therapy Relieves Motor Deficits in Pompe Disease Mice - Ni-Chung Lee; Wuh-Liang Hwu; Shin-Ichi Muramatsu; Darin J. Falk; Barry J. Byrne; Chia-Hao Cheng; Nien-Chu Shih; Kai-Ling Chang; Li-Kai Tsai; Yin-Hsiu Chien (Molecular Neurobiology, 2018)

Identifying potentially common genes between dyslipidemia and osteoporosis using novel analytical approaches - Xu Lin; Cheng Peng; Jonathan Greenbaum; Zhang-Fang Li; Ke-Hao Wu; Zeng-Xin Ao; Tong Zhang; Jie Shen; Hong-Wen Deng (Molecular Genetics and Genomics, 2018)

In Situ Observation of Rock Spalling in the Deep Tunnels of the China Jinping Underground Laboratory (2400 m Depth) - Xia-Ting Feng; Hong Xu; Shi-Li Qiu; Shao-Jun Li; Cheng-Xiang Yang; Hao-Sen Guo; Yuan Cheng; Yao-Hui Gao (Rock Mechanics and Rock Engineering, 2018)

A new species of Anagyrus (Hymenoptera: Encyrtidae) from China, parasitoid of Phenacoccus solani Ferris (Hemiptera: Pseudococcidae) on Lycoris radiata (L’Her.) Herb. - Guo-Hao Zu; Yuan-hong Wang; Yan-Zhou Zhang; Cheng-De Li; Xu Zhang (Phytoparasitica, 2018)

An Optimized and Feasible Preparation Technique for the Industrial Production of Hydrogel Patches - Wei-Ze Li; Wen-Xia Han; Xu-Liang Hao; Ning Zhao; Xi-Feng Zhai; Li-Bin Yang; Shu-Miao He; Yu-Chuan Cheng; Han Zhang; Li-Na Fu; Yan Zhang; Ze Liang (AAPS PharmSciTech, 2018)

In Situ Observation of Hard Surrounding Rock Displacement at 2400-m-Deep Tunnels - Xia-Ting Feng; Zhi-Bin Yao; Shao-Jun Li; Shi-Yong Wu; Cheng-Xiang Yang; Hao-Sen Guo; Shan Zhong (Rock Mechanics and Rock Engineering, 2018)

Supplementation with turmeric residue increased survival of the Chinese soft-shelled turtle (Pelodiscus sinensis) under high ambient temperatures - Yong Chen; Yi-fan Zhang; Hao-cheng Qian; Jing-liang Wang; Zhe Chen; Jose M. Ordovas; Chao-qiang Lai; Li-rong Shen (Journal of Zhejiang University-SCIENCE B, 2018)

Exploring the potential relationship between indoor air quality and the concentration of airborne culturable fungi: a combined experimental and neural network modeling study - Zhijian Liu; Kewei Cheng; Hao Li; Guoqing Cao; Di Wu; Yunjie Shi (Environmental Science and Pollution Research, 2018)

iTRAQ-based comparative proteomic analysis provides insights into somatic embryogenesis in Gossypium hirsutum L. - Hua-Guo Zhu; Wen-Han Cheng; Wen-Gang Tian; Yang-Jun Li; Feng Liu; Fei Xue; Qian-Hao Zhu; Yu-Qiang Sun; Jie Sun (Plant Molecular Biology, 2018)

Epigenetic modification of TLE1 induce abnormal differentiation in diabetic mice intestinal epithelium - Ji-hao Xu; Guang-cheng Chen; Can-ze Huang; Di Cheng; Ting-feng Wu; Si-yi Wang; Jie-yao Li; Tao Yu; Qi-kui Chen (Molecular and Cellular Biochemistry, 2018)

Effect of corticosteroids on atrial fibrillation after catheter ablation: a meta-analysis - Sanjay Jaiswal; Xian-bao Liu; Qu-cheng Wei; Ying-hao Sun; Li-han Wang; Liu-guang Song; Dan-dan Yang; Jian-an Wang (Journal of Zhejiang University-SCIENCE B, 2018)

The validation of two major QTLs related to the timing of spring bud flush in Camellia sinensis - Li-Qiang Tan; Min Peng; Li-Yi Xu; Li-Yuan Wang; Kang Wei; Yao Zou; Sheng-Xiang Chen; Pin-Wu Li; Qian Tang; Hao Cheng (Euphytica, 2018)

Phytotoxic, antibacterial, and antioxidant activities of mycotoxins and other metabolites from Trichoderma sp. - Ju-cheng Zhang; Guang-Yi Chen; Xiao-Zhan Li; Ming Hu; Bang-Yan Wang; Bao-Hui Ruan; Hao Zhou; Li-Xing Zhao; Jun Zhou; Zhong-Tao Ding; Ya-Bin Yang (Natural Product Research, 2017)

Mangiferin Upregulates Glyoxalase 1 Through Activation of Nrf2/ARE Signaling in Central Neurons Cultured with High Glucose - Yao-Wu Liu; Ya-Qin Cheng; Xiao-Li Liu; Yun-Chao Hao; Yu Li; Xia Zhu; Fan Zhang; Xiao-Xing Yin (Molecular Neurobiology, 2017)

Evaluation of the Integrity of Deep Rock Masses Using Results of Digital Borehole Televiewers - Hao-Sen Guo; Xia-Ting Feng; Shao-Jun Li; Cheng-Xiang Yang; Zhi-Bin Yao (Rock Mechanics and Rock Engineering, 2017)

Influenza A virus upregulates PRPF8 gene expression to increase virus production - Chee-Hing Yang; Hui-Chun Li; Yu-Ling Shiu; Tzu-Shan Ku; Chia-Wen Wang; Yi-Shuan Tu; Hung-Ling Chen; Cheng-Hao Wu; Shih-Yen Lo (Archives of Virology, 2017)

Cytoplasmic aryl hydrocarbon receptor regulates glycogen synthase kinase 3 beta, accelerates vimentin degradation, and suppresses epithelial–mesenchymal transition in non-small cell lung cancer cells - Ching-Hao Li; Chen-Wei Liu; Chi-Hao Tsai; Yi-Jen Peng; Yu-Hsuan Yang; Po-Lin Liao; Chen-Chen Lee; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2017)

A Novel, Multi-Target Natural Drug Candidate, Matrine, Improves Cognitive Deficits in Alzheimer’s Disease Transgenic Mice by Inhibiting Aβ Aggregation and Blocking the RAGE/Aβ Axis - Lili Cui; Yujie Cai; Wanwen Cheng; Gen Liu; Jianghao Zhao; Hao Cao; Hua Tao; Yan Wang; Mingkang Yin; Tingting Liu; Yu Liu; Pengru Huang; et al. (Molecular Neurobiology, 2017)

Rural landscape types and recreational value spatial analysis of valley area of Loess Plateau: A case of Hulu Watershed, Gansu Province, China - Suocheng Dong; Hao Cheng; Yu Li; Fujia Li; Zhe Wang; Feng Chen (Chinese Geographical Science, 2017)

Prestack density inversion using the Fatti equation constrained by the P- and S-wave impedance and density - Li-Feng Liang; Hong-Bing Zhang; Zhi-Wei Dan; Zi-Qiang Xu; Xiu-Juan Liu; Cheng-Hao Cao (Applied Geophysics, 2017)

Functional identification of apple MdJAZ2 in Arabidopsis with reduced JA-sensitivity and increased stress tolerance - Xiu-Hong An; Yu-Jin Hao; En-Mao Li; Kai Xu; Cun-Gang Cheng (Plant Cell Reports, 2017)

Permian–Triassic boundary microbialites (PTBMs) in southwest China: implications for paleoenvironment reconstruction - Hao Tang; Stephen Kershaw; Hong Liu; Xiucheng Tan; Fei Li; Guang Hu; Cheng Huang; Lichao Wang; Chengbo Lian; Ling Li; Xuefei Yang (Facies, 2017)

Associations of TNF-α and IL-6 polymorphisms with osteoporosis through joint effects and interactions with LEPR gene in Taiwan: Taichung Community Health Study for Elders (TCHS-E) - Cheng-Chieh Lin; Tsai-Chung Li; Chiu-Shong Liu; Chuan-Wei Yang; Chih-Hsueh Lin; Jen-Hao Hsiao; Nai-Hsin Meng; Wen-Yuan Lin; Li-Na Liao; Chia-Ing Li; Fang-Yang Wu (Molecular Biology Reports, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Antidepressant-like effects of standardized gypenosides: involvement of brain-derived neurotrophic factor signaling in hippocampus - Rong-Hao Mu; Xiao-Yan Fang; Shuang-Shuang Wang; Cheng-Fu Li; Shao-Mei Chen; Xue-Mei Chen; Qing Liu; Yu-Cheng Li; Li-Tao Yi (Psychopharmacology, 2016)

Differential allocation of carbon in fenced and clipped grasslands: a 13C tracer study in the semiarid Chinese Loess Plateau - Jie Wei; Weiguo Liu; Hao Wan; Jimin Cheng; Weijun Li (Plant and Soil, 2016)

G protein-coupled estrogen receptor inhibits the P2Y receptor-mediated Ca2+ signaling pathway in human airway epithelia - Yuan Hao; Alison W. Chow; Wallace C. Yip; Chi H. Li; Tai F. Wan; Benjamin C. Tong; King H. Cheung; Wood Y. Chan; Yangchao Chen; Christopher H. Cheng; Wing H. Ko (Pflügers Archiv - European Journal of Physiology, 2016)

Highly selective and efficient biotransformation of linarin to produce tilianin by naringinase - Pan Cui; Tong-Yi Dou; Shi-Yang Li; Jun-Xia Lu; Li-Wei Zou; Ping Wang; Yan-Ping Sun; Da-Cheng Hao; Guang-Bo Ge (Biotechnology Letters, 2016)

A pilot study on using chlorine dioxide gas for disinfection of gastrointestinal endoscopes - Ying Yi; Li-mei Hao; Shu-ren Ma; Jin-hui Wu; Tao Wang; Song Lin; Zong-xing Zhang; Jian-cheng Qi (Journal of Zhejiang University-SCIENCE B, 2016)

A novel short anionic antibacterial peptide isolated from the skin of Xenopus laevis with broad antibacterial activity and inhibitory activity against breast cancer cell - Siming Li; Linlin Hao; Wanguo Bao; Ping Zhang; Dan Su; Yunyun Cheng; Linyan Nie; Gang Wang; Feng Hou; Yang Yang (Archives of Microbiology, 2016)

SSR-based genetic mapping and QTL analysis for timing of spring bud flush, young shoot color, and mature leaf size in tea plant (Camellia sinensis) - Li-Qiang Tan; Li-Yuan Wang; Li-Yi Xu; Li-Yun Wu; Min Peng; Cheng-Cai Zhang; Kang Wei; Pei-Xian Bai; Hai-Lin Li; Hao Cheng; Gui-Nian Qi (Tree Genetics & Genomes, 2016)

Evaluation of the major royal jelly proteins as an alternative to fetal bovine serum in culturing human cell lines - Di Chen; Xiao-xuan Xin; Hao-cheng Qian; Zhang-yin Yu; Li-rong Shen (Journal of Zhejiang University-SCIENCE B, 2016)

Sustainability from a Chinese cultural perspective: the implications of harmonious development in environmental management - Ying Li; Hao Cheng; R. J. S. Beeton; Thomas Sigler; Anthony Halog (Environment, Development and Sustainability, 2016)

Analysis of EDZ Development of Columnar Jointed Rock Mass in the Baihetan Diversion Tunnel - Xian-Jie Hao; Xia-Ting Feng; Cheng-Xiang Yang; Quan Jiang; Shao-Jun Li (Rock Mechanics and Rock Engineering, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Distribution and linkage disequilibrium analysis of polymorphisms of GH1 gene in different populations of pigs associated with body size - YUNYUN CHENG; SONGCAI LIU; DAN SU; CHAO LU; XIN ZHANG; QINGYAN WU; SIMING LI; HAOYU FU; HAO YU; LINLIN HAO (Journal of Genetics, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Identification of a regulatory element responsible for salt induction of rice OsRAV2 through ex situ and in situ promoter analysis - Yong-Bo Duan; Juan Li; Rui-Ying Qin; Rong-Fang Xu; Hao Li; Ya-Chun Yang; Hui Ma; Li Li; Peng-Cheng Wei; Jian-Bo Yang (Plant Molecular Biology, 2016)

Concomitant coronary and renal revascularization improves left ventricular hypertrophy more than coronary stenting alone in patients with ischemic heart and renal disease - Hao-jian Dong; Cheng Huang; De-mou Luo; Jing-guang Ye; Jun-qing Yang; Guang Li; Jian-fang Luo; Ying-ling Zhou (Journal of Zhejiang University-SCIENCE B, 2016)

Rapid and quantitative detection of Pythium inflatum by real-time fluorescence loop-mediated isothermal amplification assay - Yanyong Cao; Yongqiang Li; Jingjing Li; Lifeng Wang; Zeqiang Cheng; Hao Wang; Zaifeng Fan; Huiyong Li (European Journal of Plant Pathology, 2016)

A novel soil manganese mechanism drives plant species loss with increased nitrogen deposition in a temperate steppe - Qiuying Tian; Nana Liu; Wenming Bai; Linghao Li; Jiquan Chen; Peter B. Reich; Qiang Yu; Dali Guo; Melinda D. Smith; Alan K. Knapp; Weixin Cheng; Peng Lu; et al. (Ecology, 2016)
Loss of plant diversity with increased anthropogenic nitrogen (N) deposition in grasslands has occurred globally. In most cases, competitive exclusion driven by preemption of light or space is invoked as a key mechanism. Here, we provide evidence from a 9‐yr N‐addition experiment for an alternative mechanism: differential sensitivity of forbs and grasses to increased soil manganese (Mn) levels. In Inner Mongolia steppes, increasing the N supply shifted plant community composition from grass–forb codominance (primarily Stipa krylovii and Artemisia frigida , respectively) to exclusive dominance by grass, with associated declines in overall species richness. Reduced abundance of forbs was linked to soil acidification that increased mobilization of soil Mn, with a 10‐fold greater accumulation of Mn in forbs than in grasses. The enhanced accumulation of Mn in forbs was correlated with reduced photosynthetic rates and growth, and is consistent with the loss of forb species. Differential accumulation of Mn between forbs and grasses can be linked to fundamental differences between dicots and monocots in the biochemical pathways regulating metal transport. These findings provide a mechanistic explanation for N‐induced species loss in temperate grasslands by linking metal mobilization in soil to differential metal acquisition and impacts on key functional groups in these ecosystems.

IL-17A enhances ADAMTS-7 expression through regulation of TNF-α in human nucleus pulposus cells - Shuai-Shuai Wang; Wei Zhang; Yuan-Qiang Zhang; Yunpeng Zhao; Yi Liu; Jing-kun Li; Hao-xuan Zhang; Lei Cheng; Lin Nie (Journal of Molecular Histology, 2015)

Effects of Cu2+ and Zn2+ on growth and physiological characteristics of green algae, Cladophora - De-ju Cao; Pan-pan Xie; Juan-wei Deng; Hui-min Zhang; Ru-xiao Ma; Cheng Liu; Ren-jing Liu; Yue-gan Liang; Hao Li; Xiao-dong Shi (Environmental Science and Pollution Research, 2015)

Fingerprinting 128 Chinese clonal tea cultivars using SSR markers provides new insights into their pedigree relationships - Li-Qiang Tan; Min Peng; Li-Yi Xu; Li-Yuan Wang; Sheng-Xiang Chen; Yao Zou; Gui-Nian Qi; Hao Cheng (Tree Genetics & Genomes, 2015)

Retraction Note to: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2015)

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

Cloning of the Aegiceras corniculatum class I chitinase gene (AcCHI I) and the response of AcCHI I mRNA expression to cadmium stress - Li-Ying Wang; You-Shao Wang; Hao Cheng; Jing-Ping Zhang; Foong Swee Yeok (Ecotoxicology, 2015)

Characterization and expression analysis of a gene encoding CBF/DREB1 transcription factor from mangrove Aegiceras corniculatum - Ya-Lan Peng; You-Shao Wang; Hao Cheng; Li-Ying Wang (Ecotoxicology, 2015)

Influence of deep-frying using various commercial oils on acrylamide formation in French fries - Hao Zhang; Hui Zhang; Lilin Cheng; Li Wang; Haifeng Qian (Food Additives & Contaminants: Part A, 2015)

Evolutionary and expression analysis of a MADS-box gene superfamily involved in ovule development of seeded and seedless grapevines - Li Wang; Xiangjing Yin; Chenxia Cheng; Hao Wang; Rongrong Guo; Xiaozhao Xu; Jiao Zhao; Yi Zheng; Xiping Wang (Molecular Genetics and Genomics, 2015)

Two Different Emission-Wavelength Fluorescent Probes for Aluminum Ion based on Tunable Fluorophores in Aqueous Media - Yanxia Li; Zengchen Liu; Wenping Zhu; Hao Fu; Yongjie Ding; Jianping Xie; Weijie Yang; Lili Li; Chao Cheng (Journal of Fluorescence, 2015)

Insufficient secretion of IL-10 by Tregs compromised its control on over-activated CD4+ T effector cells in newly diagnosed adult immune thrombocytopenia patients - Feng Li; Lili Ji; Weiguang Wang; Fanli Hua; Yanxia Zhan; Shanhua Zou; Ling Yuan; Yang Ke; Zhihui Min; Dongli Song; Lihua Sun; Hao Chen; et al. (Immunologic Research, 2015)

Activation of Extracellular Signal-Regulated Kinase1/2 in the Medial Prefrontal Cortex Contributes to Stress-Induced Hyperalgesia - Jian Qi; Chen Chen; Ya-Cheng Lu; Ting Zhang; Hao Xu; Yuan-Yuan Cui; Yan-Zhou Chen; Wen Wang; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2014)

Isolation and functional characterization of a novel rice constitutive promoter - Juan Li; Rong-Fang Xu; Rui-Ying Qin; Hui Ma; Hao Li; Ying-Ping Zhang; Li Li; Peng-Cheng Wei; Jian-Bo Yang (Plant Cell Reports, 2014)

RETRACTED ARTICLE: Analyzing time-series microarray data reveals key genes in spinal cord injury - Xun Xia; Bo Qu; Yuan Ma; Li-bin Yang; Hai-dong Huang; Jing-ming Cheng; Tao Yang; Bin Kong; En-yu Liu; Kai Zhao; Wei-qi He; Xue-min Xing; et al. (Molecular Biology Reports, 2014)

Use of single nucleotide polymorphisms and haplotypes to identify genomic regions associated with protein content and water-soluble protein content in soybean - Dan Zhang; Guizhen Kan; Zhenbin Hu; Hao Cheng; Yu Zhang; Qing Wang; Hui Wang; Yuming Yang; Hongyan Li; Derong Hao; Deyue Yu (Theoretical and Applied Genetics, 2014)

Two Chinese pedigrees for adenomatous polyposis coli: new mutations at codon 1309 and predisposition to phenotypic variations - Dai-Xiang Liao; Bing Li; Xue-Mei Du; Jun-Hui Yu; Hong Chang; Zhi-Qiang Wu; Hao-Jie Hao; You-Xin Wang; Wei-Dong Han; Shu-jun Cheng; Cheng-Hua Luo (Familial Cancer, 2014)

Sensitisation of ovarian cancer cells to cisplatin by flavonoids from Scutellaria barbata - Jie Li; Yun Wang; Jia-Chuan Lei; Yang Hao; Yuan Yang; Cheng-Xiong Yang; Jian-Qing Yu (Natural Product Research, 2014)

Contrasting patterns of ovarian development and oogenesis in two sympatric host-feeding parasitoids, Diglyphus isaea and Neochrysocharis formosa (Hymenoptera: Eulophidae) - Wan-Xue Liu; Wei Wang; Li-Sheng Cheng; Jian-Yang Guo; Fang-Hao Wan (Applied Entomology and Zoology, 2014)

Two Novel Susceptibility SNPs for Ischemic Stroke Using Exome Sequencing in Chinese Han Population - Yanwei Zhang; Yeqing Tong; Yong Zhang; Hu Ding; Hao Zhang; Yijie Geng; Renli Zhang; Yuebin Ke; Jingjun Han; Zhixiang Yan; Li Zhou; Tangchun Wu; et al. (Molecular Neurobiology, 2014)

Isolation and characterization of OsMY1, a putative partner of OsRac5 from Oryza sativa L. - Wei-Hong Liang; Hua-Hua Wang; Hui Li; Jun-Jie Wang; Dan-Dan Yang; Yu-Fan Hao; Jia-Jia Li; Chen Lou; Qun-Ting Lin; Cheng-Qian Hou (Molecular Biology Reports, 2014)

The anti-adipogenic effect of PGRN on porcine preadipocytes involves ERK1,2 mediated PPARγ phosphorylation - Hao Yang; Jia Cheng; Ziyi Song; Xinjian Li; Zhenyu Zhang; Yin Mai; Weijun Pang; Xin’e Shi; Gongshe Yang (Molecular Biology Reports, 2013)

Effects of pH, Fe, and Cd on the uptake of Fe2+ and Cd2+ by rice - Danqing Liu; Chunhua Zhang; Xue Chen; Yazhou Yang; Shu Wang; Yujiao Li; Hao Hu; Ying Ge; Wangda Cheng (Environmental Science and Pollution Research, 2013)

Minocycline accelerates hypoxia-inducible factor-1 alpha degradation and inhibits hypoxia-induced neovasculogenesis through prolyl hydroxylase, von Hippel–Lindau-dependent pathway - Ching-Hao Li; Po-Lin Liao; Ya-Ting Yang; Shih-Hsuan Huang; Cheng-Hui Lin; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2013)

Assessment of private economic benefits and positive environmental externalities of tea plantation in China - Hui Xue; Xiaoyi Ren; Shiyu Li; Xu Wu; Hao Cheng; Bin Xu; Baojing Gu; Guofu Yang; Changhui Peng; Ying Ge; Jie Chang (Environmental Monitoring and Assessment, 2013)

Identification of miR-221 and -222 as important regulators in genotype IV swine hepatitis E virus ORF3-expressing HEK 293 cells - Ying Cheng; Li Du; Qiaoyun Shi; Hanwei Jiao; Xiaoru Zhang; Yongchang Hao; Hui Rong; Jianing Zhang; Xiaoxiao Jia; Shiyu Guo; Wenhua Kuang; Hui Zhang; et al. (Virus Genes, 2013)

Effective inhibition of mRNA accumulation and protein expression of H5N1 avian influenza virus NS1 gene in vitro by small interfering RNAs - Hanwei Jiao; Li Du; Yongchang Hao; Ying Cheng; Jing Luo; Wenhua Kuang; Donglin Zhang; Ming Lei; Xiaoxiao Jia; Xiaoru Zhang; Chao Qi; Hongxuan He; et al. (Folia Microbiologica, 2013)

The combined effects of transforming growth factor-β and basic fibroblast growth factor on the human degenerated nucleus pulposus cells in monolayer culture - Erxing He; Ji Hao Cui; Chuang Li; Cheng Tang; In-Sung Kim; Young-Woo Kim; Ho-Guen Chang; Jae-Ryong Cha; Oh-Jong Byung; Yong-Chan Kim (Tissue Engineering and Regenerative Medicine, 2013)

Estimating primaries by sparse inversion of the 3D curvelet transform and the L1-norm constraint - Fei Feng; De-Li Wang; Heng Zhu; Hao Cheng (Applied Geophysics, 2013)

Molecular cloning and functional analysis of a blue light receptor gene MdCRY2 from apple (Malus domestica) - Yuan-Yuan Li; Ke Mao; Cheng Zhao; Xian-Yan Zhao; Rui-Fen Zhang; Hua-Lei Zhang; Huai-Rui Shu; Yu-Jin Hao (Plant Cell Reports, 2013)

Imposex effects on the veined rapa whelk (Rapana venosa) in Bohai Bay, China - Li-hui An; Yanqiang Zhang; Shuang-shuang Song; Yue Liu; Zi-cheng Li; Hao Chen; Xing-ru Zhao; Kun Lei; Junmin Gao; Bing-hui Zheng (Ecotoxicology, 2013)

Changes in the BAG1 Expression of Schwann Cells After Sciatic Nerve Crush - Hao Wu; Yonghua Liu; Yuan Zhou; Long Long; Xinghai Cheng; Lei Ji; Hai Weng; Tao Ding; Jiao Yang; Haixiang Wei; Ming Li; Weipeng Huan; et al. (Journal of Molecular Neuroscience, 2013)

Temporal and Spatial Expression of KIF3B after Acute Spinal Cord Injury in Adult Rats - Xiaowei Yu; Hai Wen; Jianhua Cao; Binbin Sun; Tao Ding; Ming Li; Hao Wu; Long Long; Xinghai Cheng; Guangfei Xu; Feng Zhang (Journal of Molecular Neuroscience, 2013)

Agrobacterium tumefaciens-mediated transformation of Phellodendron amurense Rupr. using mature-seed explants - Jingli Yang; Bo Zhao; Yeon Bok Kim; Chenguang Zhou; Chunyan Li; Yunlin Chen; Haizhen Zhang; Cheng Hao Li (Molecular Biology Reports, 2013)

Transforming growth factor-β1 induces matrix metalloproteinase-9 expression in rat vascular smooth muscle cells via ROS-dependent ERK–NF-κB pathways - Hao Zhang; Zhi-Wei Wang; Hong-Bing Wu; Zhi Li; Luo-Cheng Li; Xiao-Ping Hu; Zong-Li Ren; Bai-Jun Li; Zhi-Peng Hu (Molecular and Cellular Biochemistry, 2012)

Characterization of a Novel Pollen-Specific Promoter from Wheat (Triticum Aestivum L.) - Ling Chen; Yingjie Miao; Cheng Wang; Peipei Su; Tianheng Li; Rong Wang; Xinglong Hao; Guangxiao Yang; Guangyuan He; Chunbao Gao (Plant Molecular Biology Reporter, 2012)

Usefulness of Speckle Tracking Imaging to Assess Myocardial Contractility in Intra-Abdominal Hypertension: Study in a Mini-Pig Model - Wen-Hua Du; Wang Xiang; Dao-Cheng Liu; Lian-Yang Zhang; Tao Li; Shi-Jin Sun; Hao Tan (Cell Biochemistry and Biophysics, 2012)

A fully automatic registration approach based on contour and SIFT for HJ-1 images - XiLiang Ni; ChunXiang Cao; Lin Ding; Tao Jiang; Hao Zhang; HuiCong Jia; GuangHe Li; Jian Zhao; Wei Chen; Wei Ji; Min Xu; MengXu Gao; et al. (Science China Earth Sciences, 2012)

Effects of copper on growth, radial oxygen loss and root permeability of seedlings of the mangroves Bruguiera gymnorrhiza and Rhizophora stylosa - Hao Cheng; Nora Fung-Yee Tam; Youshao Wang; Shiyu Li; Guizhu Chen; Zhihong Ye (Plant and Soil, 2012)

Ten paths of PKA signaling pathway regulate hepatocyte proliferation in rat liver regeneration - Zhenchao Cheng; Lijuan Duan; Xiaoxia Hao; Zhanpeng Li; Gaiping Wang; Cunshuan Xu (Genes & Genomics, 2012)

Vegetation and climate of the Lop Nur area, China, during the past 7 million years - Hui Hao; David K. Ferguson; Hong Chang; Cheng-Sen Li (Climatic Change, 2012)

Concentrations of polycyclic aromatic hydrocarbon in the surface sediments from inter-tidal areas of Kenting coast, Taiwan - Jing-O Cheng; Fung-Chi Ko; Jan-Jung Li; Te-Hao Chen; Ying-Ming Cheng; Chon-Lin Lee (Environmental Monitoring and Assessment, 2012)

Activation of transcriptional activity of HSE by a novel mouse zinc finger protein ZNFD specifically expressed in testis - Fengqin Xu; Weiping Wang; Chen Lei; Qingmei Liu; Hao Qiu; Vinaydhar Muraleedharan; Bin Zhou; Hongxia Cheng; Zhongkai Huang; Weian Xu; Bichun Li; Minghua Wang (Molecular and Cellular Biochemistry, 2012)

Unloading the infarcted heart affect MMPs–TIMPs axis in a rat cardiac heterotopic transplantation model - Wei-jian Wang; Zi-li Meng; Yun-chang Mo; Jun-wei Liu; Cheng-chao Sun; Sheng-shou Hu; Hao Zhang (Molecular Biology Reports, 2012)

Construction and characterization of a normalized cDNA library from the river snail Bellamya aeruginosa after exposure to copper - Zi-Cheng Li; Li-Hui An; Qing Fu; Ying Liu; Lei Zhang; Hao Chen; Xing-Ru Zhao; Li-Jing Wang; Bing-Hui Zheng; Lin-Bo Zhang (Ecotoxicology, 2012)

Progress in monitoring high-temperature damage to rice through satellite and ground-based optical remote sensing - JiaHua Zhang; FengMei Yao; BingBai Li; Hao Yan; YingYu Hou; GaoFeng Cheng; Vijendra Boken (Science China Earth Sciences, 2011)

Replicative senescence of human bone marrow and umbilical cord derived mesenchymal stem cells and their differentiation to adipocytes and osteoblasts - HuanChen Cheng; Lin Qiu; Jun Ma; Hao Zhang; Mei Cheng; Wei Li; Xuefei Zhao; Keyu Liu (Molecular Biology Reports, 2011)

Induction of somatic embryogenesis from female flower buds of elite Schisandra chinensis - Jing Li Yang; Yu Da Niu; Chuan Ping Yang; Gui Feng Liu; Cheng Hao Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Shiga toxin type 2 (Stx2), a potential agent of bioterrorism, has a short distribution and a long elimination half-life, and induces kidney and thymus lesions in rats - Yue-Nan Liu; Sheng-han Wang; Tao Li; Qin Wang; Wei Tu; Kun Cai; Xiao-Jun Hou; Ren-Mao Tian; Xiang Gao; Hao Liu; Le Xiao; Jing Shi; et al. (Archives of Toxicology, 2011)

Initial research on the polarized reflectance of typical urban surface types measured by the Directional Polarimetric Camera - DongHai Xie; XingFa Gu; TianHai Cheng; Tao Yu; ZhengQiang Li; XingFeng Chen; Hao Chen; Jing Guo (Science China Earth Sciences, 2011)

Interaction of green tea polyphenol epigallocatechin-3-gallate with sunitinib: potential risk of diminished sunitinib bioavailability - Jun Ge; Ben-Xu Tan; Ye Chen; Li Yang; Xing-Chen Peng; Hong-Ze Li; Hong-Jun Lin; Yu Zhao; Meng Wei; Ke Cheng; Long-Hao Li; Hang Dong; et al. (Journal of Molecular Medicine, 2011)

RNA Interference Induces Effective Inhibition of mRNA Accumulation and Protein Expression of SHEV ORF3 Gene In vitro - Tao Liu; Ming Lei; Hanwei Jiao; Li Du; Ying Cheng; Donglin Zhang; Yongchang Hao; Churiga Man; Fengyang Wang (Current Microbiology, 2011)

Characterization and prediction of mRNA polyadenylation sites in human genes - Tzu-Hao Chang; Li-Ching Wu; Yu-Ting Chen; Hsien-Da Huang; Baw-Jhiune Liu; Kuang-Fu Cheng; Jorng-Tzong Horng (Medical & Biological Engineering & Computing, 2011)

Significant association of SNP rs2106261 in the ZFHX3 gene with atrial fibrillation in a Chinese Han GeneID population - Cong Li; Fan Wang; Yanzong Yang; Fenfen Fu; Chengqi Xu; Lisong Shi; Sisi Li; Yunlong Xia; Gang Wu; Xiang Cheng; Hui Liu; Chuchu Wang; et al. (Human Genetics, 2011)

Quantitative estimation of the shrub canopy LAI from atmosphere-corrected HJ-1 CCD data in Mu Us Sandland - Wei Chen; ChunXiang Cao; QiSheng He; HuaDong Guo; Hao Zhang; RenQiang Li; Sheng Zheng; Min Xu; MengXu Gao; Jian Zhao; Sha Li; XiLiang Ni; et al. (Science China Earth Sciences, 2010)

Development of a large-scale isolation chamber system for the safe and humane care of medium-sized laboratory animals harboring infectious diseases - Xin Pan; Jian-cheng Qi; Ming Long; Hao Liang; Xiao Chen; Han Li; Guang-bo Li; Hao Zheng (Journal of Zhejiang University-SCIENCE B, 2010)

Callus induction and high-efficiency plant regeneration via somatic embryogenesis in Papaver nudicaule L., an ornamental medicinal plant - Jing Li Yang; Bo Zhao; Eun Soo Seong; Myong Jo Kim; Won Hee Kang; Na Young Kim; Chang Yeon Yu; Cheng Hao Li (Plant Biotechnology Reports, 2010)

High-frequency somatic embryogenesis from germinated zygotic embryos of Schisandra chinensis and evaluation of the effects of medium strength, sucrose, GA3, and BA on somatic embryo development - Ai Hua Chen; Jing Li Yang; Yu Da Niu; Chuan Ping Yang; Gui Feng Liu; Chang Yeon Yu; Cheng Hao Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

A Comprehensive Study of Deep Catalytic Oxidation of Benzene, Toluene, Ethyl Acetate, and their Mixtures over Pd/ZSM-5 Catalyst: Mutual Effects and Kinetics - Chi He; Peng Li; Jie Cheng; Zheng-Ping Hao; Zhi-Ping Xu (Water, Air, & Soil Pollution, 2010)

Modeling air gun signatures in marine seismic exploration considering multiple physical factors - Guo-Fa Li; Ming-Qiang Cao; Hao-Lin Chen; Cheng-Zhou Ni (Applied Geophysics, 2010)

Early Paleocene vegetation and climate in Jiayin, NE China - Hui Hao; David K. Ferguson; Guang-Ping Feng; Albert Ablaev; Yu-Fei Wang; Cheng-Sen Li (Climatic Change, 2010)

Molecular analysis of an actin gene, CarACT1, from chickpea (Cicer arietinum L.) - Hui Peng; Huiying Cheng; Xingwang Yu; Qinghua Shi; Hua Zhang; Jiangui Li; Hao Ma (Molecular Biology Reports, 2010)

Direct somatic embryogenesis from pericycle cells of broccoli (Brassica oleracea L. var. italica) root explants - J. L. Yang; E. S. Seong; M. J. Kim; B. K. Ghimire; W. H. Kang; Chang Yeon Yu; Cheng Hao Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Intercropping alleviates the inhibitory effect of N fertilization on nodulation and symbiotic N2 fixation of faba bean - Yu-Ying Li; Chang-Bin Yu; Xu Cheng; Chun-Jie Li; Jian-Hao Sun; Fu-Suo Zhang; Hans Lambers; Long Li (Plant and Soil, 2009)

Isolation of a gene encoding endoglucanase activity from uncultured microorganisms in buffalo rumen - Li Liu; Yi Feng; Cheng-Jie Duan; Hao Pang; Ji-Liang Tang; Jia-Xun Feng (World Journal of Microbiology and Biotechnology, 2009)

Evolution of the Chloroplast trnL-trnF Region in the Gymnosperm Lineages Taxaceae and Cephalotaxaceae - Da Cheng Hao; Bei Li Huang; Shi Lin Chen; Jun Mu (Biochemical Genetics, 2009)

Somatic embryogenesis and plant regeneration in elite genotypes of Picea koraiensis - Cheng-Hao Li; Bao-Guang Liu; Tae-Dong Kim; Heung-Kyu Moon; Yong-Eui Choi (Plant Biotechnology Reports, 2008)

Protein C -1641A/-1654C haplotype is associated with organ dysfunction and the fatal outcome of severe sepsis in Chinese Han population - Qi Xing Chen; Shui Jing Wu; Hai Hong Wang; Chen Lv; Bao Li Cheng; Guo Hao Xie; Xiang Ming Fang (Human Genetics, 2008)

Genome-wide identification and characterization of putative cytochrome P450 genes in the model legume Medicago truncatula - Lingyong Li; Hao Cheng; Junyi Gai; Deyue Yu (Planta, 2007)

A Feasible and Quantitative Encoding Method for Microbeads with Multicolor Quantum Dots - Hai-Qiao Wang; Zhen-Li Huang; Tian-Cai Liu; Jian-Hao Wang; Yuan-Cheng Cao; Xiao-Feng Hua; Xiu-Qing Li; Yuan-Di Zhao (Journal of Fluorescence, 2007)

A gaussian-box modeling approach for urban air quality management in a Northern Chinese City—II. pollutant emission abatement - Shuiyuan Cheng; Jianbing Li; Beng Feng; Yuquan Jin; Ruixia Hao (Water, Air, & Soil Pollution, 2007)

A gaussian-box modeling approach for urban air quality management in a northern chinese city—I. model development - Shuiyuan Cheng; Jianbing Li; Beng Feng; Yuquan Jin; Ruixia Hao (Water, Air, & Soil Pollution, 2007)

Haplotype Frequency Distribution and Linkage Disequilibrium Analysis of Single Nucleotide Polymorphisms at the Human FMO3 Gene Locus - Da-Cheng Hao; Jie Sun; Bjarte Furnes; Daniel Schlenk; Zhen-Fang Hou; Ya-Ping Zhang; Sheng-Li Yang; Ling Yang (Biochemical Genetics, 2006)

Inhibitory effect of medroxyprogesterone acetate on human liver cytochrome P450 enzymes - Jiang-Wei Zhang; Yong Liu; Wei Li; Da-Cheng Hao; Ling Yang (European Journal of Clinical Pharmacology, 2006)

Application of swat model in the upstream watershed of the Luohe River - Xue-song Zhang; Fang-hua Hao; Hong-guang Cheng; Dao-feng Li (Chinese Geographical Science, 2003)

Alpha-naphthoflavone induces vasorelaxation through the induction of extracellular calcium influx and NO formation in endothelium - Yu-Wen Cheng; Ching-Hao Li; Chen-Chen Lee; Jaw-Jou Kang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2003)